Foam separation and coupled technologies in food industry: a review - Qing Li; Zhijie Guan; Mengting Gu; Tong Chen; Jiacong Wu; Lei Wang; Yun Wang; Juan Han (Journal of Food Engineering, 2027)

Occurrence and ecological risks of microplastics and bisphenol A in a coastal receiving environment affected by wastewater from a large-scale plastic production enterprise - Ziwei Han; Fei Gu; Bingbing Guo; Changzheng Cui (Marine Pollution Bulletin, 2026)

Artificial intelligence-assisted phenotypic monitoring and diagnostic of wastewater microbiome management towards sustainability - Zijian Wang; Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Peisheng He; Annalisa Onnis-Hayden; Nicholas B. Tooker; Zijun Meng; Mark Wallace Miller; Kester McCullough; Stephanie Klaus; et al. (Water Research, 2026)

A scale-undistorted test prediction method for ultra-high core earth-rockfill dam using multi-scale dynamic centrifuge model tests - Chaojun Han; Zhenggang Zhan; Sheng Zhu; Xingwen Gu; Wenjing Niu (Soil Dynamics and Earthquake Engineering, 2026)

Decoupling nitrous oxide emissions from carbon footprint in full-scale completely autotrophic nitrogen removal over nitrite process: key drivers and sustainability assessment - Songqing Huang; Pengchao Gu; Xiuhong Liu; Xiaoyu Han; Xinyue Cao; Yufan Dong; Jikai Lyu; Chenduo Huang; Qing Yang (Bioresource Technology, 2026)

Numerical optimization of the equivalent ring source criterion in dual detector improved segmented gamma scanning - Shiwei Liao; Weiguo Gu; Dezhong Wang; Liandong Zhang; Yufei Han (Annals of Nuclear Energy, 2026)

Rapid detection of maize seed vigor via multi-branch interpretable deep learning integrated with multimodal data fusion optimized by environmental factors - He Li; Yilin Mao; Ruisha Xie; Hongtao Shi; Han Zhang; Yinlin Chen; Xuelei Yang; Riliang Gu; Sun Qun (Computers and Electronics in Agriculture, 2026)

Petrogenesis of Late Triassic high-Mg diorites and adakitic rocks in the East Kunlun Orogenic Belt and implications for Paleo-Tethyan evolution - Yu Zhao; Yongmei Zhang; Xuexiang Gu; Yunhang Hu; Jianhua Han; Wei Chen; Hao Shi; Huadong Ma; Bingyu Zhu (Lithos, 2026)

Discovery of skarn mineralization and exploration implications for the Qukulekedong Au–Sb deposit, western East Kunlun, NW China - Yu Zhao; Yongmei Zhang; Xuexiang Gu; Yunhang Hu; Jianhua Han; Wei Chen; Hao Shi; Huadong Ma; Bingyu Zhu (Journal of Geochemical Exploration, 2026)

The role of trade protectionism and local industry support policies in low carbon technologies trade - Donghui Yu; Baihe Gu; Jing Han (Energy Policy, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Preparation of coal gasification coarse slag-based low-carbon cementitious materials based on supersulfated cement system: matching mechanism between reaction path induced by multi-mineral salts and mechanical properties - Xiaowei Ge; Xiaowei Gu; Ziyang Hu; Shenyu Wang; Xu Wang; Shaoqian Liu; Xuecheng Ding; Jinchi Han; Jianping Liu; Hao Wang; Xuemei Liu (Chemical Engineering Journal, 2026)

Slope gradient effects on train vibration induced seepage-pathway transition and shallow failure in sandy loess railway slopes - Kai Han; Jiading Wang; Peng Xiao; Dengfei Zhang; Tao Xiao; Qi Gu (Transportation Geotechnics, 2026)

A fast-response framework for real-time 3D wind field reconstruction: Supporting urban air mobility applications in complex environments - Zihao Pang; Junxia Gu; Quanqian Xu; Shuai Han; Lanxin Luo; Zhiqiang Zhang; Zhi Zhu; Tao Zhang; Yaping Ma; Dongdong Shen (Sustainable Cities and Society, 2026)

Hydrogeochemical insights into the salinization and sustainable development of surface and subsurface water in a typical hyper-arid watershed on Tibetan Plateau - Yuqing Zhang; Yong Xiao; Xu Guo; Jiahao Liu; Jianping Wang; Liang Chang; Jibin Han; Nuan Yang; Zexue Qi; Xiaofan Gu; Jing Ning (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Dual-path activation mechanism of MnO-Mn5C2/CN in periodate systems for 4-chlorophenol degradation: Interface mediated radical and nonradical synergistic catalysis - Qi Zhang; Yao Dai; Siyuan Cao; Xu Yin; Liankai Gu; Yuanbo Zhou; Zhenshan Duan; Guoyan Luo; Siqi Liu; Kajia Wei; Weiqing Han (Journal of Environmental Chemical Engineering, 2026)

Sulfidation of copper oxide with CaSO4 for copper flotation: Experimental study and first-principles calculation - Xuesong Gao; Siwen Tan; Yongwei Wang; Kunhong Gu; Xinglan Cui; Junwei Han (Journal of Environmental Chemical Engineering, 2026)

Hydrometallurgical recovery of spent Li-ion batteries driven by thermal reduction: Opportunities, challenges, and prospects - Hui Liu; Jingkun Han; Yuheng Feng; Chongqing Nong; Jing Gu; Haoran Yuan (Journal of Environmental Chemical Engineering, 2026)

High-efficiency nitrogen removal of ammonium-rich photovoltaic wastewater via a pilot-scale two-stage partial nitritation/anammox system: Long-term performance and techno-economic assessment - Xin Gu; Haixu Shen; Xiang Li; Han Wang; Yayi Wang (Journal of Environmental Chemical Engineering, 2026)

Unlocking efficient Li recovery from spent LiFePO4 batteries at high pulp density: Passivation release mechanism of Fe3+-mediated biochemical synergistic leaching and life cycle assessment - Ziyun Liang; Jinghan Gu; Xin Zhao; Lang Yun; Shenghan Li; Zaiyu Li; Wenyan Liu; Jiali Wang; Yao Wang; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2026)

Response surface methodology-guided design of oil-in-water emulsions coated with complex coacervates for precision intestinal delivery of sulforaphane - Su Min Park; Jong Hyeon Han; Keun Woo Kang; Hyun Ju Lee; Hyeonjin Kim; Judong Yeo; Sung Gu Han (Food Chemistry, 2026)

Comparative metabolomics reveals distinct metabolic profiles and in vitro activities of fermented noni juice from Samoa and China's Hainan - Qianjin Ni; Meimei Nie; Linlin Han; Mingfei Gu; Lingming Xiong; Yayuan Xu; Lei Feng; Liying Niu; Runqiang Yang; Dajing Li; Zhuqing Dai (Food Chemistry, 2026)

Synthetic microbial community-mediated community assembly regulates flavor compound formation in light-aroma type baijiu fermentation - Xuri Zhang; Tiegang Gu; Yifu Zheng; Jingxin Yu; Jiangnan Han; Lina Tian; Qun Wu (Food Bioscience, 2026)

Targeting the gut-nasal axis: probiotic-induced intestinal immune homeostasis for allergic rhinitis management - Zhidong Han; Xuan Li; Jiamei Guo; Jiajia Wang; Shuguang Fang; Ying Wu; Shaobin Gu (Food Bioscience, 2026)

Research progress on the application of bacteriophages in the “from farm to table” food safety chain - Han Li; Min Yue; Wei Zhao; Chen Wang; Jianglu Gu; Yonghua Qi (Food Bioscience, 2026)

Rapid in-situ recovery of starved anammox consortia: Metabolic stimulation and microbial synergy driven by organics and oxygen - Yihao Qiu; Chenrong Gu; Jiaqi Han; Jiaqi Zhang; Qi Zhang; Rong Li; Xiao-Ming Ji (Environmental Research, 2026)

Process intensification of directed fine-particle transport by synthetic-jet-generated vortex rings: Experimental and numerical investigation - Mingming Chai; Jiaqi Ran; Hailin Gu; Huan Han (Chemical Engineering Journal, 2026)

Residual‑lithium-assisted ZrO2/Li3VO4 interphase reconstruction enables high electrochemical and thermal transport performances in all-solid-state lithium batteries - Haojun Xu; Jiaqi Gu; Fengming Ma; Guangwu Zhang; Tianli Han; Xiaofei Huang; Jinjin Li; Qiye Zheng; Jinyun Liu (Chemical Engineering Journal, 2026)

Highly linear and sensitive crack-based strain sensor based on multi-scale synergistic engineering - Guoliang Ma; Shenao Xiong; Kun Ma; Shilong Yan; Yan Qiao; Mengze Zhang; Congtian Gu; Hu Shen; Kaixian Ba; Yuan Wang; Jianhao Li; Bin Yu; et al. (Chemical Engineering Journal, 2026)

An elevation-dependent downscaling framework for reconstructing high-resolution daily air temperature over China from 1961 to 2024 - Aodong Du; Shuai Han; Yujing Liang; Junxia Gu; Tao Zhang; Chunxiang Shi (Atmospheric Research, 2026)

In-Season monitoring of rice phenology for massive germplasm resources using Explainable Machine learning and a Transformer CNN model - Xiaoxu Han; Yangyang Gu; Hengbiao Zheng; Di Wang; Fangming Wu; Meng Zhou; Hongxu Ai; Timothy A. Warner; Chongya Jiang; Tao Cheng; Yongchao Tian; Yan Zhu; et al. (Computers and Electronics in Agriculture, 2026)

Multimodal deep fusion of Low-Field NMR and proton Density-Weighted imaging for interpretable detection of Saline-Alkali stress in wheat - Ying Gu; Guoqing Feng; Ya’nan Zhou; Han Zhang; Cheng Wang; Liping Chen; Bin Luo (Computers and Electronics in Agriculture, 2026)

Viable lactic acid bacteria across the production-food-gut continuum: Multi-stress adaptation and robustness engineering - Jing Cui; Jiahui Li; Meijuan Ran; Qi Chen; Jiehong Fang; Jiankang Jiang; Qing Cao; Ping Li; Han Jiang; Qing Gu (Trends in Food Science & Technology, 2026)

Plasma metabolomics analysis reveals potential metabolic biomarkers for predicting mushroom poisoning - Yuanping Gu; Hao Cui; Zhuange Shi; Hao Jia; Yifan Wang; Siyuan Huang; Xiulin Zhang; Jing Han; Hongmei Wang; Xiao Chen; Guobing Chen; Jiangping Song (Toxicon, 2026)

Prediction of bending buckling in subsea lined pipes using FEM-based machine learning with equivalent geometric imperfection factor - Tianping Gu; Yuhang Han; Jianbing Zhang; Xin Wang; Ze Wu; Guangyuan Weng (Ocean Engineering, 2026)

Spatiotemporal migration of slip localization zones along the Hambaeksan Fault, South Korea - Jae Hoon Kim; Jin-Han Ree; Raehee Han; Chowon Park; Dohee Gu; Jusun Woo (Journal of Structural Geology, 2026)

Variation in chemical profiles and bioactivity of Myristica fragrans essential oils from different plant parts and distillation stages against Lasioderma serricorne (Coleoptera: Ptinidae) - Wang-Yu Zheng; Yuan Zhang; Yong-Qing Gu; Yu-Chen Zhang; Xiao-Yi Shi; Han-Yu He; Shu-Shan Du (Journal of Asia-Pacific Entomology, 2026)

Phylogeny contributes to sustaining the functional diversity of temperate forests under environmental change - Yue Gu; Junhui Zhang; Shijie Han (Forest Ecology and Management, 2026)

Rapid in-situ enrichment of anammox bacteria from activated sludge via nitrate induction: pilot-scale demonstration and mechanistic insights - Xin Gu; Haixu Shen; Hao Sheng; Xiang Li; Han Wang; Yayi Wang (Environmental Research, 2026)

Resource partitioning among three commercial fish species in the Yellow Sea off Korea using stomach content and stable isotope analyses - Joo Myun Park; Samroz Majeed; Min Gu Kang; Soo Jeong Lee; Yeonjung Lee; Dong Han Choi (Estuarine, Coastal and Shelf Science, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Multiscale solvation-electronic regulation strategy toward stable Zn anode - Jiaqi Li; Yushan Ma; Yicheng Wang; Shaoyu Zhang; Jiaming Li; Nan Li; Junyi Han; Hedong Gu; Zhanhong Yang; Xiaolei Wang (Chemical Engineering Journal, 2026)

From prediction to design: Optimized design of waste wood composites via GAN-augmented interpretable machine learning - Kongjie Gu; Junjie Xia; Shenjie Han; Xingying Zhang; Lu Li; Zhiqiang Dong; Liwen Zhou; Junfeng Hou (Bioresource Technology, 2026)

Transformation characteristics and mechanisms of phosphorus during supercritical water gasification of pig manure - Mingming Du; Jing Gu; Haoran Yuan; Yunan Chen; Jingkun Han; Jiaxin Liao (Biomass and Bioenergy, 2026)

Application of Fourier transform near-infrared (FT-NIR) spectroscopy and machine learning for non-destructive viability assessment of 20-year stored Pinus densiflora seeds - Da-Eun Gu; Ja-Jung Ku; Sim-Hee Han (New Forests, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Effect of Incidence Angle on Earthquake-Induced Landslides Through FDM–DEM: The Hongshiyan Rockslide (China) Case Study - Kunsheng Gu; Jian Zhou; Salvatore Martino; Xiao Peng; Fuchu Dai; Zunhong Ke; Luqing Zhang; Zhenhua Han (Rock Mechanics and Rock Engineering, 2026)

Macrophyte-to-algae transition: Suspended particulate matter mediates the bioavailability and retention of heavy metal(loid)s in the sediment - Wenxuan Han; Yiheng Du; Xue Sun; Zhaode Wang; Lei Zhang; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Journal of Environmental Chemical Engineering, 2026)

Microplastics threaten agroecosystem multifunctionality: A global systematic review with national-scale evidence from China - Zhongke Qu; Zexin Meng; Jie Han; Fulai Yan; Feng Wang; Fangyan Zhang; Yiping Wu; Huayang Zhen; Zhaolin Gu (Journal of Environmental Management, 2026)

Converted-wave Kirchhoff pre-stack depth migration based on multi-wave traveltime tables - Bingkai Han; Weijian Mao; Hanming Gu (Journal of Applied Geophysics, 2026)

Self-assembled micelles stabilized by covalent α-lipoic acid-carboxymethyl chitosan conjugates: Enabling stable delivery and glutathione-responsive release of coenzyme Q10 - Ling Liu; Jiangyue Wang; Rui Zhao; Meihan Wang; Qingzhuo Gu; Jiaqi Han; David Julian McClements; Xuebo Liu; Fuguo Liu (Food Research International, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

A cost-effective water cooled PEMFC bipolar plate with metal mesh flow field employing 2D fabrication process - Wenjun Li; Ruonan Ding; Weichang Gu; Wenrong Shi; Yingchao Shang; Liuyuan Han; Yang Liu; Yang Li; Fangyong Yu; Zhen Guo (Chemical Engineering Journal, 2026)

Integrated Analysis of Physiological, Histological, and Transcriptomic Responses to Transport Density in Schizothorax nukiangensis - Jinlin Wang; Yuting Duan; Dapeng Gu; Hejiao Li; Luo Lei; Ning Wang; Wenjia He; Yinhua Zhou; Rongrong Liao; Mei Peng; Xinyu Liu; Zhaofang Han; et al. (Marine Biotechnology, 2026)

Ubiquitin-mediated downregulation of the proteasome subunit ADRM1 mediates in vitro capacitation of bovine spermatozoa - Lipeng Cao; Chunyu Li; Yue Han; Yanqiu Lv; Jie Wang; Xinglin Qu; Yuyang Zhang; Weiyu Gu; Qinglong Xu; Shunfa Yao; Jinwei Lu; Aihui Lv; et al. (Animal Reproduction Science, 2026)

Exogenous phytohormones as protective agents against high light-induced bleaching in Betaphycus gelatinae - Zexu Liu; Haolong Zheng; Xiangyu Wu; Shouguo Yang; Han Yang; Yifang Zhao; Yixuan Xing; Xianming Tang; Zhifeng Gu; Yaohua Shi; Feng Yu (Journal of Applied Phycology, 2026)

Genome-wide identification and expression analysis of the pectate lyase (PEL) gene family in soybean (Glycine max (L.) Merr. ) - Shuo Wu; Wanqing Du; Yu Han; Zhenggang Wang; Yujuan Gu; Xianlong Ding; Shouping Yang (Genetica, 2026)

Advances in the principles and methods for nondestructive and noninvasive soil salinity measurements in the field: A review - Xiaocan Tang; Huijie Gu; Zhenxing Yan; Baoru Li; Zongzheng Yan; Dongxue Wu; Jie Han; Xiuwei Liu (Computers and Electronics in Agriculture, 2026)

Nitric oxide inhibitory and cytotoxic secondary metabolites from Talaromyces sp. BHM8-7 - Jae Sang Han; Dahyeon Lee; Jun Gu Kim; Joon Su Jang; Vu Quan Dang; Woo Jin Kim; Dongho Lee; Mi Kyeong Lee; Jin Woo Lee; Bang Yeon Hwang (Phytochemistry, 2026)

Seasonality and aerosol microenvironment-associated processing of organic aerosol in a humid inland city - Hyo-Won Lee; Ji-Won Jeon; Young-Ji Han; Seung-Ha Lee; Hyun-Gu Jung; Seung-Hwan Cha; Ha-Yoon Jeong; Jung-Min Park; Jefferey L. Collett Jr. (Journal of Hazardous Materials, 2026)

Advanced framework for evaluating energy saving potential across multiple building types via implementing multi-hybrid methods - Fenghua Xia; Luyue Han; Song Zhou; Wei Pan; Lei Zhang; Shoupu Gu; Xia Zhao (Energy and Buildings, 2026)

Hydroxyl-functionalized CAU-1 based mixed matrix membranes with enhanced interfacial compatibility for ethane/ethylene separation - Han Zhang; Lu Wang; Hao Zhang; Zhenjie Gu; Zhihua Qiao; Chongli Zhong (Chemical Engineering Journal, 2026)

Covalent organic frameworks membrane with gradient hydrophilic channel for moisture-enabled electric generation - Jun Zhang; Jing-Dong Feng; Ruo-Meng Zhu; Yong Liu; Yu-Ou He; Yu-Ting Que; Shuai Geng; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

A logic-gated immunotherapeutic nanoplatform amplifying antigen release via reprogrammed cell death for durable antitumor immunity - Yingjing Fang; Wang Yin; Nannan Han; Zheqing Li; Ading He; Yuan Zhang; Hao Gu; Meidong Lang; Min Ruan (Chemical Engineering Journal, 2026)

Chronic exposure to environmentally relevant Bisphenol F induces hepatic injury and inflammation in Zebrafish - Yuehong Shen; Dingyu Zhou; Tong Wei; Tuantuan Lei; Yuanhui Zhu; Mengyuan Liang; Junjie Sun; Peng Wang; Guixiang Ji; Jie Gu; Han Gao; Wenzhu Wu (Aquatic Toxicology, 2026)

Dynamic Failure Analysis of Rock Slopes with Discontinuous Joints Under Obliquely Incident SV Waves Using a FDM–DEM Coupling Method - Kunsheng Gu; Jian Zhou; Xiao Peng; Fuchu Dai; Hao Liu; Luqing Zhang; Zhenhua Han (Rock Mechanics and Rock Engineering, 2026)

Rapidly screening of pancreatic lipase inhibitors from Sibiraea angustata (rehd.) Hand.-Mazz. leaves using affinity ultrafiltration combined with HPLC-QTOFMS, molecular docking, targeted separation, and in vitro experimental verification - Hai Song; Yangfei Wei; Zhixiang Gu; Jiandong Han; Xiaojun Wang; Yongpeng Gong; Junke Wang (Natural Product Research, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

An integrated geochemical and isotopic framework for nitrate source apportionment in a shallow coastal aquifer under multiple environmental pressures - Sa Xiao; Ya Wang; Tao Gu; Xiaoli Yang; Ting Han; Chaoan Mai (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Long-term dynamics and circularity implications of brominated flame retardants in China’s plastics - Yujie Jia; Mengqi Han; Jiaqi Lu; Yilu Gu; Xin Liu; Xiaofeng Gao (Journal of Hazardous Materials, 2026)

Circular valorization of oil palm empty fruit bunch residue: Biochar-assisted SSF for enhanced bioethanol production - Yazhai Zhang; Hanqi Gu; Zhiyuan Han; Yuhan Liu; Shuai Gao; Aainaa Izyan Nafsun (Bioresource Technology Reports, 2026)

Piericidin F, a Novel Marine-Derived Piericidin Derivative, Degrades High-Risk HPV Oncoproteins E6/E7 by ROS-Dependent Ubiquitin Proteasome System and Induces Apoptosis in HeLa Cells - Weiyi Zhang; Yifan Chen; Yimin Chang; Xiaoning Han; Yufeng Yang; Qianqun Gu; Dehai Li; Ming Liu (Journal of Ocean University of China, 2026)

The protective shade alters prokaryotic community dynamics on sandstone biofilm: Evidence from DNA and RNA-based high-throughput sequencing for heritage conservation - Yong Zhang; Fasi Wu; Zengyang Han; Penghui Guo; Xinghua Ding; Dongpeng He; Xiaobo Liu; Pengfei Hu; Ji-Dong Gu; Huyuan Feng (Applied Soil Ecology, 2026)

Correction: Lipid Metabolomics Analysis of a Rosacea Animal Model Induced by Demodex Mite Extract - Siwen Liu; Jiacheng Cao; Dacun Zhang; Zhiqiang Li; Renren Han; Jian Lv; Yuxin Guo; Wei Guo; Xiaodong Zhan; Shengli Gu (Acta Parasitologica, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

Analysis of wind data consistency derived from wind profile and L-band sounding radar based on ICC - Fang Pang; Yu Long Han; Yi Pan; Ming Yi Gu; Yansong Bao; George P. Petropoulos (International Journal of Remote Sensing, 2026)

Sex-specific responses of intestinal health, microbiota composition, and transcriptome profiles in golden pompano (Trachinotus blochii) subjected to hypoxia and reoxygenation - Xiao Kun Wang; Shan Ying Han; Ze Xin Zhong; Zeng Tan Hu; Tian Xiu Li; Yue Gu; Chun Xiu Jin; Tian Jiang; Fei Biao Song; Jian Luo; Jun Long Sun (Frontiers in Marine Science, 2026)
Introduction Driven by global climate change and coastal eutrophication, severe hypoxic events have become a primary environmental stressor in marine ecosystems, posing a critical threat to commercially vital teleosts like the golden pompano ( Trachinotus blochii ). Understanding the dimorphic physiological and microbial responses between sexes under such stress is crucial for developing targeted mitigation strategies. Methods Golden pompano were subjected to hypoxia stress (3.0 ± 0.2 mg/L) for 14 days, followed by restoration of dissolved oxygen to normoxic state (7.0 ± 0.2 mg/L) and cultivation for another 14 days. Subsequently, the histology ( n = 3), digestive enzyme activity ( n = 9), microbial composition ( n = 3), and transcriptome ( n = 3) of intestinal tissue were evaluated. Results Hypoxia induces marked physiological stress and a shift toward intestinal dysbiosis across both genders, manifested by damaged intestinal integrity, oxidative stress, and an increased abundance of opportunistic pathogens (e.g., Spirochaetes ). Although reoxygenation further deteriorates the histological condition of female intestinal tissue, it also triggers more significant molecular and enzyme activity rebound effects compared to males. Moreover, females exhibit significant upregulation of lipid metabolism, antioxidant defense mechanisms, and key signaling pathways, suggesting that they may have adopted a high-energy “compensatory recovery” strategy. Correlation analyses reveal that these microbial shifts are closely linked to host metabolic regulation: beneficial bacteria ( Pseudoalteromonas and Lactococcus ) support sterol transport and signaling homeostasis, while opportunistic taxa ( Brevinema ) negatively impact lipid synthesis. Discussion Our findings reveal a distinct gender dimorphism in the hypoxia and reoxygenation response, providing a theoretical foundation for sex-specific management and nutritional interventions in golden pompano aquaculture.

A novel configuration of asymmetric inlet composite bipolar plate flow field for stackable high-power PEMFCs - Wang Gu; Lei Shi; Han Liang; Wenxie Bu; Minggang Zheng; Wanchao Zhu (Process Safety and Environmental Protection, 2026)

Text mining and machine learning based health risk prediction for soil polycyclic aromatic hydrocarbons at typical coal-fired industrial sites in china - Lu Han; Hanyuan Gu; Mengfang Chen; Zhanfei He; Yufei Jia; Yudong Feng; Jing Li; Ya Zhu; Ye zou (Journal of Hazardous Materials, 2026)

Gut virome derived bacteriophage endolysin Lys572 can effectively control Streptococcus suis in refrigerated and thawed pork - Hui Ning; Yiming Ma; Siyao Zuo; Wei Ding; Wenyu Han; Jingmin Gu; Yalu Ji (International Journal of Food Microbiology, 2026)

Targeted biocontrol of Escherichia coli O157:H7 biofilms in food environments using the novel bacteriophage CAU_ECP01 - June Gu Kang; Sangha Han; Soo-Jin Jung; Ha Rim Lee; Chaeryeong Oh; I. Kang; Sang-Do Ha (Food Research International, 2026)

Dual-channel fluorescent probe for in-situ differential detection of HClO and H2S in crops and food - Wei Liu; Rumeng Zhang; Yutong Chen; Wuyan Gu; Haijiang Du; Zhixiang Han; Zhiheng Gao; Kun Wang; Lingliang Long (Food Chemistry, 2026)

Crack initiation and propagation mechanism of borehole surrounding rock subjected to cyclic thermal loading: insights from theoretical solution and DEM simulation - Qiuxin Gu; Qiang Zhang; Kai Zhang; Hui Liu; Yihan Du; Bo Huang; Wei Han (Computers and Geotechnics, 2026)

Comprehensive source health risks of PM2.5-bound trace metals in urban and rural areas of the North China Plain - Qingxia Ma; Shuangshuang Zou; Guoqing Zhao; Kaixin Cheng; Yunfei Wu; Renjian Zhang; Lei Gu; Xiaolei Bao; Quanzhou Han; Daiqi Ye (Atmospheric Pollution Research, 2026)

Enhancing γ-aminobutyric acid production by Enterococcus faecalis through atmospheric and room temperature plasma mutagenesis, adaptive evolution, and systematic fermentation optimization - Rumeng Han; Kun Qi; Shengming Gu; Qing Ding; Yimei Wang; Min Zhang; Mengkai Hu; Zhenglian Xue; Xiangfei Li (Systems Microbiology and Biomanufacturing, 2026)

Soil legacy effects in soybean intercropping enhance tobacco resistance to Fusarium root rot - Yuhao Dai; Chengzhi Wen; Zhijun Cheng; Zipeng Gao; Zhihui Wang; Peng Zhao; Mingshi Ding; Zhen Yang; Qiming Zhou; Jinpeng Gu; Dingguo Han; Lei Yang; et al. (Applied Soil Ecology, 2026)

Nutrient supply shapes fungal community structure and co-occurrence networks in biocrusts: Key roles of intermediate and rare taxa - Lina Zhao; Wenjing Zhang; Zongyi Jiao; Mingyang Geng; Yage Li; Yafeng Han; Zhe Zhao; Shaobin Gu; Xinrong Li (Applied Soil Ecology, 2026)

Myasthenia Gravis patients have reduced DTI-ALPS-Index and gBOLD-CSF coupling, suggesting impaired brain waste clearance - Jianxian Zeng; Shuting Han; Mengying Zhu; Yi Shang; Peng Wu; Qinghua Gu; Yonggang Li (Brain Imaging and Behavior, 2026)

Dynamic hydrogen buffer integrated with single Pt sites for enhanced durability of high-temperature proton exchange membrane fuel cells - Yabin Xu; Jing Tian; Li Wang; Jiuli Xia; Yandong Wu; Qie Liu; Jingjing Wang; Shiqian Du; Tingting Han; Miaoyu Li; Zuyao Jiang; Yaping Gu; et al. (Science Bulletin, 2026)

Fluorinated diol-mediated alcoholysis of waste polyurethane for high-performance recycled fluorinated polyurethane foam - Xiaohua Gu; Jiatong Chen; Xingguo Han; Jiahao Xu; Shaochun Sun; Derui Du; Yan Liu; Chenglei Wang (Journal of Environmental Chemical Engineering, 2026)

Ammonia inhibition in anaerobic digestion: A critical review of inhibition mechanisms and mitigation strategies - Linpei Han; Lei Li; Jiaqi Huang; Wenjie Ye; Yongli Liu; Bin Zhan; Yilu Gu; Xuya Peng (Journal of Environmental Management, 2026)

Bacteriophage-functionalized biopolymer packaging solutions for poultry cold chain: A bibliometric and mechanistic review - Ha Rim Lee; Sangha Han; June Gu Kang; Md. Ashikur Rahman; Ike Kang; Sang-Do Ha (International Journal of Food Microbiology, 2026)

Mechanism of phosphates modification on squid myofibrillar proteins and effect on gel properties of surimi - Mengli Han; Xin Jiang; Meijiao Gui; Qianqian Liang; Yuan Gu; Xin Song; Wenzheng Shi (Food Chemistry, 2026)

EBV-driven rewiring of Drp1-Mediated mitophagy exacerbates trichloroethylene-induced hypersensitivity syndrome - Yuyan Xu; Shuai Liu; Mengnan Yi; Wen Gu; Yican Wang; Guoyong Mei; Jun Han; Yufei Dai (Environmental Pollution, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Ecologically engineered seawall revetments for enhancing marine biodiversity: elevation and design options - Junbao Huang; Peng Yun; Yu Han; Qing Lyu; Huayu Chen; Zengfeng Li; Jiali Gu; Jian Zeng; Zhenming Ge (Coastal Engineering, 2026)

Conservative Transport Using a Compact Third-Order Scheme on the Yin–Yang Grid - Juan Gu; Yuting Qiu; Xindong Peng; Xianbiao Kang; Han Jiao (Journal of Meteorological Research, 2026)

Lipid Metabolomics Analysis of a Rosacea Animal Model Induced by Demodex Mite Extract - Siwen Liu; Jiachen Cao; Dacun Zhang; Zhiqiang Li; Renren Han; Jian Lv; Yuxin Guo; Wei Guo; Xiaodong Zhan; Shengli Gu (Acta Parasitologica, 2026)

Integrating ground-source heat pumps and photovoltaic thermal structures for low-carbon, cost-effective building energy solutions: a comparative investigation - Luyue Han; Fenghua Xia; Zhenxing Cheng; Song Zhou; Shoupu Gu; Rui Zhang; Xiuyan Zhang (Environment, Development and Sustainability, 2026)

New perspectives on key bioactive molecules of lactic acid bacteria: integrating targeted screening, key gene exploration and functional evaluation - Shi Hu; Qi Wang; Jinfeng Wu; Hangjia Zhang; Jiaqi Yin; Lina Ding; Ping Li; Hang Xiao; Qing Gu; Jiarun Han (Critical Reviews in Food Science and Nutrition, 2026)

Dynamic profiling of myogenesis in developing ovine skeletal muscle - Weiwei Duan; Zhenzhen Gu; Chenxi Liu; Wenrong Li; Sangang He; Bin Han; Lu Shi; Mingjun Liu (Meat Science, 2026)

Supply chain models dictate pork spoilage rates: Metabolomic profiling reveals the degradation mechanism under ambient exposure - Bin Han; Cheng Li; Su Wang; Dequan Zhang; Minghui Gu; Xiaochun Zheng (Food Research International, 2026)

Structural complexity trumps taxonomic diversity in sustaining forest multifunctionality under environmental change - Yue Gu; Zhijie Chen; Junhui Zhang; Shijie Han (Forest Ecology and Management, 2026)

An advanced multifunctional strategy - enabled triboelectric nanogenerator for efficient wind-energy harvesting - Bin Wang; Yan Gu; Yan Zhou; Yamei Liu; Ning Huang; Guangze Du; Xinyang Liu; Lingling Han; Huibo Zhao; Zhen Wang; Yingao Xue; Jieqiong Lin (Chemical Engineering Journal, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Spatially isolated single-site VOx on activated carbon for efficient oxidation of carbohydrates to formic acid - Zhen Zhang; Xiaojian Tian; Yuxiao Sun; Dandan Han; Bang Gu; Dan Wu; Armin Rezayan; Xian Wu; Jingpeng Zhao; Jianshe Wang; Tianliang Lu; Renfeng Nie; et al. (Chemical Engineering Journal, 2026)

Flash joule heating-induced synthesis of biowaste-derived metal-free catalysts for nitrate reduction reaction - Xin Chen; Zhaoyu Wang; Liuhong Yang; Runmiao Yuan; Shuyi Huang; Qinyuan Hu; Xue Wang; Cong Gu; Xiangli Wen; Xi Chen; Hongji Zhang; Dongjian Shi; et al. (Bioresource Technology, 2026)

Validation on cloud fraction products from satellite and reanalysis data over the Tibetan Plateau - Xiaoyang Guo; Shaoqi Gong; Hailong Zhang; Li Li; Lu Han; Li Gu; Hua Li; Hao Zhang; Qinhuo Liu (Advances in Space Research, 2026)

Research on design and prediction model of tunnel safety micro-deformation radar monitoring system - Zi-heng Gao; Gu-hua Pu; Jin-zhuang Wang; Meng-wei Han; Qiang He; Xiao-long Wang; Jian-bo Yang; Xiao-yu Yin; Jia-gui Duan; Liang Bao; Xi-can Zhao; Wei-jian Liu (Applied Geophysics, 2026)

Tunnel Micro-deformation Monitoring Method Based on Improved PS-InSAR and Its Geophysical Application Analysis - Meng-wei Han; Gu-hua Pu; Jin-zhuang Wang; Zi-heng Gao; Xiao-qian Yang; Bo Zhang; Ba-he Yang; Jun Ma; Hai-yun Wang; Yong-can Chen; Xi-can Zhao; Wei-jian Liu (Applied Geophysics, 2026)

Knockout of pilA gene in Spirulina platensis enhances the exopolysaccharide production and auto-aggregation - Yuxi Han; Xiujun Xie; Songcui Wu; Shurui Wang; Shan Gao; Wenhui Gu; Guangce Wang (Journal of Oceanology and Limnology, 2026)

Modulation of the nanoscale chimney effect in metal–organic frameworks enables efficient guest diffusion and separation - Sha-Sha Meng; Hanxi Guan; Han Yang; Hai-Yue Wei; Mo-Han Gu; Jian Zhang; Ming Xu; Lina Wu; Zhi-Yuan Gu (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Transcription factor NlHsf regulates NlABCG7 overexpression in the sulfoxaflor resistance of Nilaparvata lugens - Zhao Li; Qing Han; Kaixin Gu; Xianyan Su; Shun He; Hu Wan; Jianhong Li; Xuexiang Ren (Pesticide Biochemistry and Physiology, 2026)

Nano-bio interaction determines the early progression of lung cancer by reshaping pulmonary epithelial microenvironment - Yu-Han Zhang; Jun Zhang; Lei Shi; Meng Xiang; Xue Han; Ling Zhu; Jia-Cheng Xie; Yan Chen; Qi Gu; Jing-Yu Li; Zhen Zou; Jian-Yu Wang (Journal of Hazardous Materials, 2026)

Improvements and intelligence integration of virtual refrigerant charge (VRC) sensor - Yue Zheng; Hua Han; Jun Xiong; Hua Zhang; Xun Cao; Bo Gu; Wenjie Dai; Xu Gao; Weiqi Yi (International Journal of Refrigeration, 2026)

Data analysis of a five-inlet radial flow field bipolar plate for enhanced mass transport in PEMFC Applications - Han Liang; Peng Zhang; Wenxie Bu; Wang Gu; Minggang Zheng; Wanchao Zhu; Baolin Wang (Fuel, 2026)

Hetero-molecular junction promoted electrochemiluminescence of porphyrin-based hydrogen-bonded organic framework for antibiotic resistance gene assay - Qian Han; Yingbo Cao; Xueran Shi; Tiance Gu; Zhuohao Jiao; Fan Xu; Zhuozhe Li; Jing Wang (Food Chemistry, 2026)

Innovative cellulose-mediated liquid metal composites hydrogel with adhesive and mechanical-thermal multimodal sensing capabilities for smart wearable devices - Jingren Ma; Shengnan Li; Yuanjie Gu; Danning Wang; Weisheng Yang; Changtong Mei; Xinwu Xu; Huining Xiao; Jingquan Han (Chemical Engineering Journal, 2026)

A fully self-breathing, liquid metal-fed, solid oxide cell for high-density energy storage - Xin Gu; Yidong Jiang; Chaojun Liu; Peidong Song; Wenfei Mo; Qiaoxia Zhu; Yaowei Hao; Xiaoyi Liu; Meng Han; Yixiang Shi; Ningsheng Cai; Zongping Shao (Chemical Engineering Journal, 2026)

An agro-bionic approach to co-chelating ultrafine high-entropy metal phosphosulfide nanoparticles for superior Li/K-ion storage - Bing-Jie Feng; Jia-Jie Liu; Xiao-Hui Wu; Zhi-Qiang Gu; Li-Zhong Liu; Li-Bing Yang; Chen Dai; Ke Han; Ming-Jun Zhao; Wei-Jun Jiang; Yi Zhao (Chemical Engineering Journal, 2026)

Tuning the coordination field configuration on well-defined molecular catalysts for boosting bifunctional oxygen electrocatalytic - Bolong Yang; Linkai Han; Yunfei Shen; Junfei Peng; Weiqian Liu; Tao Gu; Zhansheng Wu (Chemical Engineering Journal, 2026)

Efficient nitrogen removal in pilot-scale single-stage partial nitritation/anammox system treating high-ammonia photovoltaic wastewater: System adaptation and potential inhibition - Xin Gu; Xiang Li; Han Wang; Jiaen Wang; Haixu Shen; Yayi Wang (Bioresource Technology, 2026)

Dissection of Fusarium head blight resistance in a modified nested association mapping panel of synthetic and bread wheat germplasm - Anil Karmacharya; Dhondup Lhamo; Krishna Acharya; Qijun Zhang; Han-Chang Chang; Shaobin Zhong; Andrew J. Green; Jason D. Fiedler; Mingcheng Luo; Kirk M. Anderson; Amanda R. Peters Haugrud; Elias M. Elias; et al. (Theoretical and Applied Genetics, 2026)

Genome-wide association study of alkali tolerance at germination stage in wheat - Haoran Gu; Zixu Wang; Xiaotong Liu; Haotian Cao; Zixin Zhou; Meishan Zhou; Xinzhi Yang; Han Sun; Ran Qin; Chunhua Zhao; Yongzhen Wu; Fa Cui (Theoretical and Applied Genetics, 2026)

Tuning biochar surface area for optimal chain elongation: a strategy for high-efficiency medium-chain fatty acids production - Yuhao Liu; Lei Zhao; Haiping Gu; Xinyi Wang; Bingjie Wang; Kui Wang; Wei Huang; Han Yang; Jingjing Zhang; Junjiao Zhang (ENGINEERING Environment, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Microencapsulated nitrogen inhibitors promote ecosystem sustainability via greenhouse gas emission reduction and maize yield improvement - Kun Zhang; Ruiyuan Lian; Daijia Li; Jingyuan Li; Wenyu Wang; Dongwei Li; Yaqun Li; Kai Liu; Han Jiang; Xiaobing Hou; Shantong Li; Jian Gu; et al. (Agriculture, Ecosystems & Environment, 2026)

Micro-granular sludge driven by powder carrier in membrane bioreactor: highly-efficient N & P removal and membrane fouling alleviation - Boran Wu; Junqian Zhong; Hao Chang; Dong Li; Chengxian Wang; Hongbo Han; Qun Gu; Yan Zhong; Xiaohu Dai; Xiaoli Chai (Water Research, 2026)

Porcine reproductive and respiratory syndrome virus nsp6 hijacks ATP1B1 antagonizing TRAF6 mediated antiviral innate immunity - Haotian Yang; Han Gu; He Qiu; Bicheng Li; Jidong Xu; Tong Cao; Du Liuyang; Xiaoliang Li; Fang He (Veterinary Microbiology, 2026)

Inductive spatial temporal graph convolutional neural network for granary temperature field reconstruction - Han Gu; Zelong Zhou; Changtian Li; Wenqiang Chen; Bin Chen (Journal of Stored Products Research, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

A novel phage lysin Lys19 can serve as potential biocontrol agent against Clostridium perfringens and Streptococcus suis - Yalu Ji; Yuqing Zhou; Yao Fu; Changjiang Sun; Wenyu Han; Xin Feng; Jingmin Gu (International Journal of Food Microbiology, 2026)

Co-pyrolysis of polyolefin separators and active materials from lithium batteries: Thermal conversion performance, interaction behaviors, and products - Hui Liu; Jingkun Han; Jing Gu; Yuheng Feng; Gongqi Liu; Haoran Yuan (Fuel, 2026)

Effect of high hydrostatic pressure on the structural, physicochemical, and functional properties of quinoa flour - Aiying Gu; Jing Wang; Long Ding; Xiaolong Wu; Jianchun Han; Xuebo Liu; Liying Wang (Food Chemistry, 2026)

Construction and application of a MASH-like liver organoid model reveals the metabolic modulatory effects of Angelica sinensis polysaccharide - Shiyi Tan; Yu-Han Cai; Wei Wang; Li Ma; Xulei Zuo; Tingting Xu; Haohan Liu; Yuxi Zhang; Hao Gao; Geyu Liang; Yuepu Pu; Zhongze Gu; et al. (Food Bioscience, 2026)

Characterization of a novel Bi-functional cold-adapted chitinase from Chitinibacter mangrovi FCG-7T for efficient production of N-acetyl-D-glucosamine - Chenxi Gu; Liyan Yang; Susu Han; Dengfeng Yang; Xiaodong Xu; WenChao Zhang; Mingguo Jiang; Lixia Pan (Food Bioscience, 2026)

Substrate-driven enrichment and mining of ligninolytic bacteria for efficient lignin-to-PHA conversion - Tao Xu; Chong Han; He Liu; Zi-Yi Zhao; Fan-Li Zeng; Yu-Cheng Gu; Zhi-Hua Liu; Bing-Zhi Li (Chemical Engineering Journal, 2026)

Activation of the Tp53 apoptosis signaling pathway by chelidonine induces cardiac developmental abnormalities in zebrafish larvae - Jin Gu; Yanwen Zheng; Jian Su; Rui Li; Chiyu Zhang; Han Wang; Zhaomin Zhong (Chemico-Biological Interactions, 2026)

Bisphenol AF induces mouse spermatogonia apoptosis via reactive oxygen species-mediated Beclin-1 cleavage - Hyo Jin Gu; Gil Un Han; Seul Gi Kim; Sung-Hwan Moon; Seung Hee Shin; Buom-Yong Ryu (Toxicological Research, 2026)

Targeting P2X7R Protects the Retina Against High-Altitude Hypoxia via NLRP3–Mediated Pyroptosis Suppression - Keke Ge; Yange Gu; Huan Xi; Siyuan Liu; Yatao Wang; Lu Yang; Cong Han; Xingxing Zheng; Hao Wang; Songjian Huang; Wenfang Zhang (Molecular Neurobiology, 2026)

Clinical Values of Serum Extracellular Vesicle MicroRNA Profiles as Molecular Biomarkers for Ischemic Stroke and Transient Ischemic Attack - Xinran Wu; Zhuoying Gu; Chenxi Kong; Xueqin Jiang; Qianqian He; Ziwu Han; Jia Wu; Junjun Wang (Molecular Neurobiology, 2026)

Photobiomodulation Reduces Fibrous Scar Formation After Spinal Cord Injury by Downregulating CXCL3 Expression in Macrophages - Zhihao Zhang; Hongwen Gu; Ting He; Yuanhang Zhao; Shilei Tang; Kangen Han; Yin Hu; Hongwei Wang; Hailong Yu (Molecular Neurobiology, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Innovative design of CXCR4 cyclic peptide via molecular docking for 99mTc-Labeled SPECT/CT imaging in melanoma - Xianrui Yin; Xin Wang; Chengwei Chen; Shenglan Jia; Wanhong Li; Yihong Wu; Xin Chen; Danling Feng; Wai Ping Cecilia Tsang; Zhihao Han; Yueqing Gu (Analytica Chimica Acta, 2026)

AMENet: a semantic segmentation framework for multimodal remote sensing lithology scene images - Chengfan Li; Jingxin Han; Xiaodong Pan; Yang Song; Jung Yoon Kim; Yili Liu; Guohui Gu; Yuejun Liu; Yuhan He (International Journal of Remote Sensing, 2025)

Potential of mechanobiology principles for cultivated meat development: Lessons from tissue engineering - Pei Leng Tan; Jasmine Si Han Seah; Andy Wei Chun Koh; Cheryl J.Y. Koh; Xin Gu; Tizhong Shan; Lay Poh Tan (Trends in Food Science & Technology, 2025)

Integrative analysis of levofloxacin-induced liver injury: Insights from pharmacovigilance, human liver organoids, and extracellular vesicle proteomics - Shiyi Tan; Yun Yang; Yu-Han Cai; Yuepu Pu; Zhongze Gu; Juan Zhang (Toxicology and Applied Pharmacology, 2025)

Dating fault rocks using optically stimulated luminescence: Insights from the northern Yangsan Fault, Korean Peninsula - Hyo-Jeong Weon; Jeong-Heon Choi; Raehee Han; Dohee Gu; Yeong-Min Hong; Chang-Min Kim (Tectonophysics, 2025)

Predicting soil erosion rates of farmland with different slope shapes in Northeast China by using the improved RUSLE2 model - Yingli Shen; Gang Liu; Ju Gu; Chengbo Shu; Kai Wang; Qiong Zhang; Han Luo; Chutian Zhang; Zhen Guo (Soil and Tillage Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A comprehensive framework for evaluating coastal spatial conflicts: Insights from four marine space use cases in China - Jiali Gu; Yu Han; Linfeng Luo; Jian Zeng (Regional Studies in Marine Science, 2025)

Application of data mining to fast prediction of propeller performance - Qingyu Xue; Kang Han; Pengli Zhao; Yu Gu; Ning Li (Ocean Engineering, 2025)

Anti-disturbance line-of-sight path following of dual-podded maritime autonomous surface ships: A case study of XIN HONG ZHUAN - Yanping Xu; Zhouhua Peng; Nan Gu; Guiyong Zhang; Bing Han (Ocean Engineering, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Thermal decomposition characteristics, products, and thermal transformation mechanisms of fluorine-containing organic components in lithium-ion batteries - Hui Liu; Jingkun Han; Yuheng Feng; Chongqing Nong; Yu Liu; LeiLei Cheng; Jing Gu; Haoran Yuan (Journal of Environmental Chemical Engineering, 2025)

Photoaging behavior and neurotoxic effects of shower gel-derived microbeads in Caenorhabditis elegans - Yulun Gu; Yajing Han; Xin Li; Ping Ding; Chaoyi Du; Xiaoxia Chen; Yongqi Jiang; Jinyu Chen; Jingwen Cui; Haibo Chen; Hui Li (Journal of Environmental Management, 2025)

Removal of Cd from severely contaminated soil by TiO2 modified magnetic sepiolite (MMSep@TiO2): The performance and possible mechanisms - Jiachao Jiang; Chunyang Gu; Yunliang Han; Xiangyu Bai; Xiaofu Shang; Jiajia Hu; Xin Xiao; Lizhang Wang; Ping Luo (Journal of Environmental Chemical Engineering, 2025)

Efficient separation of copper and aluminum foils from spent lithium-ion batteries via sulfidization flotation - Lijue Wang; Yongwei Wang; Shen’ao Zhang; Kunhong Gu; Junwei Han (Journal of Environmental Chemical Engineering, 2025)

Combining deep learning and protein engineering to develop a thermostable protease for aquafeed applications - Zipeng Wu; Yuling Wang; Yiran Lao; Yutong Gao; Lingjie Kong; Han Jiang; Yuyang Zou; Peizhi Gu; Mingtao Huang; Xiufang Liu; Tao Wei (Food Bioscience, 2025)

Nano-traps intervening in liquid-liquid phase separation-mediated scavenging of cell-free DNA for macrophage polarization remodeling - Shuyuan Qu; Yilong Zhao; Yue Han; Xiaojie Zhou; Yueqi Ni; Kun Tan; Xizhen Luo; Jing Zhang; Bin Gu; Jiaolong Wang; Chengcheng Yin; Qin Zhao; et al. (Chemical Engineering Journal, 2025)

A novel storage radiation sensitive material with wide-tunable emission chromaticity and detection dose - Naixin Li; Kuan Ren; Meng Gu; Yanshuo Han; Xue Yang; Guibin Zhai; Jingtai Zhao; Qianli Li (Chemical Engineering Journal, 2025)

Functional Effects of Probiotic Lactiplantibacillus plantarum in Alleviation Multidrug-Resistant Escherichia coli–Associated Colitis in BALB/c Mice Model - Mohamedelfatieh Ismael; Nageena Qayyum; Yaxin Gu; Li Na; Han Haoyue; Muhammad Farooq; Panpan Wang; Qingping Zhong; Xin Lü (Probiotics and Antimicrobial Proteins, 2025)

Zinc Fertilizer Application in Different Stages Changes the Accumulation and Remobilization of Zinc in Winter Wheat - Muhammad Fraz Ali; Yuxi Niu; Guoming Li; Lijuan Ma; Xiang Lin; Shubo Gu; Yong Han; Dong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Shear deformation bands in clastic dikes: a case study from the Miocene Pohang Basin, SE Korea - Donghwa Yun; Raehee Han; Chang-Min Kim; Sangwoo Woo; Hyeon-Je Park; Dohee Gu; Moon Son; Cheol Woo Song; Hakyung Lee (Geosciences Journal, 2025)

Circ_0000972 Inhibits Hepatocellular Carcinoma Cell Stemness by Targeting miR-96-5p/PFN1 - Jintian Tang; Runjuan Tang; Feng Xue; Peng Gu; Jing Han; Wukui Huang (Biochemical Genetics, 2025)

Comprehensive Index System for Evaluation of Ecological Seawalls - Peng Yuan; Yu Han; Sihao Chen; Jian Zeng; Xiaoran Wei; Yongping Chen; Jiali Gu (Journal of Marine Science and Engineering, 2025)
Seawalls are important infrastructure for coastal areas to resist natural disasters such as storm tides and typhoon waves. Traditional seawall construction often causes intertidal zone fragmentation and coastline hardening, which affects the ecological function of the coastline. Ecological seawalls have both functions of disaster prevention and ecology and have become an inevitable trend in seawall construction at home and abroad. However, constructing a comprehensive, scientifically rational evaluation index system for ecological seawalls is a critical and pressing challenge. This study is based on the summary of practical research on seawall construction and puts forward the connotation of ecological seawall clearly. Twenty indexes that reflect the safety, ecology and sustainability of ecological seawalls were selected, and a three-level comprehensive evaluation index system of ecological seawalls was constructed using the Analytic Hierarchy Process (AHP). Three cases, including the second stage of the ecological seawall of the large-scale narrowing project in Yuyao City, Zhejiang Province, were used in this evaluation system. The application results showed that the constructed comprehensive evaluation index system of ecological seawalls in this study has a reasonable evaluation index, and the evaluation result is reliable, which is suitable for popularization and application. This study clarifies the index system and construction method for the comprehensive evaluation of ecological seawalls, puts forward typical measures for ecological seawall construction from five aspects: shore beach protection, seawall body structure, seawall surface protection, building materials and vegetation selection, and provides theoretical and practical guidance for studying and judging the ecological problems of seawalls and guiding the construction of ecological seawalls.

Synergy of algal particle deposition and bioturbation amplifies the internal phosphorus loading - Fengrui Zhang; Lixian Tan; Wenxuan Han; Lei Zhang; Qiushi Shen; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Water Research, 2025)

Neighborhood thresholds, health boundaries? Spatial clustering and nonlinear decoding of respiratory health in Bengbu, Anhui, China - Jingjing Tang; Huiran Han; Kangkang Gu; Chengfeng Yang (Sustainable Cities and Society, 2025)

Efficient extraction of metals from industrial-scale pyrolytic spent LIBs materials using a leaching process without external reductants - Shen’ao Zhang; Yongwei Wang; Lijue Wang; Kunhong Gu; Junwei Han (Minerals Engineering, 2025)

Changes in volatile organic compounds of tray-packed fresh beef sausages under refrigeration: The roles of dominant spoilage bacteria - Mengjiao Han; Qianhui Gu; Sam Al-Dalali; Conggui Chen; Baocai Xu; Peijun Li (Meat Science, 2025)

Machine learning-assisted magnetic nanomotors for the identification and degradation of organic pollutants - Zhiqin Geng; Gang Wang; Bohan Gu; Bingxue Wen; Ziwen Wu; Rui Li; Linfen Duan; Yunsheng Shang; Weiqing Han; Kajia Wei; Lulu Qu (Journal of Hazardous Materials, 2025)

Modeling of water-injected coal with fracture-pore structure and experimental study of gas-water two-phase transport characteristics - Jing Han; Zhen Liu; He Yang; Zhe Zhou; Qingbo Gu (International Journal of Rock Mechanics and Mining Sciences, 2025)

Using natural nitrites from Angelica keiskei and high hydrostatic pressure treatment for producing high-quality cured pork loin with significant nitrous pigment formation - Yea-Ji Kim; Jeong-Heon Kim; Ji Yoon Cha; Tae-Kyung Kim; Jong Hyeon Han; Sung Gu Han; Yun-Sang Choi (Food Chemistry, 2025)

Effect of ultrasound combined with papain treatment on the tenderness of equatorial squid (Dosidicus gigas): in terms of myofibrillar protein modification - Mengli Han; Qianqian Liang; Meijiao Gui; Xin Jiang; Yuan Gu; Xin Song; Wenzheng Shi (Food Chemistry, 2025)

Metabolomic insights into pigment and bioactive metabolite alterations in Eucommia ulmoides leaves: A comparison between new variety and wild-type varieties - Tiannuo Hong; Jiayu Gu; Lu Chen; Xiaolu Wang; Libin Zhou; Xuehu Li; Wenke Bai; Linqi Gao; Xiaodong Li; Guangming Zhao; Juan Han; Luxiang Liu (Food Chemistry, 2025)

Food protein-based nanoemulsions: A comprehensive review with an emphasis on strategies to facilitate the formation and stabilization - Wen Han; Wen-wen Zhu; He-wei Zhang; Yu-juan Gu; Lei-Na Wang (Food Bioscience, 2025)

Revealing the role of Fe particle size in soft magnetic geopolymer for enhancing energy conversion in airport pavement induction heating - Gonghui Gu; Xinchi Xu; Jinsheng Han; Lin Wan-Wendner; Zhiji Gao; Rongze Fu; Chuanqing Fu; Tao Ma (Energy and Buildings, 2025)

How root exudates of vegetation contribute to prevention and control of soil disintegration on Chinese Loess Plateau: A case study of Robinia pseudoacacia L. - Tao Xiao; Ping Li; Rong Jiang; Sai K. Vanapalli; Xiangcheng Han; Hui Zhai; Yiyi Yang; Qi Gu; Jiading Wang (Engineering Geology, 2025)

F, O-co-regulated Ni-Co-S mesoporous heterostructured electrodes for supercapacitor applications - Xuzhao Han; Baojing Luo; Hailin Zhang; Yue Xing; Qin He; Yu Gu; Gaihua Li; Shuang Liu (Chemical Engineering Journal, 2025)

Combination of HSP70/PDGFRβ-targeted fluorescent probes for accurate diagnosis and staging of liver diseases - Xiaohui Wang; Qiurong Ju; Xue Li; Mengmeng Xiao; Jia Huang; Lenan Zou; Tianchang Liu; Zhihao Han; Yueqing Gu (Chemical Engineering Journal, 2025)

Comprehensive evaluation of the spatiotemporal distribution characteristics of multi-source precipitation products: a case study of an extreme climate event in Henan, Central China - Zihao Pang; Junxia Gu; Yu Zhang; Yang Pan; Zheng Wang; Shuai Han; Zhi Zhu (Theoretical and Applied Climatology, 2025)

Genome and transcriptome analysis provide insights into the genetics and breeding of Salix suchowensis growth traits - Wei Liu; Shaobo Gu; Mingjia Zhu; Yu Han; Xiaogang Dai; Huaitong Wu; Tongming Yin; Linjie Guo; Landi Feng; Yanjun Zan; Jianquan Liu (New Forests, 2025)

Harvesting of microalga Coelastrella sp. CHZ by flocculation with ionic liquid choline-alanine - Yihan Xie; Hong Gu; Benyong Han; Ximeng He; Qingming Long; Junwei Xu; Peng Zhao (Aquaculture, 2025)

Green collaborative recycling of spent NCM cathode and waste sodium sulfate via an unconventional process - Xuesong Gao; Kunhong Gu; Xinglan Cui; Junwei Han (Waste Management, 2025)

A comparative toxicity study depending on type of clinical use of the roots of Asarum heterotropoides var. mandshuricum (Maxim.) Kitag - Kang-Hyun Han; Seung Eui Min; Eun-Young Gu; Yong Bum Kim; Byung Sun Min (Phytochemistry Letters, 2025)

Behavior, mechanisms and hazardous changes of interactions with microplastics when heterogeneous pollutants coexist: Arsenic and thiram - Qingrun Liu; Dajun Wu; Jinchi Han; Jun Wang; Lang Gu; Meiyi Zeng; Zixuan Zhang; Yuheng Chen; Yue Pan; Yulun Chen; Zhe Chen; Weirong Yao (Journal of Hazardous Materials, 2025)

Differential enhancement of chain elongation by nano zero-valent iron and zero-valent iron: Mechanisms, microbial dynamics, and medium-chain fatty acids production - Yuhao Liu; Xinyi Wang; Haiping Gu; Lei Zhao; Kui Wang; Bingjie Wang; Wei Huang; Han Yang; Jingjing Zhang; Xiaowei Song (Journal of Environmental Chemical Engineering, 2025)

Deep learning-based colorimetric indicator on polylactic acid packaging for nondestructive monitoring of fresh-cut fruits and vegetables - Shasha Zhang; Haibin He; Xiaoxue Han; Huayu Gu; Shuaibo Zhang; Zhaorun Tang; Xianwen Ke; Juhua Liu; Xinghai Liu (Food Research International, 2025)

Centennial-scale evolution, source apportionment, and ecological risks of heavy metals in Daya Bay, South China sea - Xiangtian Man; Jian Sun; Yu Xiang; Hong Su; Honghui Huang; Yangguang Gu; Han Zhang; Richard W. Jordan; Shijun Jiang (Environmental Pollution, 2025)

Metabolomic analysis reveals paraquat-induced metabolic alternation in BV2 microglia: Focus on glutamate metabolism - Xutong Qin; Yaxin Han; Jiming Zhang; Zheng Wang; Qiuyun Gu; Jiayi Li; Zhijun Zhou; Xiuli Chang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Spatiotemporally-graded BHP/G@met scaffold system enables sequential angiogenesis-osteogenesis coupling for accelerated bone regeneration - Han Zhang; Shuqing Chen; Guodong Zhang; Yongbin Wang; Zichen Cui; Fei Chen; Yukun Du; Guanghui Gu; Tianyu Bai; Changlin Lv; Wenkang Yang; Shiqi Xu; et al. (Chemical Engineering Journal, 2025)

Ag nanoparticles anchored on oxygen vacancy-rich alumina catalyst for efficient bacterial inactivation - Ting Wang; Fangyuan Gu; Leyang Xu; Wenqi Tang; Yanfeng Han; Yongjie Wang; Shi Yang; Weiying Wang; Xinlong Zhang; Tianshuo Zhao; Biao Ran; Chaopeng Fu; et al. (Chemical Engineering Journal, 2025)

Conjugation-driven electronic structure engineering of halogenated indolequinones for bidirectional catalysis in lithium-sulfur batteries - Shiyao Liu; Hongmin Yu; Zhenhua Liu; Yueyue Zhang; Yutong Han; Yixuan Gu; Yuxuan Li; Zongtao Li; Zhao Wang; Hao Sun (Chemical Engineering Journal, 2025)

Interfacial engineering with moderate sodiophilic zinc-nitrogen sites for highly reversible anode-free sodium metal batteries - Ziyu Chen; Chen Zhang; Han Fu; Dongxu Zhou; Ying Xu; Jiawen Chen; Yu Zhong; Xiuli Wang; Changdong Gu; Jiangping Tu (Chemical Engineering Journal, 2025)

Insights into excitonic dynamics in conformational distorted porphyrinic covalent organic frameworks for efficient selective photooxidation - Wang-Kang Han; Jiayu Li; Kang Deng; Jing-Dong Feng; Ruo-Meng Zhu; Ming-De Li; Zhi-Guo Gu (Chemical Engineering Journal, 2025)

Synergistic control of SRT and DO in independent zoned sludge systems: a model-guided PDA-PN/A process achieving low-carbon nitrogen removal in municipal wastewater environment - Tianqi Liu; Xiang Li; Yayi Wang; Yan Yuan; Han Wang; Xiaodan Gu; Jun Ma; Yong Huang (Chemical Engineering Journal, 2025)

Precise Magnetic Stimulation of the Paraventricular Nucleus Improves Sociability in a Mouse Model of ASD - Sha Liu; Quyang Yang; Pengfei Zhu; Xuan Liu; Qingbo Lu; Jie Yang; Jingyao Gao; Hongbin Han; Zhijun Zhang; Ning Gu; Tao Tan; Jianfei Sun (Neuroscience Bulletin, 2025)
Magnetic stimulation has made significant strides in the treatment of psychiatric disorders. Nonetheless, current magnetic stimulation techniques lack the precision to accurately modulate specific nuclei and cannot realize deep brain magnetic stimulation. To address this, we utilized superparamagnetic iron oxide nanoparticles as mediators to achieve precise targeting and penetration. We investigated the effects of magnetic fields with varying frequencies on neuronal activity and compared the activation effects on neurons using a 10-Hz precise magneto-stimulation system (pMSS) with repetitive transcranial magnetic stimulation in mice. Oxytocin levels, dendritic morphology and density, and mouse behavior were measured before and after pMSS intervention. Our findings suggest that pMSS can activate oxytocinergic neurons, leading to upregulation of oxytocin secretion and neurite outgrowth. As a result, sociability was rapidly improved after a one-week pMSS treatment regimen. These results demonstrate a promising magneto-stimulation method for regulating neuronal activity in deep brain nuclei and provide a promising therapeutic approach for autism spectrum disorder.

Enhanced Prediction of Geothermal Heat Flow Using an Improved GBRT Model with Genetic Algorithm - Yang Chen; Kewen Li; Han Zhang; Chao Gu; Jifu He; Wei Lu (Natural Resources Research, 2025)

Improving dynamical downscaling simulations of western North Pacific tropical cyclones using bias-corrected CMIP6 data - Ying Han; Zhongfeng Xu; Meng-Zhuo Zhang; Chi-Yung Tam; Vincent S. Cheng; Hon-man Wong; Xiaofeng He; Yi Wang; Si-nan Gu (Climate Dynamics, 2025)

Occurrence and provenance of ion-adsorbed rare earth elements mineralization in alumina-rich rocks of the Permian Heshan formation, Western Guangxi, China - Chunfang Dong; Zhixuan Han; Xiaocheng Wei; Junhong Liu; Haonan Zhao; Zhiyan Gu; Bimin Zhang; Cheng Xu (Applied Geochemistry, 2025)

Deep learning-based approach for behavior recognition and pose estimation in cage-reared ducks: Leveraging cage-net elimination to propel precision improvement - Shida Zhao; Zongchun Bai; Lianfei Huo; GuoFeng Han; Enze Duan; Yue Gu; Lili Meng (Computers and Electronics in Agriculture, 2025)

Phenotypic prevalence index: Diversity of polyphosphate-accumulating organisms (PAOs) and insights in unknown PAOs revealed by combined fluorescence-activated cell sorting (FACS) and 16S rRNA gene sequencing - Peisheng He; Yuan Yan; Jangho Lee; IL Han; Guangyu Li; Fabrizio Sabba; Zhen Jia; George F. Wells; April Z. Gu (Water Research, 2025)

Mogroside V derived from Siraitia grosvenorii fruit: From evidence of health-promoting benefits to food applications - Zhongrui Zhang; Akida Adiham; Cairong Han; Feifei Huang; Yulu Yan; Dapeng Li; Kun Guo; Jian Gu; Puyang Gong (Trends in Food Science & Technology, 2025)

Local regulation and global reconstruction of polar networks in twisted bilayer MoS2 - Jiakai Wang; Xu Han; Guanchu Liu; Zihao Guo; Longshuo Gu; Jiahao Yan; Shiqi Yang; Chunsheng Hu; Chicheng Liu; Yunyun Dai; Xia Liu; Yuan Huang; et al. (Science Bulletin, 2025)

Sulfite-synergized VUV photolytic decomposition of metformin: A combined experimental and theoretical study - Yurong Gu; Zijun Dong; Qi Han; Liao Ouyang; Yihua Chen (Journal of Water Process Engineering, 2025)

Restoration of mitochondrial homeostasis by Wnt3a/β-catenin/c-Myc alleviates cadmium-induced neural stem cell senescence and cognitive impairment in mouse hippocampus - Yuwei Zhang; Qiuyun Gu; Yixi Li; Jiayi Li; Yaxin Han; Longfei Feng; Xutong Qin; Jiming Zhang; Zhijun Zhou; Xiuli Chang (Journal of Hazardous Materials, 2025)

Rethinking the dewatering mechanisms underlying bioleaching from the perspective of extracellular polymeric substances and biogenic Schwertmannite interaction - Yunbei Li; Shuyue Han; Hailong Li; Lijun Quan; Xu Yan; Gaoyuan Gu; Shipeng Wang; Jinghua Lv; Biaobing Huang (Journal of Environmental Management, 2025)

Prenatal bisphenol analogues exposure, metabolites in breast milk and offspring anthropometric growth during infancy: The Wuhan twin birth cohort study - Hong Mei; Liqin Hu; Haoshuang Liu; Neng Li; Yunxia Li; Jiali Xu; Hailin Gu; Feiyan Xiang; Meng Yang; Pan Yang; Jianduan Zhang; Han Xiao; et al. (International Journal of Hygiene and Environmental Health, 2025)

Novel nanoceria in situ-derived porphyrin heterostructure enhanced electrochemiluminescent and colorimetric dual-mode detection of tetracycline residue in foods - Xueran Shi; Yingbo Cao; Lin Cong; Tiance Gu; Jing Wang; Qian Han (Food Chemistry, 2025)

Responses of multi-trophic microbial communities to altered precipitation affected soil respiration in coastal wetlands - Yuqi Zhou; Xinge Li; Shuzhen Li; Xiongfeng Du; Zheng Zhang; Zhaojing Zhang; Kai Feng; Xi Peng; Wen Song; Song Gu; Pengpeng Duan; Baohua Xie; et al. (Applied Soil Ecology, 2025)

Combining immunomagnetic beads and the phage lysin LysGH15 for fluorescence detection of Staphylococcus aureus - Yuqing Zhou; Hanli Kang; Xiaoguang Zhang; Yalu Ji; Wenyu Han; Bin Wang; Jingmin Gu (Analytica Chimica Acta, 2025)

Large-Scale Aerial Gamma Spectroscopy for Exploring Sandstone-type Uranium Deposits: A Case Study of Gexi Area, Inner Mongolia - Zhe Jiang; XiaoZhong Han; Zhongyue Lin; Hang Hu; Qiang Lai; Yi Gu; ZhaoJian Wu; Xin Zhao (Applied Geophysics, 2025)

Design of Organic Rankine Cycle Recovering Multi-Grade Waste Heat from a Two-Stroke Marine Engine - Jinfeng Feng; Yuncheng Gu; Shengjun Han; Xunhu Zhao; Yujun Tang; Sipeng Zhu; Hao Yuan; Guihua Wang (Journal of Marine Science and Engineering, 2025)
Waste heat recovery using Organic Rankine Cycle (ORC) systems shows significant potential for reducing CO2 emissions from ships. This study designs and analyzes ORC systems for recovering multi-grade waste heat from the exhaust gas, jacket water, and scavenging air of a marine two-stroke diesel engine. A thermodynamic model is developed to investigate the effects of working fluid preheating temperature, evaporation pressure, and heat source conditions on system performance. Results show that appropriately increasing the preheating temperature of the working fluid can enhance power output. For hydrocarbons with higher critical temperatures, power output exhibits an extremum as preheating temperature increases, while for fluids with lower critical temperatures, power output increases continuously until the evaporation pressure limit is reached. Increasing evaporation pressure decreases power output but improves thermal efficiency, with a corresponding increase in heat transfer and exergy loss rates in the exhaust gas preheater. Additionally, the temperature of the heat source has an important effect on the energy and exergy balance distribution and power output of the ORC. For every 10 K rise in exhaust temperature, the bottoming cycle power output of cyclohexane increases by approximately 12.3%. This study provides theoretical support for efficient marine waste heat recovery and working fluid selection.

Organic sulfur-driven denitrification pretreatment for enhancing autotrophic nitrogen removals from thiourea-containing wastewater: performance and microbial mechanisms - Jiheng Zhu; Xiang Li; Yayi Wang; Xin Gu; Han Wang; Jun Ma; Yong Huang (Water Research, 2025)

Revising the SCS-CN model by using the effect of biocrusts to refine the results - Kangmin Gu; Yunge Zhao; Kai Yang; Shanshan Wang; Jingyi Ji; Jingrong Song; Jianqiao Han (Journal of Hydrology, 2025)

Identification and functional characterization of a novel CaSrpA enzyme for selenite reduction and selenium nanoparticle formation - Xiaoxiao Hou; Jidong Gu; Jicong Chen; Habib Ullah; Tursunay Mamtimin; Xing Wang; Xiaoqin Li; Yuchao Jiang; Jingwen Fan; Huawen Han; Xiangkai Li (Journal of Hazardous Materials, 2025)

Cellulose/ionic hydrogel moisture electric generators with enhanced output and stability - Gangli Zhao; Fangzhou Li; Linglan Guo; Dingyun Zhang; Haotian Luo; Jiaxing Huo; Zechao Han; Peicheng Han; Qiaolin Gu; Ran Tang; Yanjie Su; Feng Zhan; et al. (Chemical Engineering Journal, 2025)

Optimization of synergistic microwave and zero–valent iron co–pretreatment for anaerobic digestion of waste activated sludge - Seung–han Ha; Seung Gu Shin; Johng–Hwa Ahn (Bioresource Technology, 2025)

Response of soil microbial community composition and function to prolonged heavy metal exposure - Zhigang Zhao; Yongfeng Wang; Linghao Kong; Liyuan Zhao; Yachao Li; Teng He; Shigao Liu; Xiangcai Han; Songsong Gu; Shuyu Wu; Jiahao Zhang; Jintao Zhang; et al. (Environmental Monitoring and Assessment, 2025)

The multimodal dynamics of “ride-pooling” and metro: Spatial-temporal patterns from East Asia - Weiping Xu; Tianqi Gu; Hyungchul Chung; Zhuonan Jiang; Han Li; Kai Huang; Wenbo Zhu (Journal of Transport Geography, 2025)

Quercetin-loaded candelilla wax/sunflower oil oleogels: Structural, sensory, and storage properties, and application as fat replacer in emulsion-type sausage - Hyun Ju Lee; Jong Hyeon Han; Dong Hyun Keum; Vahinika Kothuri; Dong-Min Shin; Sung Gu Han (Food Chemistry, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Design of four-level phase-change memory Ge2Sb2Te5/Ge50Te50 bilayer films and study of their crystallization behaviors - Ling Liu; Han Gu; Qiyu Cai; Liqi Zhu; Jie Song; Weihua Wu; Zixin Wang; Tianshu Lai (Chemical Engineering Journal, 2025)

Autofluorescence cascade nanozyme catalyzes in vivo ROS scavenging for precisive anti-neuroinflammation therapy - Xiyu Du; Gang Zhao; Yifei Fu; Yushan Zhou; Li Yang; Zhaoshun Jiang; Songbin Liu; Xixue Zhang; Kaiqi Zhu; Li Wei; Weidong Gu; Han Lu; et al. (Chemical Engineering Journal, 2025)

Cytogenetic characterization of a novel wheat-rye 2R (2D) substitution line YT9 conferring powdery mildew resistance from the three-leaf stage and physical mapping of PmYT9 - Hanwen Yan; Guohao Han; Tiantian Gu; Zhipeng Shi; Lijun Cao; Jing Wang; Hong Liu; Chenlong Wang; Shiyu Zhuo; Lihui Li; Diaoguo An (Theoretical and Applied Genetics, 2025)

Predicting Geothermal Heat Flow in the Bohai Bay Basin Based on Machine Learning Methods - Zhenxi Guo; Kewen Li; Han Zhang; Chao Gu; Jifu He (Mathematical Geosciences, 2025)

Enhancing PPP-RTK performance at low latitudes through mitigation of ionospheric scintillation effects - Xin Li; Bo Wang; Xingxing Li; Shengfeng Gu; Junjie Han (GPS Solutions, 2025)

The impact of changing ambient population composition on crime during COVID-19 lockdowns - Xin Gu; Lin Liu; Su Yeon Han; Minxuan Lan; Hanlin Zhou; Debao Chen; Zihan Su (Applied Geography, 2025)

Low-coverage whole-genome sequencing for differentiating cervical cancer from cervical intraepithelial neoplasia and benign diseases - Tingting Zhang; Fang Gu; Jia yi He; Weihua Li; Ruxue Han; Xinyu Liu; Chan Dai; Zhendong Qin; Di Zhang; Jun Lu; Hua Li (Chromosome Research, 2025)

Urban heat island and the risk of schizophrenia spectrum disorders in middle-aged and older adults - Lefei Han; Yujia Bao; Jiawei Gu; Yongxuan Li; Chen Shen; Shengzhi Sun; Jinjun Ran (Urban Climate, 2025)

Numerical investigation of cyclic load effects on geogrid-encased stone columns using a 3D coupled method - Meixiang Gu; Xiaocong Cai; Yi Lu; Daoling Han (Soil Dynamics and Earthquake Engineering, 2025)

RNAi-mediated knockdown of juvenile hormone acid methyltransferase depresses reproductive performance in female Aethina tumida - Yifan Gu; Xinyu Yang; Senhao Liu; Xiaowei Chen; Ran Liu; Jinglin Gao; Yihai Zhong; Xiaoyu Li; Wensu Han (Pesticide Biochemistry and Physiology, 2025)

Lipid surface droplet 2 (LSD2) regulates lipid metabolism and male reproductive physiology in adult Sitotroga cerealella - Sakhawat Shah; Yu Li; Wen-Han Yan; Lianyun Liu; Tianyu Gu; Karam Khamis Elgizawy; Gang Wu; Feng-Lian Yang (Pesticide Biochemistry and Physiology, 2025)

Unexpected Sr enrichment in karst lacustrine sediments associated with warming and rapid socio-economic development - Xiang Gu; Peng Xing; Cheng Zhao; Xiaotong Han; Di Xu; Qinglong L. Wu; Fengchang Wu (Journal of Cleaner Production, 2025)

Characteristics and mechanisms of phosphorus adsorption by blue algae biochar modified with a polyaluminum chloride (PAC) dehydrating agent - Xueli Ren; Jie Han; Peng Gu; ZengShuai Zhang; Hengfeng Miao; Shougao Ni; Yaochu Cao; Kunlun Yang (Journal of Environmental Chemical Engineering, 2025)

Hydrothermal temperature-dependent compositions and copper complexing behaviors of hydrochar-derived dissolved organic matter: Insights from FT-ICR MS and multi-spectroscopic analysis - Bingfa Chen; Xincai Gu; Muhua Feng; Yanfang Feng; Bingyu Wang; Bensheng You; Jingcheng Zheng; Hong Liu; Shiqun Han (Journal of Environmental Sciences, 2025)

Rapid detection of the viability of naturally aged maize seeds using multimodal data fusion and explainable deep learning techniques - He Li; Yilin Mao; Yanan Xu; Keling Tu; Han Zhang; Riliang Gu; Qun Sun (Food Chemistry, 2025)

Soil emissions of HONO and other nitrogen-containing gases: Insights into microbial pathways and moisture effects - Peng Cheng; Baobin Han; Zhilin Tian; Zhen Liu; Wenda Yang; Jianwei Gu; Xiaofang Yu; Hongli Wang; Min Zhou (Atmospheric Pollution Research, 2025)

Recent duplications and rare structural variations revealed by comparative sequence analysis of low molecular weight glutenin subunits (LMW-GS) genes re-identified using LMWgsFinder in 26 genomes of the grass family - Shengli Zhang; Xiaojing Shan; Yun Wang; Tairui Lu; Daxing Xu; Han Gong; Yuchao Fan; Yuanyuan Guan; Junjie Zhao; Haili Sun; Dongfang Li; Haiyan Hu; et al. (Theoretical and Applied Genetics, 2025)

Upregulation of YY1 in M2 macrophages promotes secretion of exosomes containing hsa-circ-0000326 via super-enhancers to facilitate prostate cancer progression - Han Guan; Huaixiang Tao; Jinguang Luo; Lilin Wan; Hao Hu; Long Chen; Zhiyuan Wen; Yuxuan Tao; Saisai Chen; Mingli Gu (Molecular and Cellular Biochemistry, 2025)

A comparison of Chinese soybean collection with European soybean collections on genetic diversity by genome-wide scan - Jiangyuan Xu; Xindong Yao; Yuqing Lu; Rittler Leopold; Yongzhe Gu; Ming Yuan; Yong Zhang; Rujian Sun; Yongguo Xue; Yeli Liu; Dezhi Han; Jinxing Wang; et al. (Genetic Resources and Crop Evolution, 2025)

Inter-trophic networks reveal the central role of methanogens in deposited estuarine soils - Linlin Wang; Xiongfeng Du; Wenli Shen; Songsong Gu; Zhaojing Zhang; Zheng Zhang; Baohua Xie; Guangxuan Han; Ye Deng (Soil Ecology Letters, 2025)

Trade-offs between vegetation and sediment availability in shaping long-term tidal network morphodynamics - Yuxian Gu; Guangxuan Han; Liang Geng; Baohua Xie; Yanan Zhang; Danghan Xie; Sergio Fagherazzi; Heyue Zhang; Giovanni Coco; Zeng Zhou (Frontiers in Marine Science, 2025)
Introduction Saltmarsh introduction has been widely implemented to restore ecosystem services and promote sedimentation in tidal mudflats, yet its effects on tidal network dynamics remain hard to predict. The interplay between saltmarsh extent and sediment availability in shaping long-term mudflat morphodynamics is not fully understood. Methods We develop a two-dimensional biomorphodynamic model to examine the individual and combined influences of saltmarsh presence and sediment availability on the evolution of tidal-flat channels. Results and discussion Our results demonstrate that sediment availability controls the long-term morphological change of mudflats, while the presence of saltmarshes exerts substantial short-term alterations in mudflat evolution. During the initial phase of saltmarsh introduction, vegetation promotes the development of tidal networks, characterized by channel elongation, narrowing and deepening. However, under higher sediment supply, saltmarshes restrict sediment deposition on landward and central mudflats compared to that on unvegetated flats. Furthermore, sediment availability primarily facilitates the extension of pre-existing channels, while saltmarshes play a dual role in both generating new channels and elongating existing ones. This distinction highlights the competing mechanisms driving channel network development.

Reproductive traits of floating Ulva prolifera sporophytes and gametophytes and their contribution to the Yellow Sea green tide - Li Huan; Wenhui Gu; Xulei Wang; Yuru Yan; Qian Tang; Xue Han; Zixuan Wang; Kai Zhou; Qi Qiu; Juntian Xu; Hui Wang; Guangce Wang (Marine Pollution Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Probabilistic multi-hazard risk assessment of high-rise buildings subjected to concurrent earthquakes and strong winds - Qian-Qian Yu; Ling-Han Liu; Xiang-Lin Gu; Yao-Yao Zhang (Engineering Structures, 2025)

Preparation of zirconium-doped titanium ion sieve composites and lithium adsorption from salt-lake brine - Zhongyi Shen; Shumao Qi; Chenxiao Hong; Xuecheng Wang; Zihang Han; Jie Chen; Ying Wu; Tao Han; Jianzhong Gu; Lu Xu; Hongjuan Ma (Desalination, 2025)

Enhancing municipal potable reuse recovery with flow-reversal RO: Pilot study, challenges, and retrofit considerations - Han Gu; Megan H. Plumlee; Mingheng Li; Auryan Mohseni; Ronit Erlitzki (Desalination, 2025)

Vanillin as a quorum sensing inhibitor: effect on extracellular polymeric substance production and defoaming potential in anaerobic digestion system - Wenjie Ye; Lei Li; Miaomiao Zou; Linpei Han; Peng Xu; Yilu Gu; Ronghuan Yuan; Xuya Peng (Chemical Engineering Journal, 2025)

Evolution mechanism and pyrolysis strategy of ethylene–vinyl acetate copolymers for recycling of the end-of-life photovoltaic modules via PCMW2D and 2D-COS analysis - Jingkun Han; Haoran Yuan; Xiaoyu Zhang; Zhaokai Yan; Jing Gu; Yong Chen (Chemical Engineering Journal, 2025)

Vacancy engineering regulating specific capacitance of supercapacitors in MOF-on-MOF derived CoSe2 quantum dots embedded in carbon and CoSe2 hollow cages - Shuangxing Cui; Yaozong Gu; Yifan Tang; Wan Cui; Guochang Li; Qiuju Zhang; Lei Han (Chemical Engineering Journal, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Charge separation engineering modulates self-oxygenating nano-heterojunctions to induce ferroptosis for sonodynamic-immunotherapy of tumors” [Chem. Eng. J. 507 (2025) 160713] - Xueyu Li; Huihui Qian; Jun Du; Junjie Pan; Qian Wang; Han Yang; Liping Gu; Xiaoyuan Zhong; Yuqing Miao; Yuhao Li (Chemical Engineering Journal, 2025)

Microbial Immobilization Shapes the Non‐Linear Response of Allochthonous Nitrogen Retention to Grassland Acidification Within Soil Aggregates - Baitao Gu; Ruzhen Wang; Shaodong Wang; Ying Zhang; Xingguo Han; Biao Zhu; Feike A. Dijkstra; Yong Jiang (Global Change Biology, 2025)
Soil nitrogen (N) retention plays a crucial role in determining the ecosystem capacity to buffer anthropogenic N inputs and provides a sustainable N supply. However, the effect of acidification, driven by atmospheric deposition of N and sulfur (S), on the retention and fate of allochthonous N across soil aggregate size classes remains poorly understood. We utilized a soil‐acidification gradient induced by 0–50 g S m −2 year −1 addition to investigate 15 N recovery in soil N pools within aggregates 21 days after labeling in a Eurasian meadow. Macroaggregates showed higher 15 N recovery in microbial biomass, amino acids, amino sugars, and therefore total N (TN), as well as greater sensitivity of the former two fractions to acidification compared to microaggregates. This was accompanied by higher N hydrolases and net N mineralization in macroaggregates, supporting the aggregate hierarchical theory. Under moderate acidification (pH decrease from 7 to 6), 15 N retention in hydrolyzable ammonium, amino sugars, non‐hydrolyzable N, and TN decreased, likely due to lower microbial immobilization and entombing of allochthonous N. Conversely, severe acidification (pH decrease below 6) enhanced 15 N retention in these N fractions through stabilization of microbial necromass, revealing a non‐linear relationship between acidification and 15 N retention. Concentrations of autochthonous organic N fractions remained unchanged after five‐year acidification. These findings underscore the mediating role of soil microbes across aggregates in allochthonous 15 N retention among N fractions with contrasting bioavailability under acidification.

Evaluation of potentially toxic elements (PTEs) contamination in seawater, sediment, and sea snails (Nerita articulata and Cerithidea obtusa) from Kukup Fishing Village, Johor, Malaysia - Ruo Han Tan; Chuck Chuan Ng; Tianze Gu; Peggy Pei Yee Tek (Environmental Monitoring and Assessment, 2025)

In-situ and non-invasive measurement of stem water content of trees using an innovative Constant-Force-Arc-Electrode sensor less susceptible to contact force variations - Yuqi Liu; Haiyang Zhou; Qiaoling Han; Yue Zhao; Jiahua Gu; Yandong Zhao (Computers and Electronics in Agriculture, 2025)

Numerical study on ice load evolution and ice crushing mechanism of 2D rigid hydrofoil ice-cutting based on Peridynamics theory - Chenxu Gu; Kang Han; Chengjie Cao; Chao Wang; Chunhui Wang; Yuan Zhang (Ocean Engineering, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Effect of γ-Aminobutyric acid and dietary monosodium glutamate supplementation on gut microbiota and short-chain fatty acid: Insights from an in vitro colonic fermentation model - Jiarun Han; Xilian Zhao; Qiuqiu Ye; Yueting Wang; Yutong Wu; Shi Hu; Ping Li; Qing Gu (Food Bioscience, 2025)

Preparation, characterization, and solubility enhancement of octenyl succinate anhydride debranched starch/1-Octacosanol nanocomplex - Meiru Ji; Baoxin Gu; Junqing Han; Lingjin Li; Yahui Gao; Li Cheng; Zhengbiao Gu; Yan Hong (Food Bioscience, 2025)

Efficient bioleaching of Li from waste lithium–iron phosphate batteries by acidophilic bacterial consortium: Enrichment condition, Li recovery, and brief carbon footprint analysis - Jinghan Gu; Yuanyuan Nie; Zaiyu Li; Kun Yang; Long An; Haiqiang Jiang; Xiaoyu Han; Zhongtian Fu; Xin Zhao (Chemical Engineering Journal, 2025)

In-situ pore forming bone adhesives targeting disordered osteoimmune microenvironment and bone metabolic balance to promote osteoporotic fracture healing - Haiyue Zhao; Lingjun Wang; Kun Xi; Wei Wang; Xinzhao Jiang; Jiahao Wang; Liang Zhou; Wenbo Wang; Feng Cai; Meng Han; Jincheng Tang; Yu Feng; et al. (Chemical Engineering Journal, 2025)

One-pot synthesis of hierarchical assembly of NiMoO4/MoS2/Ni3S2 on nickel foam for highly efficient and durable electrocatalytic hydrogen evolution reaction in a wide pH range - Senkai Han; Huiqin Yao; Jiayi Zhan; Chaonan Wang; Siqi Zhang; Qingyang Gu; Cheng Li; Shenghan Zhang; Hongliang Dong; Shulan Ma (Chemical Engineering Journal, 2025)

Rapid detection of corn seed turtle cracks based on transmitted light image and deep learning method - He Li; Yun Hao; Weifeng Wu; Keling Tu; Yanan Xu; Han Zhang; Danyang Zhang; Mingliu Li; Riliang Gu; Qun Sun (Computers and Electronics in Agriculture, 2025)

Antibiotic resistance genes and virulence factors in the plastisphere in wastewater treatment plant effluent: Health risk quantification and driving mechanism interpretation - Yaxin Wang; Xiuhong Liu; Chenduo Huang; Weipeng Han; Pengchao Gu; Ruxian Jing; Qing Yang (Water Research, 2025)

miRNA-125a regulates porcine oocyte maturation in vitro by targeting ADAR - Yue Han; Ping Lu; Yongsheng Yu; Weiyu Gu; Chunyu Li; Yanqiu Lv; Xinglin Qu; Yuyang Zhang; Qinglong Xu; Shunfa Yao; Xuan Chen; Yi Jin (Theriogenology, 2025)

Optimization strategies for the carbon footprint of aluminum-plastic materials under low-carbon targets - Jingqi Deng; Tingting Hu; Mengqi Han; Yan Liu; Yusen Duan; Dungang Gu; Guanghui Li; Jiaqi Lu (Journal of Cleaner Production, 2025)

Development and characterization of novel wood-based composite materials for solar-powered atmospheric water harvesting: A machine intelligence supported approach - Xingying Zhang; Yangyang Xu; Shenjie Han; Xiang Weng; Wenbo Che; Kongjie Gu; Ying Guan; Youming Yu; Derek Hao; Junfeng Hou (Journal of Cleaner Production, 2025)

Synthesis of lactulose via semi-rational design Aided evolution of glucose isomerase - Chenlu Zhu; Jian He; Jiali Gu; Xiaomei Lyu; Renjiao Han; Han Liu; Caiyun Wang; Ruijin Yang (Food Bioscience, 2025)

Machine learning models for predicting indoor airborne fungal concentrations in public facilities utilizing environmental variables - Bong Gu Lee; Ki Heon Jeong; Han Eol Kim; Min-Kyeong Yeo (Environmental Pollution, 2025)

Study on rock-breaking mechanism of impact trenching in underground diaphragm wall with consideration of slurry effects - Ri-cheng Miao; Zi-han Gu; Cao Wang; Wei Cui (Computers and Geotechnics, 2025)

Optimizing Fe-based catalysts for CO2 hydrogenation using combined theoretical predictions and experimental insights - Seung Ju Han; Jingyu Chen; Hae-Gu Park; Ki-Won Jun; Seok Ki Kim (Chemical Engineering Journal, 2025)

Tailoring oxygen vacancies of W-doped TiO2 to stabilize Ir for boosting oxygen evolution activity in proton-exchange membrane water electrolysis - Jae-Ik Han; Deok-Hye Park; Da-Mi Lim; Yoonhi Gu; Seon-Ha Park; Chan-Eui Hong; Dong-Geon Seo; Ji-Hwan Kim; Jae-Sung Jang; Eo-Jin Kim; Ji-Woong Yun; Hyun-Moon Jo; et al. (Chemical Engineering Journal, 2025)

Charge separation engineering modulates self-oxygenating nano-heterojunctions to induce ferroptosis for sonodynamic-immunotherapy of tumors - Xueyu Li; Huihui Qian; Jun Du; Junjie Pan; Qian Wang; Han Yang; Liping Gu; Xiaoyuan Zhong; Yuqing Miao; Yuhao Li (Chemical Engineering Journal, 2025)

Covalent organic frameworks supported geminal-atom catalysts for upcycling nitrate into single-cell protein - Jing-Dong Feng; Wen-Da Zhang; Han Zhao; Bixuan Gu; Yong Liu; Xiaomei Lyu; Huan Pang; Liangliang Xu; Zhi-Guo Gu (Chemical Engineering Journal, 2025)

Broad-spectrum anti-inflammatory and antioxidant therapy of inflammatory-storm actuated diseases via programmable self-derived cryo-dead neutrophils - Bin Li; Qiuxia Gao; Yunxia Wu; Hongyi Lei; Shengchao Ma; Wei Wang; Hang Sun; Weifeng Ma; Judun Zheng; Chenchen Yuan; Yunlong Zhang; Yue Jia; et al. (Chemical Engineering Journal, 2025)

Multifunctional flexible MXene/TA@CNC electronic hydrogel patch with robust adhesion and self-healing properties for wearable electronics - Haoyu Wang; Ping Han; Ying Yu; Shaolong Han; Yue Qiao; Yuehan Li; Bin Sun; Zheng Gu (Chemical Engineering Journal, 2025)

Efficient and green extraction of chitin from Hermetia illucens using deep eutectic solvents and its application for rapid hemostasis - Ying Wang; Hanlu Chen; Xiaoli Liu; Jingxuan Song; Senxin Xu; Reziwanguli Abulaiti; Dongmei Han; Yang Hu; Zhihua Wang; Fubo Gu (Carbohydrate Polymers, 2025)

Characteristics of elevated PM2.5 events driven by enhanced organic compound concentrations in a South Korean residential city - Hye-Ji Lee; Hyo-Won Lee; Sung-Won Park; Ji-Won Jeon; Pyung-Rae Kim; Kyung-Hwan Kwak; Young-Ji Han; Thomas M. Holsen; Seung-Ha Lee; Hyun-Gu Jung; Seung-Hwan Cha; Jung-Min Park; et al. (Atmospheric Environment, 2025)

Study on the mechanism of activating SIRT1/Nrf2/p62 pathway to mediate autophagy-dependent ferroptosis to promote healing of diabetic foot ulcers - Qinglin Han; Yuming Gu; Yongquan Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Prediction and in-depth analysis of precast concrete strength by machine learning - Jiarui Gu; Chao Wei; Shanliang Ma; Jie Wang; Yang Shao; Zengqi Zhang; Xiaoming Liu; Lilei Zhu; Chun Han (Innovative Infrastructure Solutions, 2025)

Differentiating low-carbon waste management strategies for bio-based and biodegradable plastics under various energy decarbonization scenarios - Yuxin Huang; Mengqi Han; Zhujie Bi; Nannan Gu; Dungang Gu; Tingting Hu; Guanghui Li; Jiaqi Lu (Waste Management, 2025)

Biomagnetic monitoring of urban atmospheric pollution: A review of magnetic signatures from different types of plants - Gu Chen-ming; Wang Bo; Sun Xiao-han (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Research on multi-field coupling characteristics of ice-cutting with sharpened propeller blade profiles based on PD-FEM coupling method - Chenxu Gu; Chengjie Cao; Kang Han; Tao Jiang; Chunhui Wang (Ocean Engineering, 2025)

A shear strength criterion of rock joints under dynamic normal load - Qiang Zhang; Qiuxin Gu; Shuchen Li; Hongying Wang; Guilei Han (International Journal of Rock Mechanics and Mining Sciences, 2025)

Promoting the catalytic performance by tungstophosphoric acid modification Fe0.15Ce0.85 bimetal oxide catalysts for NH3-SCR - Chengheng Huang; Shifei Gu; Qiuju Qin; Xiaorong Han; Donghai Mo; Zhengjun Chen; Bin Li; Hongyan Zhang; Lihui Dong (Fuel, 2025)

Occurrence of organophosphate flame retardants in agricultural products from Korean markets - Eun Seon Jeong; Taek Gu Han; Jin Hwan Kim; Kyung Tae Kim; Dong-Kyu Lee; Sang Beom Han; Jong Seong Kang; Yong Seok Choi; Hyung Min Kim (Food Control, 2025)

Research on improving the accuracy of remote sensing-based bathymetry on muddy coasts - Xuelian Xu; Qiqi Pan; Han Wu; Dong Zhang; Zhuo Zhang; Yunjuan Gu; Zaifeng Wang (Estuarine, Coastal and Shelf Science, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Screening of Genes Associated with Immune Infiltration of Discoid Lupus Erythematosus Based on Weighted Gene Co-expression Network Analysis - Yuru Han; Shuang Liu; Shuo Shi; Yongyong Shu; Changlian Lu; Xuefeng Gu (Biochemical Genetics, 2025)

Investigation of Feeding Effects and Environmental Impact of Fish-Feed Quality: Evidence from Crucian Carp Feeding Experiments - Jiayin Wang; Ran Wu; Jianhua Wang; Jiangtao Guo; Ya Zhang; Nanbing Shi; Jinxing Gu; Yibing Han; Xinyi Guo; Zhe Yu; Guoxi Li; Zhenjiang Yang (Fishes, 2025)
The effects of three types of feed, purchased from online stores and having similar prices, on the growth performance and culture environment of crucian carp (Carassius auratus) were studied in this experiment, which aimed to provide a reference for the evaluation and selection of fish feed. The results showed that feeding different feeds had a significant effect on crucian carp, and that the growth-promoting effect of HD feed (feed produced by Haida Company Limited) was significantly better than that of the other two feeds. For example, the weight gain rate (WGR) of fish in the HD group was 47.1% higher than that in the LD group (p

Impacts of low-carbon city pilot policy on ecological well-being performance across Chinese cities: A spatial difference-in-difference analysis - Hongfang Han; Runde Gu; Yangyang Yang (Sustainable Cities and Society, 2025)

Soil erodibility and hillslope erosion processes affected by vegetation restoration duration - Ya Liu; Gang Liu; Ju Gu; Hongqiang Shi; Hairu Li; Yuqian Han; Dandan Liu; Xiaolin Xia; Zhen Guo (Soil and Tillage Research, 2025)

Co-capture and recovery of ammonia and CO2 driven by microbial electrolysis system coupling with mineral carbon sequestration by industrial wastes - Shujuan Liu; Guofang Ding; Ruize Gu; Jianxin Hao; Pengcheng Liu; Wenyong Qin; Yanling Yu; Yu Han; Jianjun Huang; Weihua He (Resources, Conservation and Recycling, 2025)

Molecular networking-guided isolation of melanogenesis inhibitory dihydro-β-agarofuran sesquiterpenoids from Celastrus orbiculatus - Jun Gu Kim; Jae Sang Han; Yong Beom Cho; Beom Kyun An; Dongho Lee; Mi Kyeong Lee; Bang Yeon Hwang (Phytochemistry, 2025)

Targeted isolation of dimeric sesquiterpene lactones and sesquiterpene derivatives from the roots of Inula helenium - Jae Sang Han; Jun Gu Kim; Yong Beom Cho; Beom Kyun An; Dongho Lee; Mi Kyeong Lee; Bang Yeon Hwang (Phytochemistry, 2025)

Numerical study of regular wave dynamics for optimizing coral reef restoration - Jiuming Han; Yanjun Li; Xizeng Zhao; Tao Liu; Yanzhen Gu; Shuangyan He; Peiliang Li; Ruili Sun (Ocean Engineering, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Utilization of emulsion gels in plant-based meat analog formulations: A review - Vahinika Kothuri; Jong Hyeon Han; Dong Hyun Keum; Hyuk Cheol Kwon; Do Hyun Kim; Sung Gu Han (Food Hydrocolloids, 2025)

Interface-induced Fe-rich NixFe3-xO4 electrode for efficient oxygen evolution at high current densities - Yiting Zhao; Yahui Wei; Shaonan Gu; Pengfei Yan; Hongbo Zhang; Jingyun Jiang; Qun Xu; Buxing Han (Chemical Engineering Journal, 2025)

Circular RNA-chimeric CeO2 nanoplatform maintains protective autophagy in macrophages for periodontitis - Yue Han; Liu Yang; Jing Zhang; Shuyuan Qu; Ziming Wang; Bin Gu; Yilong Zhao; Yufeng Zhang; Qin Zhao; Yaoting Ji (Chemical Engineering Journal, 2025)

Single-cell omics: experimental workflow, data analyses and applications - Fengying Sun; Haoyan Li; Dongqing Sun; Shaliu Fu; Lei Gu; Xin Shao; Qinqin Wang; Xin Dong; Bin Duan; Feiyang Xing; Jun Wu; Minmin Xiao; et al. (Science China Life Sciences, 2025)

Design, synthesis, and evaluation of antitumor activity of quinazoline derivatives containing different terminal segments of basic amine groups - Shihao Wang; Zichen Yang; Dongling Gu; JiaHui Han; Hongjing Chen; Hao Wang; JiaXin Zheng; Hongmin Liu; Yu Ke; Qiurong Zhang (Medicinal Chemistry Research, 2025)

Cadmium Exposure was Associated with Sex-Specific Thyroid Dysfunction: Consistent Evidence from Two Independent Cross-Sectional Studies Based on Urinary and Blood Cadmium Measurements - Ranqi Shao; Liqin Su; Peng Wang; Xu Han; Ting Wang; Jun Dai; Yi Gu; Jiao Luo; Lifang Deng; Jingping Liu (Biological Trace Element Research, 2025)

Isoalcanivorax beigongshangi sp. nov., isolated from the fermented grains of Chinese baijiu - Tong-Xi Zhang; Yi-Ming Li; Hao-Yue Gu; Ru Zhang; Zhan-Bin Sun; Han-Xu Pan; Qing Ren (Antonie van Leeuwenhoek, 2025)

Plant growth strategies and microbial contributions to ecosystem nitrogen retention along a soil acidification gradient - Ying Zhang; Ruzhen Wang; Baitao Gu; Heyong Liu; Feike A. Dijkstra; Xingguo Han; Yong Jiang (Ecology, 2025)
Nitrogen (N) retention is a critical ecosystem function associated with sustainable N supply. Lack of experimental evidence limits our understanding of how grassland N retention can vary with soil acidification. A 15 N‐labeling experiment was conducted for 2 years to quantify N retention by soil pathways and plant functional groups across a soil‐acidification gradient in a meadow. The 15 N added to the ecosystem was mainly intercepted by the soil (up to 87.3%). Within the soil, 15 N recovery in ammonium, dissolved organic N, microbial biomass, and amino sugars (a proxy for microbial necromass) represented approximately 46% of soil‐retained 15 N. 15 N recovery in these N fractions increased with acidification, highlighting the complexity of microbial N transformations that affect ecosystem N retention. Plant 15 N‐retention increased in sedges, decreased in forbs, and was unaffected in grasses with acidification, reflecting their divergent associations with mycorrhizas and sensitivities to soil acidification. Soil microbial biomass was the key variable delineating soil N retention, while sedges were critical for plant N retention, resulting in a clear trade‐off and competition in 15 N retention between the two compartments. Overall, acidification might curb N losses by strengthening microbial retention and shifting plant N retention among different plant growth strategies.

Development of an autonomous drone spraying control system based on the coefficient of variation of spray distribution - Pingan Wang; Adhitya Saiful Hanif; Seung-Hwa Yu; Chun-Gu Lee; Yeong Ho Kang; Dae-Hyun Lee; Xiongzhe Han (Computers and Electronics in Agriculture, 2024)

Evacuation efficiency and survival rate of bent-over walking during horizontal cabin fire evacuation - Haoyang Han; Guohui Lan; Hui Song; Chengtao Yi; Dongliang Gu; Jingwei Du (Ocean Engineering, 2024)

A novel collaborative collision avoidance decision method for multi-ship encounters in complex waterways - Han Dong; Rong Zhen; Qiyong Gu; Zhong Lin; Jiuhu Chen; Kai Yan; Bing Chen (Ocean Engineering, 2024)

Innovative multi-tagline anti-swing and positioning system: Dynamic analysis and experimental validation for slender-beam payloads in offshore environments - Maokai Sun; Shenghai Wang; Wanru Deng; Binteng Gu; Guangdong Han; Zhiming Yuan; Haiquan Chen; Yuqing Sun (Ocean Engineering, 2024)

Green method for preparation NaVO2 from vanadium-chromium slag based on Na2CO3 roasting and water leaching - Qiuping Li; Shaopeng Gu; Liang Yu; Funian Han; Jingmeng Dong; Chunmei Li; Jiaqi Jia (Journal of Environmental Chemical Engineering, 2024)

Corrigendum to “An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community” [Food Res. Int. 196 (2024) 115052] - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

Efficient electrocatalytic bromine evolution and extraction from wastewater by oxygen vacancy enriched Ti/Ov-Co3O4-NRs electrode - Xu Yin; Renping Li; Wei Li; Zhifeng Gao; Kajia Wei; Hongwei Zhu; Liankai Gu; Yun Jiang; Weiqing Han (Desalination, 2024)

Modeling obliquely incident seismic wave propagation in rocks via the FDM-DEM coupling scheme: Algorithms and applications - Kunsheng Gu; Jian Zhou; Fuchu Dai; Luqing Zhang; Wei Cheng; Zhenhua Han (Computers and Geotechnics, 2024)

Phosphorylation promotes liquid-phase proton transfer and carrier separation for boosted photocatalytic hydrogen evolution over g-C3N4 - Yongpan Gu; Yanan Han; Yike Li; Lu Zhang; Zhaohui Wang; Zhongjun Li (Chemical Engineering Journal, 2024)

Inhibition of the RXRA-PPARα-FABP4 signaling pathway alleviates vascular cellular aging by an SGLT2 inhibitor in an atherosclerotic mice model - Weiwei Zhang; Linghuan Wang; Yujia Wang; Yan Fang; Ruihua Cao; Zhiyi Fang; Dong Han; Xu Huang; Zhenghui Gu; Yingjie Zhang; Yan Zhu; Yan Ma; et al. (Science China Life Sciences, 2024)

Dysregulation of the Gut Microbiota Contributes to Sevoflurane-Induced Cognitive Dysfunction in Aged Mice by Activating the NLRP3 Inflammasome - Shanshan Han; Ruxi Bian; Yuxuan Chen; Junjie Liang; Peng Zhao; Yanfang Gu; Dengxin Zhang (Molecular Neurobiology, 2024)

Effects of Artificially Crushing Bedrock by Rotary Tillage on Soil Infiltration: A Field Study in a Shallow Hillslope in China - Guohui Luo; Shikang Yu; Yunwei Han; Huizhan Gu; Xinkui Yang; Yu Li; Tao Wu; Fucheng Li (Journal of Soil Science and Plant Nutrition, 2024)

Case studies of hailstorms in Shandong Province using hail size discrimination algorithm based on dual Polarimetric parameters - Juxiu Wu; Fan Xia; Jiawen Pan; Guanglu Han; Weijia Sun; Chen Gu (Frontiers of Earth Science, 2024)

Design Method for Low-Ice-Class Propellers Based on Multi-Objective Optimization - Chenxu Gu; Kang Han; Kaiqiang Weng; Chao Wang; Chunhui Wang (Journal of Marine Science and Engineering, 2024)
The objective of this paper was to establish a comprehensive methodology for the optimized design of propellers for ice-class vessels, aiming to enhance hydrodynamic efficiency while ensuring structural integrity. This paper begins by introducing a novel approach for calculating blade stress, which takes into account both extreme ice loads and hydrodynamic loads, to be utilized in the propeller strength design process. Subsequently, a backpropagation (BP) neural network model was developed based on the data obtained from B-series propeller charts and integrated with a genetic algorithm to achieve a preliminary optimized design of the propeller’s hydrodynamic performance. To illustrate the application of this methodology, a case study of an ice-breaking tug propeller design is presented, detailing the optimization design process, including the preliminary, intermediate, and final design stages. The study also addresses key aspects such as geometric parameterization, the selection of optimization variables, the implementation of optimization algorithms, and the balance of multi-objective trade-offs. The proposed design approach can serve as a valuable reference for the practical engineering design of propellers for ice-class vessels, providing a systematic framework for achieving optimal performance in challenging operating conditions.

Molecular evidence of internal carbon-driven partial denitrification in a mainstream pilot A-B system coupled with side-stream EBPR treating municipal wastewater - Da Kang; Yuan Yan; IL Han; Jangho Lee; Kester McCullough; Guangyu Li; Zijian Leo Wang; Peisheng He; Dongqi Wang; Stephanie Klaus; Ping Zheng; Varun Srinivasan; et al. (Water Research, 2024)

Corrigendum to “A time-space varying distributed unit hydrograph (TS-DUH) for operational flash flood forecasting using publicly-available datasets” [J. Hydrol. 642 (2024) 131785] - Ying Hu; Huan Wu; Lorenzo Alfieri; Guojun Gu; Koray K. Yilmaz; Chaoqun Li; Lulu Jiang; Zhijun Huang; Weitian Chen; Wei Wu; Qinzhe Han (Journal of Hydrology, 2024)

Visible-light-sensitive microrobots using H2O as fuel for highly efficient capture and precise detection of nanoplastics - Zhiqin Geng; Tangtang Deng; Bohan Gu; Xinting Qian; Rui Li; Linfen Duan; Junyang Li; Weiqing Han; Lulu Qu; Kajia Wei (Journal of Hazardous Materials, 2024)

The design of long afterglow pavement mixture by optimizing optical properties and basic road performance - Shu Yang; Leyu Chen; Chengjia Han; Yubin Huang; Fan Gu (Journal of Cleaner Production, 2024)

Surface S doping induced ladder-regulation of lattice oxygen on the vertical FeCoOOH for water oxidation - Ning Yu; Ren-Ni Luan; Chao-Yue Gu; Yi-Lin Dong; Guanqun Han; Han Hu; Bin Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

Simultaneous detection of Vibrio parahemolyticus and antimicrobial resistance genes using immonomagnetic separation combined with RPA-microfluidic method in seafood - Han Jiang; Jingwen Wang; Wenjie Jiang; Jing Wang; Xiuying Gu; Xiaorui Feng; Chenze Lu; Jiehong Fang (Food Control, 2024)

Multi-touch microcapsules/silicone-polyacrylate hybrid hydrogels with precise self-healing ability and their self-powered sensing applications in emergency rescue - Bingqian Zhao; Xiaolong He; Wenjian Li; Hang Zhang; Han Liu; Hua Qiu; Peng Gu; Kunlin Chen (Chemical Engineering Journal, 2024)

Design, synthesis and biological evaluation of novel pyrimidine-phenylsulfonylfuroxan hybrids - Dongling Gu; Shihao Wang; Zichen Yang; Hongjing Chen; Jiahui Han; Lingling Chi; Fuqiang Yu; Hao Wang; Jiaxin Zheng; Peirong Zhao; Hongmin Liu; Yu Ke; et al. (Medicinal Chemistry Research, 2024)

Application and evaluation of a modified intraparticle diffusion model for mono‑/multiadsorption of chlorobenzene pollutants on biochar - Wei Zhao; Lifei Yang; Wenjia Han; Chenggang Gu; Zhihong Xu; Xiuying Lv; Hui Zhang (Journal of Soils and Sediments, 2024)

Exploring the impact of sustainable finance on carbon emissions: Policy implications and interactions with low-carbon energy transition from China - Wei Zhang; Jie Han; Shiyi Kuang; Cem Işık; Ya Su; Gu Li Ni Ga Er Ju Lai Ti; Su Li; Zebang Xia; Anas Muhammad (Resources Policy, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

A time-space varying distributed unit hydrograph (TS-DUH) for operational flash flood forecasting using publicly-available datasets - Ying Hu; Huan Wu; Lorenzo Alfieri; Guojun Gu; Koray K. Yilmaz; Chaoqun Li; Lulu Jiang; Zhijun Huang; Weitian Chen; Wei Wu; Qinzhe Han (Journal of Hydrology, 2024)

Robust resiliency-oriented planning of electricity-hydrogen island energy systems under contingency uncertainty - Yulong Gu; Zhinong Wei; Yizhou Zhou; Sheng Chen; Haiteng Han; Guoqiang Sun; Haixiang Zang (Journal of Cleaner Production, 2024)

Construction of bienzyme-inorganic hybrid nanoflowers as a high-efficiency biocatalyst for the degradation of indole - Jiping Han; Qiang Zhang; Ke Zhang; Ying Liu; Deyu Rao; Yaohua Gu; Mingming Li; Huiqin Yao (Journal of Environmental Chemical Engineering, 2024)

Anthropogenic gadolinium contaminations in the marine environment and its ecological implications - Zhaolin Zhang; Wei Jiang; Tingwu Gu; Ning Guo; Ruipeng Sun; Yang Zeng; Yansong Han; Kefu Yu (Environmental Pollution, 2024)

In situ construction of ether-based composite electrolyte with stable electrode interphase for high-performance solid state lithium metal battery - Yixiao Zhang; Xue Ye; Han Fu; Yu Zhong; Xiuli Wang; Changdong Gu; Jiangping Tu (Chemical Engineering Journal, 2024)

Enhanced sensitivity of spectral CT imaging in vivo by using Ytterbium chelate - Chunmei Yang; Didi Gu; Xin Zhu; Pan Han; Liping Pan; Xiaoling Che; Xinyao Chen; Qiuyu Meng; Guidong Dai; Lu Yang (Chemical Engineering Journal, 2024)

Polystyrene microplastics induce molecular toxicity in Simocephalus vetulus: A transcriptome and intestinal microorganism analysis - Chenxi Zhu; Hui Zhou; Mengyu Bao; Shengkai Tang; Xiankun Gu; Mingming Han; Peng Li; Qichen Jiang (Aquatic Toxicology, 2024)

Effects of 6-methoxybenzoxazolinone (6-MBOA) on animals: state of knowledge and open questions - Jia-Yi Shi; Ke-Han Gu; Sheng-Mei Yang; Wan-Hong Wei; Xin Dai (The Science of Nature, 2024)

Quercetin alleviates kidney damage caused by mercury Chloride: The protective effects of quercetin on autophagy and inflammation were studied based on TRIM32/TLR4/LC3 pathway - Fan Jin; JiaYue Li; Chenyu Zhao; Lixiang Gu; Min Pu; Simin Jiang; Mingming Liang; Ying Zhao; Jianli Shen; Agabuwei Agabuwei; Qin Han; Dan Liao (Toxicon, 2024)

Follicular fluid exosome-derived miR-339-5p enhances in vitro maturation of porcine oocytes via targeting SFPQ, a regulator of the ERK1/2 pathway - Yue Han; Junzheng Zhang; Wanfeng Liang; Yanqiu Lv; Xiaotong Luo; Chunyu Li; Xinglin Qu; Yuyang Zhang; Weiyu Gu; Xuan Chen; Yi Jin (Theriogenology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Chemosensory protein 22 in Riptortus pedestris is involved in the recognition of three soybean volatiles - Nan Gu; Yu-Wen Chen; Sai Ma; Qiang Liu; Jian-Qiao Li; Shu-Han Yang; Wen-Wen Zhu; Jin-Bu Li; Xiu-Yun Zhu; Xiao-Ming Li; Ya-Nan Zhang (Pesticide Biochemistry and Physiology, 2024)

SedaDNA reveals mid-to late Holocene aquatic plant and algae changes in Luanhaizi Lake on the Tibetan Plateau - Xu Han; Lianfang Feng; Naimeng Zhang; Shihua Hu; Zhengquan Gu; Xiaozhong Huang; Xiaoyan Yang; Fahu Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Emission characteristics of lead and particulate matter from lead and zinc smelters in China - Jiawei Zhang; Xiaohui Sun; Qingru Wu; Jianguo Deng; Zhijian Li; Minneng Wen; Liwen Xu; Yongzheng Gu; Tao Han; Lei Feng; Lei Duan (Journal of Hazardous Materials, 2024)

Straw removal reduces Cd availability and rice Cd accumulation in Cd-contaminated paddy soil: Cd fraction, soil microorganism structure and porewater DOC and Cd - Hang Zhou; Zi-Yu Wang; Chang Li; Hai-Wei Yuan; Lu Hu; Peng Zeng; Wen-Tao Yang; Bo-Han Liao; Jiao-Feng Gu (Journal of Hazardous Materials, 2024)

Integrating genomics, molecular docking, and protein expression to explore new perspectives on polystyrene biodegradation - Qing Qiu; Han Li; Xuejian Sun; Kejian Tian; Jinming Gu; Fenglin Zhang; Dandan Zhou; Xinwen Zhang; Hongliang Huo (Journal of Hazardous Materials, 2024)

Integrated framework for dynamic conservation of bamboo forest in giant panda habitat under climate change - Xiaotong Shang; Weirui Qin; Biao Yang; Qiang Dai; Han Pan; Xuyu Yang; Xiaodong Gu; Zhisong Yang; Zejun Zhang; Li Zhang (Journal of Environmental Management, 2024)

A preliminary integrated analysis of regional paleoclimate variations in China over the past ∼ 21 ka - Huayu Lu; Yan Zhao; Xiangdong Yang; Haibing Wu; Cheng Zhao; Jingjing Wang; Xiaoyong Wang; Xueyuan Kuang; Xiaojian Zhang; Chunmei Ma; Fuzhi Lu; Xiayun Xiao; et al. (Global and Planetary Change, 2024)

Optimized data representation and understanding method for the intelligent design of shear wall structures - Jin Han; Xinzheng Lu; Yi Gu; Wenjie Liao; Qing Cai; Hongjing Xue (Engineering Structures, 2024)

Efficient modeling of fractional Laplacian viscoacoustic wave equation with fractional finite-difference method - Bingluo Gu; Shanshan Zhang; Xingnong Liu; Jianguang Han (Computers & Geosciences, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

A near-complete cucumber reference genome assembly and Cucumber-DB, a multi-omics database - Jiantao Guan; Han Miao; Zhonghua Zhang; Shaoyun Dong; Qi Zhou; Xiaoping Liu; Diane M. Beckles; Xingfang Gu; Sanwen Huang; Shengping Zhang (Molecular Plant, 2024)

Synergistic effects of ε-poly-l-lysine and lysozyme against Pseudomonas aeruginosa and Listeria monocytogenes biofilms on beef and food contact surfaces - Ah. Jin Cho; Sangha Han; Shamsun Nahar; Eun Her; June Gu Kang; Sang-Do Ha (Meat Science, 2024)

Spectral intelligent detection for aflatoxin B1 via contrastive learning based on Siamese network - Hongfei Zhu; Yifan Zhao; Qingping Gu; Longgang Zhao; Ranbing Yang; Zhongzhi Han (Food Chemistry, 2024)

Screening and evaluation of a novel nucleotide-degrading Levilactobacillus brevis grx821 with anti-hyperuricemia ability - Haiying Wang; Jiaxing Dai; Yifeng Han; Yunchao Wa; Dawei Chen; Renqin Yang; Yujun Huang; Hua Wei; Ruixia Gu; Boxing Yin; Wenlong Ma (Food Bioscience, 2024)

Bifunctional energy materials based on cellulose ionic complexes toward low-grade heat and photon energy storage - Lei Zhang; Jingjing Gu; Guoqiang Zhang; Qianyao Du; Han Liu; Xiliang Luo; Zhongtao Wu (Chemical Engineering Journal, 2024)

Injectable exosome-loaded quaternized chitosan/oxidized sodium alginate hydrogel with self-healing, bioadhesive, and antibacterial properties for treating combined radiation-wound injury - Guanqun Peng; Jia Hu; Jinnan Guo; Jiahui Dong; Yuanyuan Zhao; Tong Ye; Fengjun Xiao; Zhiyun Meng; Hui Gan; Ruolan Gu; Peng Han; Wenzhong Sun; et al. (Chemical Engineering Journal, 2024)

Recent advances in spoilage mechanisms and preservation technologies in beef quality: A review - Yiqun Zhu; Mengqing Gu; Yuhan Su; Zhe Li; Zhigang Xiao; Fei Lu; Chunyang Han (Meat Science, 2024)

Spatiotemporal carbon footprint analysis of bottled water production by ultrafiltration and reverse osmosis - Wenqi Hu; Mengqi Han; Dungang Gu; Robin Smith; Tingting Hu; Yuhang Lou; Yiran Sun; Guanghui Li; Nan Zhang; Jiaqi Lu (Journal of Water Process Engineering, 2024)

Covalently doping polyaniline-based photothermal fabric for continuous recovery of salt and freshwater from seawater via solar-driven interfacial evaporation - Kang Chen; Tao Cui; Xiaogang Xue; Mengtao Fu; Yunyou Yao; Chen Huang; Jie Chen; Jiaguang Han; Jianzhong Gu; Bowu Zhang; Gang Xu; Hongjuan Ma (Desalination, 2024)

Bridging the buried interface with conjugated molecule for highly efficient carbon-based inorganic CsPbI2Br perovskite solar cells fabricated in air - Yifei Shi; Lei Zhang; Shuming Hu; Xu Wang; Jiajia Han; Jincheng Huang; Junjie Chen; Yuanfang Zhang; Xinlong Zhang; Jintao He; Hengzhi Zuo; Jiayao Ju; et al. (Chemical Engineering Journal, 2024)

This is MATE: A Multiple scAttering correcTion rEtrieval algorithm for accurate lidar profiling of seawater optical properties - Yatong Chen; Xiaoyu Cui; Qiuling Gu; Yudi Zhou; Hongkai Zhao; Han Zhang; Shizhe Ma; Peituo Xu; Henrich Frielinghaus; Lan Wu; Chong Liu; Wenbo Sun; et al. (Remote Sensing of Environment, 2024)

Enzyme-free intelligent films in electrochemistry of malathion with a binary architecture: Combined Cu2+ complexed carbon nitride nanosheets and poly(N,N-dimethylacrylamide) hydrogels - Xinyu Wang; Jiping Han; Ke Zhang; Ying Liu; Changyi Yang; Keren Shi; Lingchen Meng; Shuo Gu; Huiqin Yao (Journal of Environmental Chemical Engineering, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Effects of the physical structure and surface charge of activated carbon on the reduction of biogenic amines in anchovy fish sauce - Kil Bo Shim; Jung-Jin In; Jong Bong Lee; Hyeong Gu Han; Seong Ah Son; Woo Jin Lee; Yeon Joo Bae; Ga Yeon Kwon; Byoung Kyu An (Food Chemistry, 2024)

Dominance by cyanobacteria in the newly formed biofilms on stone monuments under a protective shade at the Beishiku Temple in China - Yong Zhang; Fasi Wu; Ji-Dong Gu; Kun He; Zhou Fang; Xiaobo Liu; Dongpeng He; Xinghua Ding; Jie Li; Zengyang Han; Qi Zhang; Huyuan Feng (Environmental Research, 2024)

Modulations of ocean-atmosphere interactions on squid abundance over Southwest Atlantic - Chia-Ying Ko; Yu-Chi Lee; Yi-Chi Wang; Huang-Hsiung Hsu; Chun Hoe Chow; Ruei-Gu Chen; Tsung-Han Liu; Chih-Shin Chen; Tai-Sheng Chiu; Don-Hsieh Chiang; Ren-Fen Wu; Wan-Ling Tseng (Environmental Research, 2024)

Surface hydroxyl groups mediated g-C3N4-Modified perovskite catalytic ozone oxidation interface activation and silicon salt resistance mechanism - Shengzhe Wang; Xianru Li; Weiyang Xue; Bin Gu; Peiwei Han; Chenxing Yao; Huangzhao Wei; Chenglin Sun (Chemical Engineering Journal, 2024)

Comprehensive review of microbial production of medium-chain fatty acids from waste activated sludge and enhancement strategy - Xin Gu; Jing Sun; Tong Wang; Jia Li; Han Wang; Jialin Wang; Yayi Wang (Bioresource Technology, 2024)

Spatial Distribution, Risk Assessment, Source Apportionment and Stabilization Performance of Potentially Toxic Elements in Sediments of Dongdagou River, Northwest China - Duan Zhao; Yimin Sang; Qian Zhang; Yang Man; Yanhe Han; Bin Wu; Caiyun Guo; Qingbao Gu (Water, Air, & Soil Pollution, 2024)

Pollution characteristics, source apportionment, and health risk assessment of PM10 and PM2.5 in rooftop and kerbside environment of Lanzhou, NW China - Chen-ming Gu; Bo Wang; Qu Chen; Xiao-han Sun; Mei Zhang (Environmental Science and Pollution Research, 2024)

Identification of lignans as ATP citrate lyase (ACLY) inhibitors from the roots of Pouzolzia zeylanica - Jin-Long Li; Jia-Yi Jiang; Shan-Shan Gu; Lei Zhang; Yan Sun; Xue-Han Wang; Dan-Yu Li; Zhe-Yu Chen; Sheng-Shi Jiang; Wei-Zhong Zhu; Hao-Wen Jiang; Hong-Jie Zhang (Natural Product Research, 2024)

Crosstalk among proximal tubular cells, macrophages, and fibroblasts in acute kidney injury: single-cell profiling from the perspective of ferroptosis - Yulin Wang; Ziyan Shen; Shaocong Mo; Han Zhang; Jing Chen; Cheng Zhu; Shiqi Lv; Di Zhang; Xinhui Huang; Yulu Gu; Xixi Yu; Xiaoqiang Ding; et al. (Human Cell, 2024)
The link between ferroptosis, a form of cell death mediated by iron and acute kidney injury (AKI) is recently gaining widespread attention. However, the mechanism of the crosstalk between cells in the pathogenesis and progression of acute kidney injury remains unexplored. In our research, we performed a non-negative matrix decomposition (NMF) algorithm on acute kidney injury single-cell RNA sequencing data based specifically focusing in ferroptosis-associated genes. Through a combination with pseudo-time analysis, cell–cell interaction analysis and SCENIC analysis, we discovered that proximal tubular cells, macrophages, and fibroblasts all showed associations with ferroptosis in different pathways and at various time. This involvement influenced cellular functions, enhancing cellular communication and activating multiple transcription factors. In addition, analyzing bulk expression profiles and marker genes of newly defined ferroptosis subtypes of cells, we have identified crucial cell subtypes, including Egr1 + PTC-C1, Jun + PTC-C3, Cxcl2 + Mac-C1 and Egr1 + Fib-C1. All these subtypes which were found in AKI mice kidneys and played significantly distinct roles from those of normal mice. Moreover, we verified the differential expression of Egr1, Jun, and Cxcl2 in the IRI mouse model and acute kidney injury human samples. Finally, our research presented a novel analysis of the crosstalk of proximal tubular cells, macrophages and fibroblasts in acute kidney injury targeting ferroptosis, therefore, contributing to better understanding the acute kidney injury pathogenesis, self-repairment and acute kidney injury-chronic kidney disease (AKI-CKD) progression.

Enhancing Growth and Intestinal Health in Triploid Rainbow Trout Fed a Low-Fish-Meal Diet through Supplementation with Clostridium butyricum - Chang’an Wang; Fangyuan Li; Di Wang; Shaoxia Lu; Shicheng Han; Wei Gu; Haibo Jiang; Zhuang Li; Hongbai Liu (Fishes, 2024)
This study evaluates the effects of dietary Clostridium butyricum on growth performance and intestinal health in triploid rainbow trout (Oncorhynchus mykiss). Administered in a 12-week trial, five isonitrogenous and isolipidic feeds contained different C. butyricum levels [G1 (0), G2 (1.6 × 106 CFU/g), G3 (1.2 × 107 CFU/g), G4 (1.1 × 108 CFU/g), and G5 (1.3 × 109 CFU/g)]. Significant enhancements in growth performance, including improved feed conversion ratios and specific growth rates in the G4 group, were indicative of enhanced nutrient utilization, corroborated by optimal digestive enzyme activity levels. Antioxidant capabilities were also enhanced in the G4 group, indicated by increased serum superoxide dismutase and catalase activities, along with a significant decrease in malondialdehyde levels. Gut microbiota analysis indicated a probiotic concentration-dependent modulation of microbial communities, with a marked enrichment in beneficial bacterial phyla like Firmicutes in the G4 group. This microbial shift correlated with significant downregulations in immune-related gene expressions, including interleukins (IL-1β, IL-8), NF-κB, MyD88, and TNF-α, highlighting an activated immune response. Correspondingly, serum lysozyme and immunoglobulin M contents were significantly elevated in the G4 group. Challenge tests with Aeromonas salmonicida exhibited the higher disease resistance of fish fed the G4 diet. In conclusion, the study shows the potential of dietary C. butyricum, especially at 1.1 × 108 CFU/g, in enhancing the growth, health, and disease resistance of triploid rainbow trout through modulating gut microflora and stimulating immune responses.

Effects of COVID-19 on coastal and marine environments: Aggravated microplastic pollution, improved air quality, and future perspective - Yixuan Han; Xiang Gu; Chunye Lin; Mengchang He; Yidi Wang (Chemosphere, 2024)

Research progress on improving the freeze-drying resistance of probiotics: A review - Sitong Ge; Jiarun Han; Qiaoyu Sun; Qingqing Zhou; Zhongdu Ye; Ping Li; Qing Gu (Trends in Food Science & Technology, 2024)

Adavosertib-encapsulated metal-organic frameworks for p53-mutated gallbladder cancer treatment via synthetic lethality - Shijie Li; Sarun Juengpanich; Win Topatana; Tianao Xie; Lidan Hou; Yiyuan Zhu; Jiadong Chen; Yukai Shan; Yina Han; Ziyi Lu; Tianen Chen; Charlie Topatana; et al. (Science Bulletin, 2024)

Vessel intrusion interception utilising unmanned surface vehicles for offshore wind farm asset protection - Yang Gu; Peiji Wang; Zhenwei Rong; Hao Wei; Shujie Yang; Kui Zhang; Zili Tang; Tao Han; Yulin Si (Ocean Engineering, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Pliocene CO2 rise due to sea-level fall as a mechanism for the delayed ice age - Shiling Yang; Yongda Wang; Xiaofang Huang; Minmin Sun; Jingtai Han; Xu Wang; Zuoling Chen; Shihao Zhang; Wenying Jiang; Zihua Tang; Zhaoyan Gu; Shangfa Xiong; et al. (Global and Planetary Change, 2024)

Poly(vinylidene fluoride)-based composite membranes with continuous metal–organic framework layer for high-performance separators of lithium-ion batteries - Mengying Li; Sha Cheng; Jisong Zhang; Cheng Huang; Jiapei Gu; Jin Han; Xu Xu; Xiao Chen; Pengchao Zhang; Ya You (Chemical Engineering Journal, 2024)

Defect control for high efficiency antimony selenosulfide solar cells by interface Engineering of buried monoatomic aluminum oxide layer - Huafei Guo; Honcheng Zhu; Kangjun Geng; Tingyu Zhang; Shan Huang; Yusheng Yang; Xiang Fang; Xiaoshuang Zhou; Jian Su; Han Zhang; Shuai Zhang; Sai Jiang; et al. (Chemical Engineering Journal, 2024)

Effects of tillage regime on soil aggregate-associated carbon, enzyme activity, and microbial community structure in a semiarid agroecosystem - Chenglong Han; Weidi Zhou; Yanjie Gu; Junqiang Wang; Yanfang Zhou; Yunyin Xue; Zhiguo Shi; Kadambot H. M. Siddique (Plant and Soil, 2024)

Using the paddy eco-ditch wetland system to reduce nitrogen non-point source pollution discharge from paddies: A consecutive six-year study in the Yunnan Plateau, China - Huanhao Han; Xinru Wang; Haili Zheng; Bo Liu; Rong Gao; Yuanlai Cui; Xiaogang Liu; Shixiang Gu; Bochao Zhang; Ming Yang (Agriculture, Ecosystems & Environment, 2024)

Comammox and unknown ammonia oxidizers contribute to nitrite accumulation in an integrated A-B stage process that incorporates side-stream EBPR (S2EBPR) - Yuan Yan; Jangho Lee; IL Han; Zijian Wang; Guangyu Li; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Anand Patel; Jim McQuarrie; Beverley M. Stinson; et al. (Water Research, 2024)

Resource recovery and regeneration strategies for spent lithium-ion batteries: Toward sustainable high-value cathode materials - Kunhong Gu; Chiharu Tokoro; Yutaro Takaya; Jiang Zhou; Wenqing Qin; Junwei Han (Waste Management, 2024)

Janus biopolymer nanocomposite coating with excellent antibacterial and water/oxygen barrier performance for fruit preservation - Liubo Yuan; Ruiqi Liu; Yifan Zhou; Rongya Zhang; Sheng Chen; Qin Yang; Yingchun Gu; Linbo Han; Bin Yan (Food Hydrocolloids, 2024)

Morphology and phylogenetic relationships of two Antarctic strains within the genera Carolibrandtia and Chlorella (Chlorellaceae, Trebouxiophyceae) - Hyunsik Chae; Eun Jae Kim; Han Soon Kim; Han-Gu Choi; Sanghee Kim; Ji Hee Kim (Algae, 2024)

Revisiting the role of Acinetobacter spp. in side-stream enhanced biological phosphorus removal (S2EBPR) systems - Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Varun Srinivasan; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Peisheng He; Anand Patel; Charles Bott; et al. (Water Research, 2024)

Side-Stream Enhanced Biological Phosphorus Removal (S2EBPR) enables effective phosphorus removal in a pilot-scale A-B stage shortcut nitrogen removal system for mainstream municipal wastewater treatment - Dongqi Wang; Il Han; Kester McCullough; Stephanie Klaus; Jangho Lee; Varun Srinivasan; Guangyu Li; Zijian Leo Wang; Charles B. Bott; Jim McQuarrie; Beverley M. Stinson; Christine deBarbadillo; et al. (Water Research, 2024)

The pig intestinal phageome is an important reservoir and transfer vector for virulence genes - Yalu Ji; Hengyu Xi; Chong Chen; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; Jingmin Gu (Science of The Total Environment, 2024)

New policy framework for circular economy in South Korea: Achieving both management and chemical recycling of polymeric waste via pyrolysis reaction - Tae Uk Han; Jun-Gu Kang; Tae-Wan Jeon (Resources, Conservation and Recycling, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Significance of phosphate adsorbed on the cellular surface as a storage pool and its regulation in marine microalgae - Xian-Yang Zhang; Zhuo-Fan Li; Hai-Feng Gu; Ai-Qin Han; Feng-Xian Han; Lin-Jian Ou (Marine Environmental Research, 2024)

Diffusion kinetic processes and release risks of trace metals in plateau lacustrine sediments - Xiang Gu; Xiaotong Han; Peng Xing; Di Xu; Shiqiang Wan; Qinglong L. Wu; Fengchang Wu (Journal of Hazardous Materials, 2024)

A study on visual impact assessment of the enclosing wall entourage of Chinese traditional private garden - Zhongjv Yang; Chenping Han; Tao Gu; Lin Zhang; Guanjun Li; Jingjing Zhao; Xing Huang (Environmental Impact Assessment Review, 2024)

A study on the demographic differences in visual impact assessments of the external space of electric vehicle battery swapping stations - Lin Zhang; Chenping Han; Tao Gu; Guanjun Li; Xiwu Qi; Jingjing Zhao (Environmental Impact Assessment Review, 2024)

Surface residual alkali reverse utilization: Stabilizing the lay-structured oxide cathode for high stability potassium ion batteries - Haotian Shi; Xuan-Wen Gao; Xuanchen Wang; Hong Chen; Wenzhe Han; Qinfen Gu; Zhaomeng Liu; Wen-Bin Luo (Chemical Engineering Journal, 2024)

Bio-adhesive barrier with active ROS-scavenging ability for simultaneous management of dura tear and epidural inflammatory fibrosis - Meng Han; Jincheng Tang; Haiyue Zhao; Yachao Sheng; Ziang Li; Wenxiao Shi; Jiahao Wang; Chao Ma; Kun Xi; Yong Gu; Liang Chen (Chemical Engineering Journal, 2024)

Mechanical interlocking induced emission in two-dimensional covalent organic frameworks - Ruo-Meng Zhu; Wang-Kang Han; Yong Liu; Jia-Xing Fu; Jing-Dong Feng; Jinfang Zhang; Huan Pang; Zhi-Guo Gu (Chemical Engineering Journal, 2024)

Dynamic synthetic analysis of circulation field of tropical cyclones affecting Shanghai - Wen Gu; Caijun Yue; Zhihui Han; Yanqing Gao; Yuqi Tang; Xiangyu Ao; Yao Yao (Frontiers of Earth Science, 2024)

Tunneling route prediction of shield machine based on random forest P-wave generation - Su-zhen Shi; Jian-ying Gu; Zui-liang Liu; Pei-fei Duan; Qi Han; You-chao Qi; Xin Zhang (Applied Geophysics, 2024)

Diversification of food production in rapidly urbanizing areas of China, evidence from southern Jiangsu - Zhengming Gu; Xiaobin Jin; Xinyuan Liang; Jing Liu; Bo Han; Yinkang Zhou (Sustainable Cities and Society, 2024)

Integrated control strategy for dual sludge ages in the high-concentration powder carrier bio-fluidized bed (HPB) technology: Enhancing municipal wastewater treatment efficiency - Chengxian Wang; Xiaoli Chai; Bin Lu; Wei Lu; Hongbo Han; Yue Mu; Qun Gu; Boran Wu (Journal of Environmental Management, 2024)

Incorporating environmental capacity considerations to prioritize control factors for the management of heavy metals in soil - Yujie Pan; Wenjing Han; Huanhuan Shi; Xiaorui Liu; Shasha Xu; Jiarui Li; Hongxia Peng; Xinwen Zhao; Tao Gu; Chansgheng Huang; Ke Peng; Simiao Wang; et al. (Journal of Environmental Management, 2024)

Remote sensing image classification using an ensemble framework without multiple classifiers - Peng Dou; Chunlin Huang; Weixiao Han; Jinliang Hou; Ying Zhang; Juan Gu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Comparative analysis of key precursors and metabolites involved in flavor formation of different rapid-fermented Chinese fish sauces based on untargeted metabolomics analysis - Jiarun Han; Jialan Jiang; Xin Zhao; Xilian Zhao; Tao Kong; Ping Li; Qing Gu (Food Chemistry, 2024)

Metal-sensitized Au-Bi2O3 nanoheterojunction for immunogenic cell death-boosted sono-immuno cancer therapy - Guobo Chen; Jun Du; Liping Gu; Qian Wang; Qingwen Qi; Xueyu Li; Rui Zhang; Han Yang; Yuqing Miao; Yuhao Li (Chemical Engineering Journal, 2024)

Self-dispersed bimetallic NiRu nanoparticles on CeO2 for CO2 methanation - Tengfei Zhang; Peng Zheng; Jiajian Gao; Zhennan Han; Fangna Gu; Wenqing Xu; Fang Wang; Tingyu Zhu; Guangwen Xu; Ziyi Zhong; Fabing Su (Chemical Engineering Journal, 2024)

Upgrading dry acid pretreatment by post-hydrolysis for carbon efficient conversion of lignocellulose - Hanqi Gu; Xushen Han; Jian Zhang; Jie Bao (Bioresource Technology, 2024)

Magnetic characteristics of atmospheric particulate matter and its indication of atmospheric pollution during winter in Lanzhou, NW China - Bo Wang; Chen-ming Gu; Qu Chen; Mei Zhang; Xiao-han Sun; Jia Jia (Atmospheric Environment, 2024)

An analysis of lncRNAs related to fiber quality and the discovery of their target genes in a Gossypium hirsutum line with Gossypium mustelinum introgression - Baohua Wang; Meijun Ji; Hui Fang; Haijing Gu; Teame Gereziher Mehari; Jinlei Han; Wenxiang Feng; Xuehan Huo; Jingxia Zhang; Yu Chen; Jun Zhang; Allah Ditta; et al. (Theoretical and Applied Genetics, 2024)

Identifying spatial variability of water chemical characteristics and groundwater discharge in Hulun Lake integrated remote sensing data and chemical components - Mengyong Xue; Wenlin Wang; Xiaomin Gu; Bo Liu; Yanwen Jiao; Wanchen Zhang; Chuang Zhao; Yujie Han; Yi Tong (Environmental Science and Pollution Research, 2024)

Tartaric acid coupled with gibberellin improves remediation efficiency and ensures safe production of crops: A new strategy for phytoremediation - Teng-yue Yuan; Da-juan Wan; Wen-jun Yang; Jiao-feng Gu; Hang Zhou; Peng Zeng; Bo-han Liao (Science of The Total Environment, 2024)

Photochemical behavior of dissolved organic matter derived from Alternanthera philoxeroides hydrochar: Insights from molecular transformation and photochemically reactive intermediates - Xincai Gu; Bingfa Chen; Hong Liu; Yanfang Feng; Bingyu Wang; Shiying He; Muhua Feng; Guojun Pan; Shiqun Han (Journal of Hazardous Materials, 2024)

Metals recovery from polymetallic sulfide tailings by bioleaching functional bacteria isolated with the improved 9K agar: Comparison between one-step and two-step processes - Muqiu Hu; Xin Zhao; Jinghan Gu; Lulu Qian; Zhiqing Wang; Yuanyuan Nie; Xiaoyu Han; Long An; Haiqiang Jiang (Environmental Research, 2024)

HPF1 regulates tendon stem/progenitor cell senescence and tendon repair via PARP1-mediated poly-ADP ribosylation of HuR - Weifeng Han; Dongqiang GU; Hongguang Chen; Xu Tao; Lei Chen (Genes & Genomics, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Climate match is key to predict range expansion of the world's worst invasive terrestrial vertebrates - Yuanbao Du; Xuyu Wang; Sadia Ashraf; Weishan Tu; Yonghong Xi; Ruina Cui; Shengnan Chen; Jiajie Yu; Lixia Han; Shimin Gu; Yanhua Qu; Xuan Liu (Global Change Biology, 2024)
Understanding the determinants of the range expansion of invasive alien species is crucial for developing effective prevention and control strategies. Nevertheless, we still lack a global picture of the potential factors influencing the invaded range expansion across taxonomic groups, especially for the world's worst invaders with high ecological and economic impacts. Here, by extensively collecting data on 363 distributional ranges of 19 of world's worst invasive terrestrial vertebrates across 135 invaded administrative jurisdictions, we observed remarkable variations in the range expansion across species and taxonomic groups. After controlling for taxonomic and geographic pseudoreplicates, model averaging analyses based on generalized additive mixed‐effect models showed that species in invaded regions having climates more similar to those of their native ranges tended to undergo a larger range expansion. In addition, as proxies of propagule pressure and human‐assisted transportation, the number of introduction events and the road network density were also important predictors facilitating the range expansion. Further variance partitioning analyses validated the predominant role of climate match in explaining the range expansion. Our study demonstrated that regions with similar climates to their native ranges could still be prioritized to prevent the spread of invasive species under the sustained global change.

Novel rearrangements in the mitochondrial genomes of the Ceramiales (Rhodophyta) and evolutionary implications - Min Ho Seo; Shin Chan Kang; Kyeong Mi Kim; Min Seok Kwak; Jihoon Jo; Han-Gu Choi; Ga Hun Boo; Hwan Su Yoon (Algae, 2023)
The Ceramiales is the most diverse and species-rich group (2,669 spp.) of red algae, and it is widely distributed from tropical to polar oceans. Mitochondrial genomes (mitogenomes) and other genes have contributed to our knowledge regarding the classification and phylogeny of this diverse red algal group; however, the mitogenome architecture remains understudied. Here, we compared 42 mitogenomes, including 19 newly generated in this study, to expand our knowledge. The number of genes in mitogenome varied from 43 to 68 due to gene duplication. The mitogenome architecture was also variable, categorized into four types (A–D): type A = ancestral type with a basic composition; type B = those with inverse transpositions; type C = those with inverted duplications; and type D = those with both inversion and duplication. T﻿he palindromic and inverted repeats were consistently found in flanking regions of the rearrangement, especially near the cob and nad6 genes. The three rearranged mitogenome architectures (types B, C, D) are the first report of these in red algae. Phylogenetic analyses of 23 protein-coding genes supported the current familial classification of the Ceramiales, implying that the diversity of mitogenome architecture preceded the phylogenetic relationships. Our study suggests that palindromic and inverted repeats may drive mitogenome architectural variation.

Morphology and phylogenetic relationships of two Antarctic strains within the genera Carolibrandtia and Chlorella (Chlorellaceae, Trebouxiophyceae) - Hyunsik Chae; Eun Jae Kim; Han Soon Kim; Han-Gu Choi; Sanghee Kim; Ji Hee Kim (Algae, 2023)
The genera Carolibrandtia and Chlorella have been described as small green algae with spherical cell shapes that inhabit various environments. Species of these genera are often difficult to identify because of their simple morphology and high phenotypic plasticity. We investigated two small coccoid strains from Antarctica based on morphology, molecular phylogeny by two alignment methods which have been applied to previous phylogenetic studies of the genus Chlorella, and comparison of the secondary structures of nuclear small subunit (SSU) and internal transcribed spacer (ITS) rDNA sequences. Light microscopy of two strains revealed spherical cells containing chloroplasts with pyrenoids, and the morphological characteristics of the strains were nearly identical to those of other Chlorella species. However, based on the phylogenetic analyses of nuclear SSU and ITS rDNA sequences, it was determined that the Antarctic microalgal strains belonged to two genera, as the Chlorella and Carolibrandtia. In addition, the secondary structures of the SSU and ITS2 sequences were analyzed to detect compensatory base changes (CBCs) that were used to identify and describe the two strains. A unique CBC in the SSU rDNA gene was decisive for distinguishing strain CCAP 211/45. The ITS2 rDNA sequences for each strain were compared to those obtained previously from other closely related species. Following the comparison of morphological and molecular characteristics, we propose KSF0092 as a new species, Chlorella terrestris sp. nov., and the reassignment of the strain Chlorella antarctica CCAP 211/45 into Carolibrandtia antarctica comb. nov.

Physiological tolerance of black locust (Robinia pseudoacacia L.) and changes of rhizospheric bacterial communities in response to Cd and Pb in the contaminated soil - Xu-Feng Luo; Meng-Yu Liu; Zi-Xi Tian; Yue Xiao; Peng Zeng; Zi-Yu Han; Hang Zhou; Jiao-Feng Gu; Bo-Han Liao (Environmental Science and Pollution Research, 2023)

Progress in phytoremediation of chromium from the environment - Lingzhuo Han; Haiping Gu; Wenjie Lu; Hanyin Li; Wan-xi Peng; Nyuk Ling Ma; Su Shiung Lam; Christian Sonne (Chemosphere, 2023)

Distribution of microplastic contamination in the major tributaries of the Yellow River on the Loess Plateau - Xiaoli Zhao; Minmin Qiang; Yuan Yuan; Man Zhang; Wenjing Wu; Jiaocheng Zhang; Zesen Gao; Xinmei Gu; Sitian Ma; Zihan Liu; Lu Cai; Jianqiao Han (Science of The Total Environment, 2023)

Evaluating methane emissions from rice paddies: A study on the cultivar and transplanting date - Jae-Han Lee; Jun-Yeong Lee; Yun-Gu Kang; Jun-Ho Kim; Taek-Keun Oh (Science of The Total Environment, 2023)

Artificial light at night, MRI-based measures of brain iron deposition and incidence of multiple mental disorders - Jianbo Jin; Wenxing Han; Teng Yang; Zhihu Xu; Jin Zhang; Ru Cao; Yuxin Wang; Jiawei Wang; Xin Hu; Tiantian Gu; Fan He; Jing Huang; et al. (Science of The Total Environment, 2023)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

A glimpse of the re-granulation process after artificially crushing anammox granular sludge - Zhipeng You; Ji Zhao; Han Xiang; Jimiao Wang; Ruihuan Gu; Yan Zhang; Chuanhao Shen; Deshuang Yu; Xiaoxia Wang (Journal of Water Process Engineering, 2023)

A comparison of milk fat globule membranes and whey proteomes: New insight into variation nutrient differences between Buffalo, Cow, Goat, and Yak - Lu Chen; Tiannuo Hong; Ziqi Li; Guohui Shen; Yanting Gu; Juan Han (Food Chemistry, 2023)

Inhibitory effects and action mechanism of five antioxidant peptides derived from wheat gluten on cells oxidative stress injury - Wenying Liu; Jie Ren; Hanshuo Wu; Xinxue Zhang; Lujia Han; Ruizeng Gu (Food Bioscience, 2023)

Performance comparison of anthocyanin-based smart indicator films - Zhigang Xiao; Linna Han; Mengqing Gu; Yiqun Zhu; Yifan Zhang; Zhe Li; Tiemin Xie; Fei Lu (Food Packaging and Shelf Life, 2023)

Identification of a fundamental cryoinjury mechanism in MSCs and its mitigation through cell-cycle synchronization prior to freezing - Brian H. Johnstone; Dongsheng Gu; Chieh-Han Lin; Jianguang Du; Erik J. Woods (Cryobiology, 2023)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

Telluribacter roseus sp. nov., Isolated from the Kumtag Desert Soil - Chu-Ying Feng; Jia-Rui Han; Chun-Yan Lu; Li Gu; Shuai Li; Wen-Hui Lian; Lei Dong; Wen-Jun Li (Current Microbiology, 2023)

Altered connectivity in the cognitive control-related prefrontal cortex in Parkinson’s disease with rapid eye movement sleep behavior disorder - Jinjing Liu; Xiaoya Zou; Jinming Gu; Qian Yu; Zhaoying Dong; Hongzhou Zuo; Xiaocui Chen; Xinyi Du; Dezhi Zou; Yu Han; Juan Peng; Oumei Cheng (Brain Imaging and Behavior, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Online learning-based active disturbance rejection control of autonomous surface vehicles with HIL simulations - Bo Peng; Nan Gu; Dan Wang; Tieshan Li; Bing Han; Zhouhua Peng (Ocean Engineering, 2023)

Enhanced heat-integrated distillation processes: Simultaneous synthesis via structural modification utilizing the matrix method - Nan Hu; Qingpeng Wu; Han Yue; Zhongqi Ren; Junjie Gu; Hongkang Zhao; Qunsheng Li (Journal of Cleaner Production, 2023)

A linear positive relationship between tree species diversity and forest productivity across forest-dominated natural reserves on a large spatial scale - Leilei Yang; Junhui Zhang; Jiahui Wang; Yue Gu; Shijie Han (Forest Ecology and Management, 2023)

Identification of pancreatic lipase inhibitors from Eucommia ulmoides tea by affinity-ultrafiltration combined UPLC-Orbitrap MS and in vitro validation - Han Huang; Ming-Hao Han; Qi Gu; Jian-Dong Wang; Heng Zhao; Bo-Wen Zhai; Si-Ming Nie; Zhi-Guo Liu; Yu-Jie Fu (Food Chemistry, 2023)

Effect and mechanism of a concentration-dependent inorganic ion biomimetic periosteum in a repairing bone defect - Lichen Zhang; Jincheng Tang; Meng Han; Yang Sun; Wei Wang; Zhuojun Wu; Yachao Sheng; Kun Xi; Yong Gu; Liang Chen (Chemical Engineering Journal, 2023)

Soil potassium regulation by initial K level and acidification degree when subjected to liming: A meta-analysis and long-term field experiment - Tianfu Han; Dongchu Li; Kailou Liu; Jing Huang; Lu Zhang; Shujun Liu; Asad Shah; Lisheng Liu; Gu Feng; Huimin Zhang (CATENA, 2023)

Regulation of microbial metabolism on the formation of characteristic flavor and quality formation in the traditional fish sauce during fermentation: a review - Jiarun Han; Tao Kong; Qi Wang; Jialan Jiang; Qingqing Zhou; Ping Li; Beiwei Zhu; Qing Gu (Critical Reviews in Food Science and Nutrition, 2023)

Coastal sediment heavy metal(loid) pollution under multifaceted anthropogenic stress: Insights based on geochemical baselines and source-related risks - Zexing Kuang; Huijuan Wang; Beibei Han; Yiyong Rao; Haixing Gong; Wanru Zhang; Yangguang Gu; Zhengqiu Fan; Shoubing Wang; Honghui Huang (Chemosphere, 2023)

Towards effective recovery of humate as green fertilizer from landfill leachate concentrate by electro-neutral nanofiltration membrane - Wenyuan Ye; Mingqiu Hong; Xuan Huang; Tianci Chen; Ailiang Gu; Xiaocheng Lin; Xuewei Li; Xiangrong Chen; Dong Han Seo; Shuaifei Zhao; Xueming Chen; Bart Van der Bruggen; et al. (Science of The Total Environment, 2023)

Research on the low carbon development path of China's coal industry under carbon peaking & carbon neutral target: Based on the RCPs-SSPs framework - Yujie Wang; Qingqing Sun; Jingjun Wu; Shuai Han; Ruonan Zhang; Shiyan Jiang; Xiao Gu (Resources Policy, 2023)

Lake sediment DNA reveals the response of phytoplankton to warming - Dongna Yan; Bashir Bolaji Tiamiyu; Jinzhao Liu; Jianghu Lan; Hai Xu; Weiguo Hou; Hanfeng Wen; Maolin Gu; Hong Yan; Zhihai Tan; Zhisheng An; Yongming Han (Quaternary Science Reviews, 2023)

Molecular networking-assisted isolation of chlorophenolic glycosides from the rhizomes of Curculigo orchioides and their inhibitory effect on α-glucosidase - Jun Gu Kim; Thi Phuong Linh Le; Jae Sang Han; Yong Beom Cho; Dongho Lee; Mi Kyeong Lee; Bang Yeon Hwang (Phytochemistry, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Burial or mineralization: Origins and fates of organic matter in the water–suspended particulate matter–sediment of macrophyte- and algae-dominated areas in Lake Taihu - Cheng Liu; Qiushi Shen; Xiaozhi Gu; Lei Zhang; Chao Han; Zhaode Wang (Water Research, 2023)

Closed-loop recycling of spent lithium-ion batteries based on selective sulfidation: An unconventional approach - Kunhong Gu; Xuesong Gao; Yuxin Chen; Wenqing Qin; Junwei Han (Waste Management, 2023)

PbrWRKY70 increases pear (Pyrus bretschneideri Rehd) black spot disease tolerance by negatively regulating ethylene synthesis via PbrERF1B-2 - Caihua Xing; Qiming Chen; Qinghai Qiao; Shenao Gu; Xiangyu Cheng; Huizhen Dong; Likun Lin; Feng Zhang; Chenyang Han; Zan Zhang; Hao Yin; Kaijie Qi; et al. (Plant Science, 2023)

The glacier melting process is an invisible barrier to the development of Antarctic subtidal macroalgal assemblages - Young Wook Ko; Dong Seok Lee; Jeong Ha Kim; Sun-Yong Ha; Sanghee Kim; Han-Gu Choi (Environmental Research, 2023)

Experimental study on the morphodynamic evolution of sandbar-lagoon system with emergent vegetation - Xin Cong; Cuiping Kuang; Guangwei Huang; Qingping Zou; Xuejian Han; Chao Shen; Jie Gu (Coastal Engineering, 2023)

Enhancing wheat Fusarium head blight detection using rotation Yolo wheat detection network and simple spatial attention network - Dong-Yan Zhang; Han-Sen Luo; Tao Cheng; Wei-Feng Li; Xin-Gen Zhou; Wei-Guo; Chun-Yan Gu; Zhihua Diao (Computers and Electronics in Agriculture, 2023)

Comparative analysis of volatile compounds and microbial community succession in Chinese fish sauce: Three typical types of fast-fermented fish sauces - Jiarun Han; Jialan Jiang; Tao Kong; Xilian Zhao; Xin Zhao; Ping Li; Qing Gu (Food Bioscience, 2023)

Mitigation of benzoic acid-driven autotoxicity in waste nutrient solution using O3 and O3/H2O2 treatments: Seed germination and root growth of Lactuca sativa L. - Uijeong Han; Yong-Gu Lee; Jihui Byeon; Kangmin Chon; Si-Kyung Cho (Environmental Pollution, 2023)

A bifunctional single-atom catalyst assisted by Fe2O3 for efficiently electrocatalytic perfluorooctanoic acid degradation by integrating reductive and oxidative processes - Jianyu Han; Mingxuan Zhao; Kaiqing Wu; Yixin Hong; Tianyi Huang; Xiaofei Gu; Zhi Wang; Songqin Liu; Guangcan Zhu (Chemical Engineering Journal, 2023)

Impact of Cold Spells on Ischemic Stroke Severity and Clinical Outcomes in Tianjin, China - Juanjuan Xue; Chanjuan Wei; Xiaoshuang Xia; Xuemei Qi; Yumeng Gu; Zhongyan Wang; Suqin Han; Lin Wang; Xin Li (Journal of Meteorological Research, 2023)

Levoglucosan and its isomers in terrestrial sediment as a molecular markers provide direct evidence for the low-temperature fire during the mid-Holocene in the northern Shandong Peninsula of China - Zhihai Tan; Yubo Yuan; Maolin Gu; Yongming Han; Longjiang Mao; Tantan Tan; Chuang Wu; Tong Han (Quaternary International, 2023)

Barium isotope behavior during interaction between serpentinite-derived fluids and metamorphic rocks in the continental subduction zone - Anxia Chen; Yi-Xiang Chen; Xiaofeng Gu; Zhen Zeng; Zicong Xiao; Hans-Peter Schertl; Xiqiu Han; Zi-Fu Zhao; Fang Huang (Geochimica et Cosmochimica Acta, 2023)

Network prediction of surgical complication clusters: a prospective multicenter cohort study - Xiaochu Yu; Peng Wu; Zixing Wang; Wei Han; Yuguang Huang; Shijie Xin; Qiang Zhang; Shengxiu Zhao; Hong Sun; Guanghua Lei; Taiping Zhang; Luwen Zhang; et al. (Science China Life Sciences, 2023)

Life stage affects prey use with fitness consequences in a zoophytophagous mirid bug - Ruo-han Ma; Jia-min Gu; Coline C. Jaworski; Zheng-xuan Xue; Xue-ling Li; Pei-ling Wang; Peng Han; Nicolas Desneux (Phytoparasitica, 2023)

Stimulating carbon and nitrogen metabolism of Chlorella pyrenoidosa to treat aquaculture wastewater and produce high-quality protein in plate photobioreactors - Jia Wang; Yuxin Wang; Ziqiang Gu; Haijin Mou; Han Sun (Science of The Total Environment, 2023)

Stevia extract enhances the fermentation and functional properties of fermented milk in human colon epithelial cells - Do Hyun Kim; Chang Hee Jeong; Seo Gu Han; Hyun Su Jung; Sung Gu Han (Food Bioscience, 2023)

Structure and Evolution of Clay-Organic Nanocomposites in Three Leading Shales in China - Yuantao Gu; Quan Wan; Xiaoxia Li; Tao Han; Shuguang Yang; Qinhong Hu (Journal of Earth Science, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

Pentacyclic triterpenoids from spikes of Prunella vulgaris L. with thyroid tumour cell cytostatic bioactivities - Xiu-Qin Zheng; Lei-Xin Song; Zhu-Zhen Han; Ying-Bo Yang; Yi Zhang; Li-Hua Gu; Li Yang; Gui-Xin Chou; Zheng-Tao Wang (Natural Product Research, 2023)

Iron oxides act as an alternative electron acceptor for aerobic methanotrophs in anoxic lake sediments - Biao Li; Ye Tao; Zhendu Mao; Qiujin Gu; Yixuan Han; Baolan Hu; Hongwei Wang; Anxing Lai; Peng Xing; Qinglong L Wu (Water Research, 2023)

The derivation of soil generic assessment criteria for polychlorinated biphenyls under the agricultural land scenario in Pearl and Yangtze River Delta regions, China - Lu Han; Wenpei Wu; Xueyan Chen; Mingyue Gu; Jing Li; Mengfang Chen; Youya Zhou (Science of The Total Environment, 2023)

Thermal gelation and digestion properties of hen egg white: Study on the effect of neutral and alkaline salts addition - Junhua Li; Weijian Zhang; Tingting Tang; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Food Chemistry, 2023)

Europium doped RuO2@TP enhanced chlorine evolution reaction performance by charge redistribution - Lingshu Qiu; Fan Zhang; Yang Qian; Weiwei Han; Yi He; Xiangdong Feng; Jianxin Jin; Yongping Gu; Shaoyun Hao; Xingwang Zhang (Chemical Engineering Journal, 2023)

Bacterial cellulose-based hydrogel with antibacterial activity and vascularization for wound healing - Lili Deng; Yinjun Huang; Shiyan Chen; Zhiliang Han; Zhengzhe Han; Mengtian Jin; Xiangyang Qu; Baoxiu Wang; Huaping Wang; Song Gu (Carbohydrate Polymers, 2023)

Galectin-3-centered paracrine network mediates cardiac inflammation and fibrosis upon β-adrenergic insult - Guomin Hu; Jimin Wu; Huijun Gu; Xiangning Deng; Wenli Xu; Shan Feng; Shuaixing Wang; Yao Song; Zhengda Pang; Xiuling Deng; Aleksandr E. Vendrov; Nageswara R. Madamanchi; et al. (Science China Life Sciences, 2023)

Mono-/multiadsorption of chlorobenzene compounds on biochar: influence of the properties of the chlorobenzene molecules and biochar - Lifei Yang; Wenjia Han; Wei Zhao; Chenggang Gu; Zhihong Xu; Xin Jiang (Journal of Soils and Sediments, 2023)

Deciphering Functional Connectivity Differences Between Motor Imagery and Execution of Target-Oriented Grasping - Eunkyung Kim; Woo Hyung Lee; Han Gil Seo; Hyung Seok Nam; Yoon Jae Kim; Min-Gu Kang; Moon Suk Bang; Sungwan Kim; Byung-Mo Oh (Brain Topography, 2023)

The status of the global food waste mitigation policies: experience and inspiration for China - Guohui Shen; Ziqi Li; Tiannuo Hong; Xin Ru; Kunzhen Wang; Yanting Gu; Juan Han; Yanzhi Guo (Environment, Development and Sustainability, 2023)
Food waste has become a significant challenge faced by the community with a shared future for mankind, and it has also caused a considerable impact on China's food security. Scholars across disciplines, international organizations, and especially policymakers are increasingly interested in food waste. Policies are seen as a powerful factor in reducing food waste, but current research on related policies is more scattered. This paper summarizes and analyzes the experiences of food waste policy development and implementation by systematically reviewing the studies on food waste reduction policies. The results of this paper's analysis show that current global food waste policies are focused at the national strategic level, with approaches such as legislation, food donation, waste recycling, awareness and education, and data collection. At the same time, we find that the current experience of developed countries in policy formulation and implementation is beneficial for policy formulation in developing countries. And taking China as an example, we believe that developing countries can improve food waste policies in the future by improving legislation, guiding the development of food banks, promoting social governance, and strengthening scientific research projects. These policies will all contribute strongly to global environmental friendliness. In addition, we discuss some of the factors that influence the development of food waste policies and argue that in the future, more consideration needs to be given to the effects of policy implementation and that case studies should focus more on developing countries. This will contribute to the global sustainable development process.

Proactive control model for safety prediction in tailing dam management: Applying graph depth learning optimization - Shunling Ruan; Simiao Han; CaiWu Lu; Qinghua Gu (Process Safety and Environmental Protection, 2023)

Measurement and control of containing-fluorine particulate matter emission during spent pot lining combustion detoxification process - Funian Han; Liang Yu; Xinyun Mo; Lu Zhang; Jiaqi Jia; Jingmeng Dong; Shaopeng Gu (Journal of Hazardous Materials, 2023)

Foaming properties of dried egg white at different outlet temperatures - Junhua Li; Jinjing Sun; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Journal of Food Engineering, 2023)

Indoor air particles in research vessel from Shanghai to Antarctic: Characteristics, influencing factors, and potential controlling pathway - Xudong Wu; Fange Yue; Jiancheng Wang; Xiawei Yu; Hongwei Liu; Weihua Gu; Mingming Han; Juan Li; Zhouqing Xie (Journal of Environmental Sciences, 2023)

Spatial distribution, contamination characteristics and ecological-health risk assessment of toxic heavy metals in soils near a smelting area - Han Gui; Qingchun Yang; Xingyu Lu; Hualin Wang; Qingbao Gu; Jordi Delgado Martín (Environmental Research, 2023)

Matthew effect photoimmunotheranostics enabled by proton-driven nanoconverter - Jingjing Wang; Wei Zhang; Dachong Gu; Chunmei Chen; Wei Tang; Yi Ouyang; Xiaohong Liu; Shi-Yu Lu; Wei Zhang; Xingcai Zhang; Yulong Han; Jie Hu; et al. (Chemical Engineering Journal, 2023)

Removal of nitrate nitrogen from wastewater by green synthetic hydrophilic activated carbon supported sulfide modified nanoscale zerovalent Iron: Characterization, performance and mechanism - Shuaibing Fang; Jingxi Zhang; Yifan Niu; Shaohua Ju; Yongwan Gu; Kai Han; Xiaoxi Wan; Na Li; Yu Zhou (Chemical Engineering Journal, 2023)

Profiles and key drivers of bacteria/phage co-mediated antibiotic resistance genes during swine manure composting amended with humic acid - Meiling Shi; Zixuan Zhao; Xiaojuan Wang; Huakang Li; Jie Gu; Zilin Song; Ting Hu; Yifan Sun; Han Wang (Bioresource Technology, 2023)

Unanswered questions on the airborne transmission of COVID-19 - Zhaolin Gu; Jie Han; Liyuan Zhang; Hongliang Wang; Xilian Luo; Xiangzhao Meng; Yue Zhang; Xinyi Niu; Yang Lan; Shaowei Wu; Junji Cao; Eric Lichtfouse (Environmental Chemistry Letters, 2023)

Effect of PVC microplastics on soil microbial community and nitrogen availability under laboratory-controlled and field-relevant temperatures - Hangru Shen; Yuhan Sun; Hongbing Duan; Jinliu Ye; Aoyu Zhou; Han Meng; Fengxiao Zhu; Huan He; Cheng Gu (Applied Soil Ecology, 2023)

The rapid shift of intertidal macroalgal assemblage from vertical shoreline profiles in Barton Peninsula, King George Island, Antarctica during summer - Young Wook Ko; Dong Seok Lee; Sanghee Kim; Jeong Ha Kim; Han-Gu Choi (Polar Science, 2023)

Electrochemical oxidation of bio-treated landfill leachate using a novel dynamic reactive electrochemical membrane (DREM) - Xu Yin; Wei Li; Hongwei Zhu; Jie Zhang; Liankai Gu; Kajia Wei; Zhanping Gao; Laisong Zhu; Weiqing Han (Journal of Hazardous Materials, 2023)

Significant roles of surface functional groups and Fe/Co redox reactions on peroxymonosulfate activation by hydrochar-supported cobalt ferrite for simultaneous degradation of monochlorobenzene and p-chloroaniline - Lei Yang; Zifei Wei; Zihan Guo; Mengfang Chen; Jingchun Yan; Linbo Qian; Lu Han; Jing Li; Mingyue Gu (Journal of Hazardous Materials, 2023)

Experimental study on the redistribution law of heavy metals in sludge disintegration - Juanjuan Zhao; Feng Deng; Han Zhang; Wenwen Gu; Huidan Chen; Siqi Huang (Journal of Environmental Management, 2023)

Synergistic effect of F and triggered oxygen vacancies over F-TiO2 on enhancing NO ozonation - Lina Guo; Xu Zhang; Fanyu Meng; Jing Yuan; Yiqing Zeng; Chenyang Han; Yong Jia; Mingyan Gu; Shule Zhang; Qin Zhong (Journal of Environmental Sciences, 2023)

Altering autotrophic carbon metabolism of Nitzschia closterium to mixotrophic mode for high-value product improvement - Yuxin Wang; Jia Wang; Ziqiang Gu; Shufang Yang; Yongjin He; Haijin Mou; Han Sun (Bioresource Technology, 2023)

Excavation Stress Path Induced Fracturing Mechanism of Hard Rock in Deep Tunnel - Liangjie Gu; Xia-Ting Feng; Rui Kong; Chengxiang Yang; Qiang Han; Yuelin Xia (Rock Mechanics and Rock Engineering, 2023)

Predicting the Height of the Water-Conducting Fractured Zone in Fully Mechanized Top Coal Caving Longwall Mining of Very Thick Jurassic Coal Seams in Western China Based on the NNBR Model - Yanbo Han; Qiqing Wang; Wenping Li; Zhi Yang; Tianyu Gu; Zhenkang Wang (Mine Water and the Environment, 2023)

Growth and clearance rate of Corbicula fluminea in relation to fine sediment resuspension in eutrophic shallow lakes - You Zhang; Long Cheng; Wei Li; Yanqing Han; Jiao Gu; Kuanyi Li; Erik Jeppesen (Hydrobiologia, 2023)

Hydrodynamic constraint loads estimation on connectors of column-pontoon type very large floating structure (CP-VLFS) under wave stimulation - Linjian Wu; Han Jiang; Xudong Ji; Xueli Ju; Zhouyu Xiang; Mingjie Gu (Frontiers in Marine Science, 2023)
Column-pontoon type very large floating structure (CP-VLFS) operated at the deep and sea faraway areas are generally exposed to the extremely complex wave conditions. The connectors of CP-VLFS are generally subjected to complicated hydrodynamic constraint loads when the modules of CP-VLFS are stimulated by the long-tern wave forces. The general method for analyzing the hydrodynamic performances for marine floating structures and their components is almost on the basis of potential flow/fluid theory (PFT), but its algorithm principle is relatively complex and would consume plenty of computing time. During the preliminary design and scheme comparison stages for CP-VLFSs, the hydrodynamic results for CP-VLFSs’ modules and their connectors required to be rapidly determined. Hence, a rapid and high-efficiency estimating method for time-domain hydrodynamic constraint loads of connectors on CP-VLFS considering the mathematical and mechanical model of rigid module and flexible connector (RMFC) is developed via this paper. During this estimation method, the Morison theory of floating body is employed to assess the hydrodynamic excitation forces by random and irregular wave (RIW) on CP-VLFS structures, and a series of concise formulas for estimating the hydrodynamic constraint loads of CP-VLFS connectors are derived based on the geometrical relationship of the CP-VLFS modules’ motion. For this paper’s explorations, a three-module CP-VLFS model is considered as a case, and the time-domain hydrodynamic constraint loads of CP-VLFS’s connectors are determined under the RIW stimulations with different wave angles. Hydrodynamic constraint loads of CP-VLFS connectors estimated by this paper agree well with the results of PFT and those of physical experiment, validation the methodologies developed by this paper. Some useful conclusions may provide significant technical supports for hydrodynamic characteristics of CP-VLFS modules and their connectors optimization.

Autophagy and polyphenol intervention strategy in aging - Yanpei Gu; Jianzhong Han (Trends in Food Science & Technology, 2023)

A V2G-oriented reinforcement learning framework and empirical study for heterogeneous electric vehicle charging management - Xu Hao; Yue Chen; Hewu Wang; Han Wang; Yu Meng; Qing Gu (Sustainable Cities and Society, 2023)

Metagenomics analysis reveals potential pathways and drivers of piglet gut phage-mediated transfer of ARGs - Yalu Ji; Hengyu Xi; Zhen Zhao; Qiujie Jiang; Chong Chen; Xinwu Wang; Fengyang Li; Na Li; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; et al. (Science of The Total Environment, 2023)

Preferred prey reduce species realized niche shift and improve range expansion prediction - Lixia Han; Zhixin Zhang; Weishan Tu; Qing Zhang; Yanhua Hong; Shengnan Chen; Zhiqiang Lin; Shimin Gu; Yuanbao Du; Zhengjun Wu; Xuan Liu (Science of The Total Environment, 2023)

Simultaneous alleviation of Cd availability in contaminated soil and accumulation in rice (Oryza sativa L.) by Fe-Mn oxide-modified biochar - Wen-Tao Tan; Hang Zhou; Shang-Feng Tang; Qiong Chen; Xia Zhou; Xin-Hui Liu; Peng Zeng; Jiao-Feng Gu; Bo-Han Liao (Science of The Total Environment, 2023)

Elucidation of microbial interactions, dynamics, and keystone microbes in high pressure anaerobic digestion - Ajay Thapa; Jeong-Hoon Park; Seung Gu Shin; Hong-Mok Jo; Min-Sang Kim; Yeongmi Park; Uijeong Han; Si-Kyung Cho (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Targeted isolation of sesquiterpene lactone dimers from Aucklandia lappa guided by LC-HRMS/MS-based molecular networking - Jae Sang Han; Jun Gu Kim; Thi Phuong Linh Le; Yong Beom Cho; Dongho Lee; Jin Tae Hong; Mi Kyeong Lee; Bang Yeon Hwang (Phytochemistry, 2023)

Effect of Tribute citrus essential oil nanoemulsion-loaded gelatin on the gel behavior and gelation surface morphologies - Guoqiang Li; Qingqing Zhou; Shuxun Liu; Cheng Qian; Jiarun Han; Tao Zhou; Ping Li; Qing Gu (Food Bioscience, 2023)

Comprehensive study of energy and water exchange over the Tibetan Plateau: A review and perspective: From GAME/Tibet and CAMP/Tibet to TORP, TPEORP, and TPEITORP - Yaoming Ma; Tandong Yao; Lei Zhong; Binbin Wang; Xiangde Xu; Zeyong Hu; Weiqiang Ma; Fanglin Sun; Cunbo Han; Maoshan Li; Xuelong Chen; Jiemin Wang; et al. (Earth-Science Reviews, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Spatiotemporal Dynamics of the Molecular Expression Pattern and Intercellular Interactions in the Glial Scar Response to Spinal Cord Injury - Leilei Gong; Yun Gu; Xiaoxiao Han; Chengcheng Luan; Chang Liu; Xinghui Wang; Yufeng Sun; Mengru Zheng; Mengya Fang; Shuhai Yang; Lai Xu; Hualin Sun; et al. (Neuroscience Bulletin, 2023)
Nerve regeneration in adult mammalian spinal cord is poor because of the lack of intrinsic regeneration of neurons and extrinsic factors – the glial scar is triggered by injury and inhibits or promotes regeneration. Recent technological advances in spatial transcriptomics (ST) provide a unique opportunity to decipher most genes systematically throughout scar formation, which remains poorly understood. Here, we first constructed the tissue-wide gene expression patterns of mouse spinal cords over the course of scar formation using ST after spinal cord injury from 32 samples. Locally, we profiled gene expression gradients from the leading edge to the core of the scar areas to further understand the scar microenvironment, such as neurotransmitter disorders, activation of the pro-inflammatory response, neurotoxic saturated lipids, angiogenesis, obstructed axon extension, and extracellular structure re-organization. In addition, we described 21 cell transcriptional states during scar formation and delineated the origins, functional diversity, and possible trajectories of subpopulations of fibroblasts, glia, and immune cells. Specifically, we found some regulators in special cell types, such as Thbs1 and Col1a2 in macrophages, CD36 and Postn in fibroblasts, Plxnb2 and Nxpe3 in microglia, Clu in astrocytes, and CD74 in oligodendrocytes. Furthermore, salvianolic acid B, a blood–brain barrier permeation and CD36 inhibitor, was administered after surgery and found to remedy fibrosis. Subsequently, we described the extent of the scar boundary and profiled the bidirectional ligand-receptor interactions at the neighboring cluster boundary, contributing to maintain scar architecture during gliosis and fibrosis, and found that GPR37L1_PSAP, and GPR37_PSAP were the most significant gene-pairs among microglia, fibroblasts, and astrocytes. Last, we quantified the fraction of scar-resident cells and proposed four possible phases of scar formation: macrophage infiltration, proliferation and differentiation of scar-resident cells, scar emergence, and scar stationary. Together, these profiles delineated the spatial heterogeneity of the scar, confirmed the previous concepts about scar architecture, provided some new clues for scar formation, and served as a valuable resource for the treatment of central nervous system injury.

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Integrated electro-Fenton system based on embedded U-tube GDE for efficient degradation of ibuprofen - Kaiqiang Shi; Yi Wang; Anlin Xu; Hongwei Zhu; Liankai Gu; Xiaodong Liu; Jinyou Shen; Weiqing Han; Kajia Wei (Chemosphere, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Investigation of the relationship between MBP gene polymorphisms and delayed encephalopathy after acute carbon monoxide poisoning - Fan Zhang; Jiao Zeng; Xiaoli Zhang; Jiapeng Gu; Yongkai Han; Ping Zhang; Wenqiang Li; Renjun Gu (NeuroToxicology, 2023)

Suggestion on further strengthening ultra-low emission standards for PM emission from coal-fired power plants in China - Jianguo Deng; Shumin Wang; Jiawei Zhang; Yi Zhang; Jingkun Jiang; Yongzheng Gu; Tao Han; Lei Feng; Jian Gao; Lei Duan (Journal of Environmental Sciences, 2023)

ε-Poly( -lysine)-based bioreducible nanogels for mitochondria-targeted delivery and release: Hydrophobicity-tuned nucleus-to-mitochondria organelle-targeting switch and slow disulfide cleavage - Hana Cho; Yeon Su Choi; Da Gyeom Choung; Won Gu Choi; Min Seo Lee; Yong-Yeon Cho; Joo Young Lee; Hye Suk Lee; Han Chang Kang (Chemical Engineering Journal, 2023)

Superwettable Surface-Dependent efficiently electrocatalytic water splitting based on their excellent liquid adsorption and gas desorption - Fei Zhang; Ran Zhao; Yiran Wang; Lu Han; Jianmin Gu; Zhimin Niu; Yiming Yuan; Nianrui Qu; Jingxin Meng; Desong Wang (Chemical Engineering Journal, 2023)

Enhanced cellulosic d-lactic acid production from sugarcane bagasse by pre-fermentation of water-soluble carbohydrates before acid pretreatment - Zhongyang Qiu; Xushen Han; Anqing Fu; Yalan Jiang; Wenyue Zhang; Ci Jin; Dengchao Li; Jun Xia; Jianlong He; Yuanfang Deng; Ning Xu; Xiaoyan Liu; et al. (Bioresource Technology, 2023)

Coassisted carbonization with HCOOK/(HCOO)2Ca for the fabrication of bamboo-derived oxygen-doped porous carbons exhibiting high-performance sorption of diethyl phthalate from aqueous solutions - Fei Gu; Rongting Ji; Qian Sun; Shengcun Chen; Rong Bai; Yuying Shen; Xinran Liu; Yang Song; Jiangang Han; Xin Jiang; Hu Cheng; Jianming Xue (Bioresource Technology, 2023)

Association between placental DNA methylation and fetal congenital heart disease - Jingjing Liu; Yuduo Wu; Hairui Sun; Xiaowei Liu; Xiaoyan Gu; Ye Zhang; Ying Zhao; Jiancheng Han; Yihua He (Molecular Genetics and Genomics, 2023)

Evaluation of the Effectiveness of Marking Juvenile Takifugu obscurus Otoliths with Strontium - Lingling Gu; Hui Zhang; Guangpeng Feng; Yong Liu; Zhiqiang Han; Feng Zhao; Qing Ye; Wangjiao Hu; Chao Song (Fishes, 2022)
Strontium marking technology is commonly used for extensive marking in stock enhancement and releasing activities. In order to explore the feasibility of this technology for juvenile Takifugu obscurus, five different concentrations of strontium (0, 12, 18, 36, and 72 mg/L) were set up by strontium chloride hexahydrate (SrCl2·6H2O) and T. obscurus were immersed for 7 days. Then, T. obscurus were reared in non-additive water for 25 days. The results showed that the survival rate of all groups was 100%, except the 72 mg/L group, after 7 days of immersion. Moreover, the growths of all the marked groups were better than that of the control group. There was no significant difference between the control and marked groups, except for the 18 mg/L group, indicating that the appropriate concentration of strontium might have positive effect for T. obscurus. The strontium to calcium (Sr/Ca) ratios of otoliths in the marked groups increased with increasing concentration and time, which were higher than the baseline, respectively. Then, the Sr/Ca ratios returned to the original level, but the peak value was still retained, suggesting that the success rate of the strontium marking reached 100%. Notably, the residual strontium content of 18 mg/L group was insufficient for causing negative effects for T. obscurus after 25 days. Therefore, in consideration of the growth, survival, and effect of strontium marking on otolith, 18 mg/L is an appropriate concentration for strontium marking of juvenile T. obscurus. This study confirmed the feasibility of strontium marking for T. obscurus and provided a new approach to rationally and scientifically evaluate the stock enhancement and releasing efficiency of T. obscurus.

Clinical features and epidemiology of severe fever with thrombocytopenia syndrome in dogs in the Republic of Korea: an observational study (2019–2020) - Sun-Woo Han; Ye-In Oh; Ji-Min Rim; Yoon-Kyoung Cho; Dong-Hoo Kim; Jun-Gu Kang; Kyoung-Seong Choi; Joon-Seok Chae (Veterinary Research Communications, 2022)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Fenpropathrin exposure induces neurotoxicity in zebrafish embryos - Tingting Yu; Xiaowen Xu; Huiling Mao; Xue Han; Yulong Liu; Hongying Zhang; Jingli Lai; Jianfeng Gu; Mengling Xia; Chengyu Hu; Dongming Li (Fish Physiology and Biochemistry, 2022)

Evaluation on the applicability of ERA5 reanalysis dataset to tropical cyclones affecting Shanghai - Zhihui Han; Caijun Yue; Changhai Liu; Wen Gu; Yuqi Tang; Yongyu Li (Frontiers of Earth Science, 2022)

Mercury removal from flue gas by a MoS2/H2O heterogeneous system based on its absorption kinetics - Yongpeng Ma; Jiandong Wang; Xiaojing Zhang; Wentao Gu; Lifeng Han; Yakun Li (Environmental Science and Pollution Research, 2022)

Novel Deep Eutectic Solvent–Hydrogel Systems for Synergistic Transdermal Delivery of Chinese Herb Medicine and Local Treatments for Rheumatoid Arthritis - Suyun Xiao; Liyun Wang; Wei Han; Liyun Gu; Xiuming Cui; Chengxiao Wang (Pharmaceutical Research, 2022)

A review for recent advances on soil washing remediation technologies - Fei Gu; Jiapeng Zhang; Ziqi Shen; Yang Li; Rongting Ji; Wei Li; Longjiang Zhang; Jiangang Han; Jianming Xue; Hu Cheng (Bulletin of Environmental Contamination and Toxicology, 2022)

Fine mapping and candidate gene analysis of gummy stem blight resistance in cucumber stem - Jianan Han; Shaoyun Dong; Yanxia Shi; Han Miao; Xiaoping Liu; Diane M. Beckles; Xingfang Gu; Shengping Zhang (Theoretical and Applied Genetics, 2022)

Rapid changes in coastal ocean microbiomes uncoupled with shifts in environmental variables - Jessica L. Gronniger; Zhao Wang; Genevieve R. Brandt; Christopher S. Ward; Despina Tsementzi; Han Mu; Junyao Gu; Zackary I. Johnson; Konstantinos T. Konstantinidis; Dana E. Hunt (Environmental Microbiology, 2022)
Summary Disturbances, here defined as events that directly alter microbial community composition, are commonly studied in host‐associated and engineered systems. In spite of global change both altering environmental averages and increasing extreme events, there has been relatively little research into the causes, persistence and population‐level impacts of disturbance in the dynamic coastal ocean. Here, we utilize 3 years of observations from a coastal time series to identify disturbances based on the largest week‐over‐week changes in the microbiome (i.e. identifying disturbance as events that alter the community composition). In general, these microbiome disturbances were not clearly linked to specific environmental factors and responsive taxa largely differed, aside from SAR11, which generally declined. However, several disturbance metagenomes identified increased phage‐associated genes, suggesting that unexplained community shifts might be caused by increased mortality. Furthermore, a category 1 hurricane, the only event that would likely be classified a priori as an environmental disturbance, was not an outlier in microbiome composition, but did enhance a bloom in seasonally abundant phytoplankton. Thus, as extreme environmental changes intensify, assumptions of what constitutes a disturbance should be re‐examined in the context of ecological history and microbiome responses.

Identification of novel biofilm genes in avian pathogenic Escherichia coli by Tn5 transposon mutant library - Jiangang Hu; Yi Gu; Huiqi Lu; Muhammad Akmal Raheem; Fangheng Yu; Xiangpeng Niu; Jiakun Zuo; Huifang Yin; Cuiqin Huang; Xiangjun Song; Jian Tu; Wen Zhou; et al. (World Journal of Microbiology and Biotechnology, 2022)

The qLTG1.1 candidate gene CsGAI regulates low temperature seed germination in cucumber - Caixia Li; Shaoyun Dong; Diane M. Beckles; Han Miao; Jiaqiang Sun; Xiaoping Liu; Weiping Wang; Shengping Zhang; Xingfang Gu (Theoretical and Applied Genetics, 2022)

A short review of probabilistic slope stability analysis considering spatial variability of geomaterial parameters - Wengang Zhang; Xin Gu; Liang Han; Jiahao Wu; Zhiwei Xiao; Maoyi Liu; Lin Wang (Innovative Infrastructure Solutions, 2022)

Comprehensive analysis of a paleo-landslide damming event on the upper reach of the Jinsha River, SE Tibetan Plateau - Yuchao Li; Jianping Chen; Zhihai Li; Xudong Han; Shijie Zhai; Yongchao Li; Yiwei Zhang; Feifan Gu (Bulletin of Engineering Geology and the Environment, 2022)

Transcriptome Profiling of Duodenum Reveals the Importance of Boron Supplementation in Modulating Immune Activities in Rats - Chunfang Zhao; Yujiao Han; Chenfang Wang; Man Ren; Qianqian Hu; Youfang Gu; Pengfei Ye; Shenghe Li; Erhui Jin (Biological Trace Element Research, 2022)

Comparative analysis of the structure and function of rhizosphere microbiome of the Chinese medicinal herb Alisma in different regions - Chenbin Wei; Wei Gu; Rong Tian; Fei Xu; Yun Han; Yuanyuan Ji; Tao Li; Yu Zhu; Peilei Lang; Wenqing Wu (Archives of Microbiology, 2022)

Statistical optimization of phytol and polyunsaturated fatty acid production in the Antarctic microalga Micractinium variabile KSF0031 - Eun Jae Kim; Hyunsik Chae; Man Hyung Koo; Jihyeon Yu; Hyunjoong Kim; Sung Mi Cho; Kwang Won Hong; Joo Young Lee; Ui Joung Youn; Sanghee Kim; Han-Gu Choi; Se Jong Han (Algae, 2022)
Polar microorganisms produce physiologically active substances to adapt to harsh environments, and these substances can be used as biomedical compounds. The green microalga Micractinium variabile KSF0031, which was isolated from Antarctica, produced phytol, a natural antimicrobial agent. Furthermore, several polyunsaturated fatty acids (PUFAs), including omega-3, exhibit antioxidant properties. Here statistical methods (Plackett-Burman design and Box- Behnken design) were used to optimize the culture medium of KSF0031 to improve biomass production, and K2HPO4, MgSO4·7H2O, and ammonium ferric citrate green (AFCg) were selected as significant components of the culture medium. Changes in the concentration of K2HPO4 and MgSO4·7H2O as positive factors and AFCg as a negative factor affected cell growth to a remarkable degree. The biomass production in a 100 L culture using the optimized medium for 24 d at 18°C was improved by 37.5% compared to that obtained using the original BG-11 medium. The quantities of PUFAs and phytol obtained were 13 mg g-1 dry cell weight (DCW) and 10.98 mg g-1 DCW, which represent improved yields of 11.70% and 48.78%, respectively. The results of this study could contribute to an improved production of phytol and fatty acids from Antarctic microalgae in the biomedical industry.

Genetic variants in choline metabolism pathway are associated with the risk of bladder cancer in the Chinese population - Zhichao Han; Jingjing Gu; Junyi Xin; Hanting Liu; Yanling Wu; Mulong Du; Haiyan Chu; Yadong Liu; Zhengdong Zhang (Archives of Toxicology, 2022)

Emergence of a novel reassortant avian influenza virus (H10N3) in Eastern China with high pathogenicity and respiratory droplet transmissibility to mammals - Kaituo Liu; Pingyun Ding; Yuru Pei; Ruyi Gao; Wenwen Han; Huafen Zheng; Zhuxing Ji; Miao Cai; Jinyuan Gu; Xiuli Li; Min Gu; Jiao Hu; et al. (Science China Life Sciences, 2022)

TREM2 and CD163 Ameliorate Microglia-Mediated Inflammatory Environment in the Aging Brain - Xue Han; Yu-Jia Liu; Bin-Wen Liu; Zheng-Liang Ma; Tian-Jiao Xia; Xiao-Ping Gu (Journal of Molecular Neuroscience, 2022)

Probabilistic stability analysis of embankment slopes considering the spatial variability of soil properties and seismic randomness - Wen-gang Zhang; Jia-hao Wu; Xin Gu; Liang Han; Lin Wang (Journal of Mountain Science, 2022)

Ziprasidone suppresses pancreatic adenocarcinoma cell proliferation by targeting GOT1 to trigger glutamine metabolism reprogramming - Yueying Yang; Mengzhu Zheng; Fei Han; Lei Shang; Mingxue Li; Xiaoxia Gu; Hua Li; Lixia Chen (Journal of Molecular Medicine, 2022)

Application of exogenous glycinebetaine alleviates lead toxicity in pakchoi (Brassica chinensis L.) by promoting antioxidant enzymes and suppressing Pb accumulation - Yu Ji; Yanfang Ren; Chuan Han; Wenjia Zhu; jinyu Gu; Junyu He (Environmental Science and Pollution Research, 2022)

Novel blood-based hypomethylation of SH3BP5 is associated with very early-stage lung adenocarcinoma - Rong Qiao; Runbo Zhong; Chunlan Liu; Feifei Di; Zheng Zhang; Ling Wang; Tian Xu; Yue Wang; Liping Dai; Wanjian Gu; Baohui Han; Rongxi Yang (Genes & Genomics, 2022)

Baroclinic Effect on Inner-Port Circulation in a Macro-Tidal Estuary: A Case Study of Incheon North Port, Korea - Jae-Soon Jeong; Seung-Buhm Woo; Han Soo Lee; Bon-Ho Gu; Jong Wook Kim; Jin Il Song (Journal of Marine Science and Engineering, 2022)
This study investigated the flow patterns and affecting factors in the North Port of Incheon, South Korea, to understand the inner-port circulation characteristics by applying an unstructured grid finite volume community ocean model (FVCOM) together with a field survey. The FVCOM considered the tide, river discharge, surface winds, and atmospheric pressure with the highest resolution of 50 m around the port. The model results were validated with current velocity and salinity observations. In the main channel, the difference in salinity between the sea surface and bottom increased during the neap tide due to weakened tidal currents, thus strengthening the stratification. However, at the inner port, strong stratification was observed during spring tide as the near-surface freshwater from upstream of the estuary moved relatively farther south of the port than that during the neap tide. Freshwater flowed into the port during the flood current and was trapped in the semi-closed geometry of the inner port. The horizontal salinity gradient between the trapped fresher water in the port and saltier water in the main channel increased during the flood current. As a result, density-driven circulations associated with near-bed currents towards the port were maintained for more than 3 h after high tide. This result implies that the baroclinic effect, mainly due to the salinity gradient in the North Port, could significantly affect residual circulation at the inner harbor in a macro-tidal environment and the mass transport mechanism, such as sediment transport. In general, such enhanced baroclinic effects due to salinity and tides are not limited to the North Port and can have greater effects on inner-port circulation in other macro-tidal harbors that suffer from severe sedimentation problems.

Effects of anthropogenic activities on hydrochemical characteristics of ground water of Da’an irrigation area in Western of Jilin Province - Zhiqi Gu; Jianmin Bian; Juanjuan Wu; Dongmei Ruan; Yexiang Yu; Han Zhang (Environmental Science and Pollution Research, 2022)

Autophagy inhibitors alleviate Japanese encephalitis virus-induced cerebral inflammation in mice - Jinhua Zhang; Wei Han; Changqing Xie; Mingxing Gao; Xugang Wang; Xueying Hu; Wanpo Zhang; Shengbo Cao; Xiaoli Liu; Guofu Cheng; Changqin Gu (Archives of Virology, 2022)

Failure mode of monopile foundation for offshore wind turbine in soft clay under complex loads - Song Dai; Bo Han; Guoxiang Huang; Xiaoqiang Gu; Liu Jian; Shiliang Liu (Marine Georesources & Geotechnology, 2022)

The adaptability of Phytophthora sojae to different types of soil determines the distribution of Phytophthora root rot of soybean in Heilongjiang Province of China - Haixu Liu; Han Yu; Zhuoqun Zhang; Xiangqi Bi; Zhiyue Yang; Yufei Chen; Xin Gu; Jingzhi Wen (European Journal of Plant Pathology, 2022)

A Standardized Protocol for the Induction of Specific Social Fear in Mice - Junqiang Zheng; Yuanyuan Tian; Haifeng Xu; Linfan Gu; Han Xu (Neuroscience Bulletin, 2021)

Sandstorms and desertification in Mongolia, an example of future climate events: a review - Jie Han; Han Dai; Zhaolin Gu (Environmental Chemistry Letters, 2021)

Spatial Distribution and Environmental Risk of Arsenic and Antimony in Soil Around an Antimony Smelter of Qinglong County - Yingping He; Zhiwei Han; Fuzhong Wu; Jia Xiong; Shangyi Gu; Pan Wu (Bulletin of Environmental Contamination and Toxicology, 2021)

Effect of lgals3a on embryo development of zebrafish - Kan Chen; Yuqi Fan; Jun Gu; Zhihua Han; Yue Wang; Lin Gao; Huasu Zeng; Chengyu Mao; Changqian Wang (Transgenic Research, 2021)

Erratum to: Settlement patterns of mountainous half-filled and half-cut widened subgrade with retaining wall - Yong-guo Fu; Xin Jiang; Han-yan Gu; Yan-jun Qiu (Journal of Mountain Science, 2021)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Red light enhances folate accumulation in wheat seedlings - Jianwei Chang; Chong Xie; Pei Wang; Zhenxin Gu; Yongbin Han; Runqiang Yang (Journal of Zhejiang University-SCIENCE B, 2021)

Dietary Supplementation of Bacillus sp. SJ-10 and Lactobacillus plantarum KCCM 11322 Combinations Enhance Growth and Cellular and Humoral Immunity in Olive Flounder (Paralichthys olivaceus) - Md Tawheed Hasan; Won Je Jang; Bong-Joo Lee; Sang Woo Hur; Sang Gu Lim; Kang Woong Kim; Hyon-Sob Han; Eun-Woo Lee; Sungchul C Bai; In-Soo Kong (Probiotics and Antimicrobial Proteins, 2021)

Defective Autophagy and Mitophagy in Alzheimer’s Disease: Mechanisms and Translational Implications - Jie Chen; Hai-Jun He; Qianqian Ye; Feifei Feng; Wen-Wen Wang; Yingying Gu; Ruiyu Han; Chenglong Xie (Molecular Neurobiology, 2021)

Near-field prediction of chemical hazard diffusion based on improved differential evolution algorithm and fireworks algorithm - Chaoshuai Han; Xuezheng Zhu; Jin Gu; Qinwen Zuo; Lin Chen; Yihao Shi (Environmental Monitoring and Assessment, 2021)

Diversity, abundance, and distribution of anammox bacteria in shipping channel sediment of Hong Kong by analysis of DNA and RNA - Xiaowei Zhang; Han Meng; Yuchun Yang; Wensheng Lan; Weidong Wang; Paul K. S. Lam; Xiao-Yan Li; Ji-Dong Gu (Ecotoxicology, 2021)

Distribution of ammonia-oxidizing archaea and bacteria along an engineered coastal ecosystem in subtropical China - Yong-Feng Wang; Ji-Dong Gu; Richard P. Dick; Wei Han; Hui-Xiao Yang; Huan-Qin Liao; Yi Zhou; Han Meng (Ecotoxicology, 2021)

Settlement patterns of mountainous half-filled and half-cut widened subgrade with retaining wall - Yong-guo Fu; Xin Jiang; Han-yan Gu; Yan-jun Qiu (Journal of Mountain Science, 2021)

Effects on the STAT3-shRNA in Non-Small-Cell Lung Cancer Therapy: Design, Induction of Apoptosis, and Conjugation with Chitosan-Based Gene Vectors - Wangwang Zhang; Yan Zhang; Zhiwen Jiang; Le Sun; Litong Wang; Zhiyang Gu; Wenya Li; Lili Guo; Xiaotong Chen; Haibin Zhang; Baoqin Han; Jing Chang (Journal of Ocean University of China, 2021)

Apamin inhibits renal fibrosis via suppressing TGF-β1 and STAT3 signaling in vivo and in vitro - Mi-Gyeong Gwon; Hyun-Jin An; Hyemin Gu; Young-Ah Kim; Sang Mi Han; Kwan-Kyu Park (Journal of Molecular Medicine, 2021)

Differential DNA Methylation Profiles in Patients with Temporal Lobe Epilepsy and Hippocampal Sclerosis ILAE Type I - Wang Zhang; Haiyang Wang; Binchao Liu; Miaomiao Jiang; Yifei Gu; Shi Yan; Xian Han; Alicia Y. Hou; Chongyang Tang; Zhenfeng Jiang; Hong Shen; Meng Na; et al. (Journal of Molecular Neuroscience, 2021)

Dietary Shifts and Risks of Artifact Ingestion for Argentine Shortfin Squid Illex argentinus in the Southwest Atlantic - Ssu-Wei Chang; Ruei-Gu Chen; Tsung-Han Liu; Yao-Chang Lee; Chih-Shin Chen; Tai-Sheng Chiu; Chia-Ying Ko (Frontiers in Marine Science, 2021)
Cephalopods play an important role in both ecology and fisheries. Variations in the dietary compositions of squids with large populations further promote interactions between different trophic levels in marine ecosystems. Moreover, due to marine pollution, squids are also at risks of artifact ingestion, and there is limited understanding about the influence of artifacts on the feeding behavior of squids. We examined 296 stomachs of the Argentine shortfin squid Illex argentinus collected through commercial catches across the Southwest Atlantic from February to April of 2018 and 2019 to establish the monthly dietary compositions and risks of artifact ingestion. The results supported typical observations that the Argentine shortfin squids switched from a diet dominated by crustaceans at small sizes to consuming larger prey, predominantly fishes and/or cephalopods, at large sizes during their growth and southward migration. Significantly higher consumption of fishes was observed in recent years compared with that observed in other studies since 1992. The ingested artifacts examined were composed of plastic and non-plastic materials. Artifacts were observed in 19.9% of the total number of stomachs, with 20.5% of the empty stomachs containing artifact remains. The results indicate that although the main dietary compositions of the Argentine shortfin squid maintain the taxonomic groups of prey compositions, the dietary structure, i.e., composition percentage, is varying. The detection of artifacts suggests that environmental monitoring is needed in this region in order to manage and conserve the squid and safeguard aquatic food safety.

Interactive effect of water level and flushing rate on population dynamics of a harmful cyanobacterial species: Raphidiopsis raciborskii - Quehui Tang; Lamei Lei; Li Zhao; Jiguang Gu; Lijuan Xiao; Bo-Ping Han (Ecotoxicology, 2021)

Fusarium solani G6, a novel vitexin-producing endophytic fungus: characterization, yield improvement and osteoblastic proliferation activity - Pei-jia Tang; Zhi-hui Zhang; Li-li Niu; Cheng-bo Gu; Wen-yi Zheng; Hai-chao Cui; Xiao-han Yuan (Biotechnology Letters, 2021)

2D anisotropic nonslant stack beam migration for multicomponent seismic data - Jianguang Han; Zhiwei Liu; Yun Wang; Jiayong Yan; Bingluo Gu (Arabian Journal of Geosciences, 2021)

Dependency analysis of frequency and strength of gamma oscillations on input difference between excitatory and inhibitory neurons - Xiaochun Gu; Fang Han; Zhijie Wang (Cognitive Neurodynamics, 2021)

Effect of juvenile omni-benthivorous fish (Carassius carassius) disturbance on the efficiency of lanthanum-modified bentonite (LMB) for eutrophication control: a mesocosm study - Yanqing Han; Qisheng Li; Hu He; Jiao Gu; Zhaoshi Wu; Xiaolong Huang; Xiaojuan Zou; You Zhang; Kuanyi Li (Environmental Science and Pollution Research, 2021)

The Fe3O4-modified biochar reduces arsenic availability in soil and arsenic accumulation in indica rice (Oryza sativa L.) - Yao Yao; Hang Zhou; Xiu-Lan Yan; Xiao Yang; Kang-Wen Huang; Juan Liu; Li-Juan Li; Jing-Yi Zhang; Jiao-Feng Gu; Yaoyu Zhou; Bo-Han Liao (Environmental Science and Pollution Research, 2021)

Docosahexaenoic Acid (DHA) Supplementation Alters Phospholipid Species and Lipid Peroxidation Products in Adult Mouse Brain, Heart, and Plasma - Grace Y. Sun; Michael K. Appenteng; Runting Li; Taeseon Woo; Bo Yang; Chao Qin; Meixia Pan; Magdalena Cieślik; Jiankun Cui; Kevin L. Fritsche; Zezong Gu; Matthew Will; et al. (NeuroMolecular Medicine, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Pathotypes of Phytophthora sojae and their distribution in Jilin, China - Zhuoqun Zhang; Yuqi Zhao; Han Yu; Yufei Chen; Xin Gu; Jingzhi Wen (Journal of Plant Pathology, 2021)

Preparation and antibacterial properties of gold nanoparticles: a review - Xiao Gu; Zhixiang Xu; Lipeng Gu; Huayu Xu; Fengxia Han; Bo Chen; Xuejun Pan (Environmental Chemistry Letters, 2021)

New nitrogen-containing metabolites from cultures of rice false smut pathogen Villosiclava virens - Ali Wang; Peng Li; Peipei Han; Gan Gu; Tijiang Shan; Daowan Lai; Ligang Zhou (Natural Product Research, 2021)

Update on recommendations for the diagnosis and treatment of SARS-CoV-2 infection in children - Hongjun Miao; Han Li; Yinying Yao; Mingfu Wu; Chao Lu; Jun Wang; Man Tian; Ying Li; Peiliang Luo; Jianhui Gu; Bin Yuan; Shouchuan Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Since the outbreak of novel coronavirus infection pneumonia in Wuhan City, China, in late 2019, such cases have been gradually reported in other parts of China and abroad. Children have become susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of their immature immune function. As the outbreak has progressed, more cases of novel coronavirus infection/pneumonia in children have been reported. Compared with adults, the impact of SARS-CoV-2 infection in children is less severe, with a lower incidence and susceptibility in children, which results in fewer children being tested, thereby underestimating the actual number of infections. Therefore, strengthening the diagnosis of the disease is particularly important for children, and early and clear diagnosis can determine treatment strategies and reduce the harm caused by the disease to children. According to the Novel Coronavirus Infection Pneumonia Diagnosis and Treatment Standards ( trial version 7 ) issued by National Health Committee and the latest diagnosis and treatment strategies for novel coronavirus infection pneumonia in children, this review summarizes current strategies on diagnosis and treatment of SARS-CoV-2 infection in children.

Effects of juvenile crucian carp (Carassius carassius) removal on submerged macrophyte growth—implications for subtropical shallow lake restoration - Yanqing Han; Jiao Gu; Qisheng Li; You Zhang; Hu He; Ruijie Shen; Kuanyi Li (Environmental Science and Pollution Research, 2020)

Metagenomic Analysis Revealed that the Terrestrial Pollutants Override the Effects of Seasonal Variation on Microbiome in River Sediments - Han Qiu; Likun Gu; Bo Sun; Jianyun Zhang; Miao Zhang; Shanshan He; Shuqing An; Xin Leng (Bulletin of Environmental Contamination and Toxicology, 2020)

Intelligent identification method for near-surface ground fissures based on seismic data - Su-Zhen Shi; Jian-Ying Gu; Jian Feng; Pei-fei Duan; You-chao Qi; Qi Han (Applied Geophysics, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Soil moisture estimation using Bayesian Maximum Entropy algorithm from FY3-B, MODIS and ASTER GDEM remote-sensing data in a maize region of HeBei province, China - Chunmei Wang; Qiuxia Xie; Xingfa Gu; Tao Yu; Qingyan Meng; Xiang Zhou; Leran Han; Yulin Zhan (International Journal of Remote Sensing, 2020)

Combined effects of green manure returning and addition of sewage sludge compost on plant growth and microorganism communities in gold tailings - Yan-Jun Ai; Fu-Ping Li; Hai-Hong Gu; Xiao-Jie Chi; Xue-Tao Yuan; Dong-Yun Han (Environmental Science and Pollution Research, 2020)

The influence of flow rates and water depth gradients on the growth process of submerged macrophytes and the biomass composition of the phytoplankton assemblage in eutrophic water: an analysis based on submerged macrophytes photosynthesis parameters - Duo Xu; Yan Xia; Zhaoxin Li; Yonggang Gu; Chunhua Lou; Hao Wang; Jinlong Han (Environmental Science and Pollution Research, 2020)

Correction to: Adipose mesenchymal stem cell exosomes promote wound healing through accelerated keratinocyte migration and proliferation by activating the AKT/HIF-1α axis - Yue Zhang; Fei Han; Lan Gu; Peng Ji; Xuekang Yang; Mengdong Liu; Ke Tao; Dahai Hu (Journal of Molecular Histology, 2020)

Adipose mesenchymal stem cell exosomes promote wound healing through accelerated keratinocyte migration and proliferation by activating the AKT/HIF-1α axis - Yue Zhang; Fei Han; Lan Gu; Peng Ji; Xuekang Yang; Mengdong Liu; Kao Tao; Dahai Hu (Journal of Molecular Histology, 2020)

Species diversity and seasonal dynamics of filamentous cyanobacteria in urban reservoirs for drinking water supply in tropical China - Yang Yang; Xunhao Zheng; Quehui Tang; Jiguang Gu; Lamei Lei; Bo-Ping Han (Ecotoxicology, 2020)

The characteristics and genome analysis of vB_ApiP_XC38, a novel phage infecting Acinetobacter pittii - Mengjun Cheng; Man Luo; Hengyu Xi; Yunze Zhao; Shuai Le; Li-Kuang Chen; Demeng Tan; Yuan Guan; Tianqi Wang; Wenyu Han; Nannan Wu; Tongyu Zhu; et al. (Virus Genes, 2020)

Decadal change in summer precipitation over the east of Northwest China and its associations with atmospheric circulations and sea surface temperatures - Shasha Shang; Gaofeng Zhu; Ruolin Li; Jie Xu; Juan Gu; Huiling Chen; Xiaowen Liu; Tuo Han (International Journal of Climatology, 2020)
As global warming has progressed, precipitation patterns over arid Northwest China have undergone significant change. In this study, changes in summer (JJA) precipitation over the eastern part of Northwest China (ENWC) from 1980 to 2014 were investigated using the China gridded monthly precipitation dataset (CN05.1). The results showed that summer precipitation over the ENWC experienced a decadal wet‐to‐dry shift in 1998. Westerlies played an important role in the upper atmospheric levels in terms of water vapour transport; the decadal variations in summer precipitation were principally controlled by the water vapour input from the ENWC's western boundary. In addition, the decadal variations in summer precipitation in the ENWC appear to be associated with a meridional teleconnection around 110°E and a zonal pattern over 45–60°N in the lower troposphere. These two teleconnections led to cyclonic anomalies in the ENWC and enhanced water vapour transport into the ENWC, resulting in above‐normal precipitation during the 1989–1998 decadal period. Further, the warmer (colder) sea surface temperatures (SSTs) observed in the tropical Eastern Pacific correspond to the southward (northward) displacement of the Asian jet stream and a negative (positive) phase of the Silk Road pattern, resulting in a wet (dry) ENWC. Moreover, the SST anomalies in the North Atlantic and Northwest Pacific may affect summer precipitation over the ENWC via a zonal teleconnection in the middle troposphere.

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Effect of three Napier grass varieties on phytoextraction of Cd- and Zn-contaminated cultivated soil under mowing and their safe utilization - Wen-Jun Yang; Jiao-Feng Gu; Hang Zhou; Fang Huang; Teng-Yue Yuan; Jing-Yi Zhang; Shi-Long Wang; Zhi-Guang Sun; Hong-Wei Yi; Bo-Han Liao (Environmental Science and Pollution Research, 2020)

Cleaning chromium pollution in aquatic environments by bioremediation, photocatalytic remediation, electrochemical remediation and coupled remediation systems - Caiwen He; Lipeng Gu; Zhixiang Xu; Huan He; Gen Fu; Fengxia Han; Bin Huang; Xuejun Pan (Environmental Chemistry Letters, 2020)

Cumulative damage evolution and failure modes of the bedding rock slope under frequent microseisms - Zhiyun Deng; Xinrong Liu; Yongquan Liu; Shulin Liu; Yafeng Han; Yiliang Tu; Jun Gu (Arabian Journal of Geosciences, 2020)

Taxonomic study of three new Antarctic Asterochloris (Trebouxio-phyceae) based on morphological and molecular data - Jong Im Kim; Yong Jun Kim; Seung Won Nam; Jae Eun So; Soon Gyu Hong; Han-Gu Choi; Woongghi Shin (Algae, 2020)

Vitamin C inhibits lipid deposition through GSK-3β/mTOR signaling in the liver of zebrafish - Dongwu Liu; Yaqi Gu; Qiuxiang Pang; Qiang Han; Ao Li; Weiwei Wu; Xiuzhen Zhang; Qilong Shi; Lanlan Zhu; Hairui Yu; Qin Zhang (Fish Physiology and Biochemistry, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Exploiting the reference genome sequence of hexaploid wheat: a proteomic study of flour proteins from the cultivar Chinese Spring - Susan B. Altenbach; Han-Chang Chang; Annamaria Simon-Buss; Toni Mohr; Naxin Huo; Yong Q. Gu (Functional & Integrative Genomics, 2020)

Morphology and phylogenetic relationships of Micractinium (Chlorellaceae, Trebouxiophyceae) taxa, including three new species from Antarctica - Hyunsik Chae; Sooyeon Lim; Han Soon Kim; Han-Gu Choi; Ji Hee Kim (Algae, 2019)

Evaluation of Genomic Selection for Seven Economic Traits in Yellow Drum (Nibea albiflora) - Guijia Liu; Linsong Dong; Linlin Gu; Zhaofang Han; Wenjing Zhang; Ming Fang; Zhiyong Wang (Marine Biotechnology, 2019)
Yellow drum ( Nibea albiflora ) is an important maricultural fish in China, and genetic improvement is necessary for this species. This research evaluated the application of genomic selection methods to predict the genetic values of seven economic traits for yellow drum. Using genome-wide single-nucleotide polymorphisms (SNPs), we estimated the genetic parameters for seven traits, including body length (BL), swimming bladder index (SBI), swimming bladder weight (SBW), body thickness (BT), body height (BH), body length/body height ratio (LHR), and gonad weight index (GWI). The heritability estimates ranged from 0.309 to 0.843. We evaluated the prediction performance of various statistical methods, and no one method provided the highest predictive ability for all traits. We then evaluated and compared the use of genome-wide association study (GWAS)–informative SNPs and random SNPs for prediction and found that GWAS-informative SNPs obviously increased. It only needed 5 and 100 informative SNPs for LHR and BT to achieve almost the same predictive abilities as using genome-wide SNPs, and for BL, SBI, SBW, BH, and GWI, about 1000 to 3000 informative SNPs were needed to achieve whole-genome level predictive abilities. It can be concluded from the test results that breeders can use fewer SNPs to save the breeding costs of genomic selection for some traits.

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Effects of Immunostimulants, Prebiotics, Probiotics, Synbiotics, and Potentially Immunoreactive Feed Additives on Olive Flounder ( Paralichthys olivaceus ): A Review - Md Tawheed Hasan; Won Je Jang; Jong Min Lee; Bong-Joo Lee; Sang Woo Hur; Sang Gu Lim; Kang Woong Kim; Hyon-Sob Han; In-Soo Kong (Reviews in Fisheries Science & Aquaculture, 2019)

Phenotypic and molecular spectrum of Korean patients with Lesch-Nyhan syndrome and attenuated clinical variants - Ja Hyang Cho; Jin-Ho Choi; Sun Hee Heo; Gu-Hwan Kim; Mi-Sun Yum; Beom Hee Lee; Han-Wook Yoo (Metabolic Brain Disease, 2019)

Biological properties and genomics analysis of vB_KpnS_GH-K3, a Klebsiella phage with a putative depolymerase-like protein - Ruopeng Cai; Zijing Wang; Gang Wang; Hao Zhang; Mengjun Cheng; Zhimin Guo; Yalu Ji; Hengyu Xi; Xinwu Wang; Yibing Xue; Sadeeq ur Rahman; Changjiang Sun; et al. (Virus Genes, 2019)

Exploring the Probiotic and Compound Feed Fermentative Applications of Lactobacillus plantarum SK1305 Isolated from Korean Green Chili Pickled Pepper - Kai-Min Niu; Damini Kothari; Sang-Buem Cho; Sung-Gu Han; In-Geun Song; Sam-Churl Kim; Soo-Ki Kim (Probiotics and Antimicrobial Proteins, 2019)

Aerobic cometabolism of tetrabromobisphenol A by marine bacterial consortia - Chen Gu; Jing Wang; Zelong Zhao; Ying Han; Miaomiao Du; Shuaijun Zan; Fenbo Wang (Environmental Science and Pollution Research, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Methoxetamine Induces Cytotoxicity in H9c2 Cells: Possible Role of p21 Protein (Cdc42/Rac)-Activated Kinase 1 - Kyung Sik Yoon; Sun Mi Gu; Santosh Lamichhane; Kyoung Moon Han; Jisoon Shin; Young-Hoon Kim; Soo Kyung Suh; Hye Jin Cha; Jaesuk Yun (Cardiovascular Toxicology, 2019)

The apple U-box E3 ubiquitin ligase MdPUB29 contributes to activate plant immune response to the fungal pathogen Botryosphaeria dothidea - Peng-Liang Han; Yuan-Hua Dong; Kai-Di Gu; Jian-Qiang Yu; Da-Gang Hu; Yu-Jin Hao (Planta, 2019)

Application of the SeDeM Expert System in Studies for Direct Compression Suitability on Mixture of Rhodiola Extract and an Excipient - Shulin Wan; Rui Yang; Han Zhang; Xuelian Li; Mingxian Gu; Tianbing Guan; Jianbing Ren; Huimin Sun; Chuanyun Dai (AAPS PharmSciTech, 2019)

The links between potassium availability and soil exchangeable calcium, magnesium, and aluminum are mediated by lime in acidic soil - Tianfu Han; Andong Cai; Kailou Liu; Jing Huang; Boren Wang; Dongchu Li; Muhammad Qaswar; Gu Feng; Huimin Zhang (Journal of Soils and Sediments, 2019)

Novel loci fsd6.1 and Csgl3 regulate ultra-high fruit spine density in cucumber - Kailiang Bo; Han Miao; Min Wang; Xiaoxiao Xie; Zichao Song; Qing Xie; Lixue Shi; Weiping Wang; Shuang Wei; Shengping Zhang; Xingfang Gu (Theoretical and Applied Genetics, 2019)

A Review on the Macromolecular Compositions of Phytoplankton and the Implications for Aquatic Biogeochemistry - P. S. Bhavya; Bo Kyung Kim; Naeun Jo; Kwanwoo Kim; Jae Joong Kang; Jae Hyung Lee; Dabin Lee; Jang Han Lee; HuiTae Joo; So Hyun Ahn; Yewon Kim; Jun-Oh Min; et al. (Ocean Science Journal, 2019)

Temporal variation in bacterial and methanogenic communities of three full-scale anaerobic digesters treating swine wastewater - Gyuseong Han; Seung Gu Shin; Kyungjin Cho; Joonyeob Lee; Woong Kim; Seokhwan Hwang (Environmental Science and Pollution Research, 2019)

The impact of biotic and abiotic factors on the distribution of surface sediment dinoflagellate cyst assemblages on the Nanji Island in the East China Sea - Han Gao; Shengpao You; Xiangdong Lei; Yunpu Xiao; Haifeng Gu; Mengmeng Tong (Acta Oceanologica Sinica, 2019)

Genetic analysis and identification of a candidate gene associated with in vitro regeneration ability of cucumber - Ye Wang; Qian Zhou; Guangtao Zhu; Shenhao Wang; Yongshuo Ma; Han Miao; Shengping Zhang; Sanwen Huang; Zhonghua Zhang; Xingfang Gu (Theoretical and Applied Genetics, 2018)

Relevance of the incubation period in cytotoxicity testing with primary human hepatocytes - Xiaolong Gu; Wiebke Albrecht; Karolina Edlund; Franziska Kappenberg; Jörg Rahnenführer; Marcel Leist; Wolfgang Moritz; Patricio Godoy; Cristina Cadenas; Rosemarie Marchan; Tim Brecklinghaus; Laia Tolosa Pardo; et al. (Archives of Toxicology, 2018)

Transcriptomic analysis of porcine PBMCs in response to Actinobacillus pleuropneumoniae reveals the dynamic changes of differentially expressed genes related to immuno-inflammatory responses - Hexiang Jiang; Rining Zhu; Hongtao Liu; Chuntong Bao; Jianfang Liu; Abdalla Eltahir; Paul R. Langford; Diangang Sun; Zhonghua Liu; Changjiang Sun; Jingmin Gu; Wenyu Han; et al. (Antonie van Leeuwenhoek, 2018)

Piperlongumine Improves Lipopolysaccharide-Induced Amyloidogenesis by Suppressing NF-KappaB Pathway - Sun Mi Gu; Hee Pom Lee; Young Wan Ham; Dong Ju Son; Hoi Yeong Kim; Ki Wan Oh; Sang-Bae Han; Jaesuk Yun; Jin Tae Hong (NeuroMolecular Medicine, 2018)

Climate change favours a destructive agricultural pest in temperate regions: late spring cold matters - Shimin Gu; Peng Han; Zhengpei Ye; Lynda E. Perkins; Jing Li; Huiqing Wang; Myron P. Zalucki; Zhaozhi Lu (Journal of Pest Science, 2018)

Rapid monitoring of proline accumulation in paprika leaf sap relative to leaf position and water stress - Shiva Ram Bhandari; Min Ji Lee; Han Cheol Rhee; Gyeong Lee Choi; Sang Seok Oh; Je Taek Lee; Jun Gu Lee (Horticulture, Environment, and Biotechnology, 2018)

Combined fine mapping, genetic diversity, and transcriptome profiling reveals that the auxin transporter gene ns plays an important role in cucumber fruit spine development - Qing Xie; Panna Liu; Lixue Shi; Han Miao; Kailiang Bo; Ye Wang; Xingfang Gu; Shengping Zhang (Theoretical and Applied Genetics, 2018)

Isolation and identification of Salmonella pullorum bacteriophage YSP2 and its use as a therapy for chicken diarrhea - Kunyuan Tie; Yuyu Yuan; Shiqing Yan; Xi Yu; Qiuyang Zhang; Huihui Xu; Yang Zhang; Jingmin Gu; Changjiang Sun; Liancheng Lei; Wenyu Han; Xin Feng (Virus Genes, 2018)

Ideal cardiovascular health and incidence of atherosclerotic cardiovascular disease among Chinese adults: the China-PAR project - Chao Han; Fangchao Liu; Xueli Yang; Jichun Chen; Jianxin Li; Jie Cao; Ying Li; Chong Shen; Ling Yu; Zhendong Liu; Xianping Wu; Liancheng Zhao; et al. (Science China Life Sciences, 2018)

Effects of 7-MEGA TM 500 on Oxidative Stress, Inflammation, and Skin Regeneration in H 2 O 2 -Treated Skin Cells - In-Bong Song; Hyejung Gu; Hye-Ju Han; Na-Young Lee; Ji-Yun Cha; Yeon-Kyong Son; Jungkee Kwon (Toxicological Research, 2018)

Selenium Protects against Lead-induced Apoptosis via Endoplasmic Reticulum Stress in Chicken Kidneys - Xiaoyu Wang; Yang An; Wanying Jiao; Zhongyuan Zhang; Hui Han; Xianhong Gu; Xiaohua Teng (Biological Trace Element Research, 2018)

Biogeographic pattern of four endemic Pyropia from the east coast of Korea, including a new species, Pyropia retorta (Bangiaceae, Rhodophyta) - Sun-Mi Kim; Han-Gu Choi; Mi-Sook Hwang; Hyung-Seop Kim (Algae, 2018)

Subcritical n-hexane/isopropanol extraction of lipid from wet microalgal pastes of Scenedesmus obliquus - Xiaoyu Bian; Wenbiao Jin; Qiong Gu; Xu Zhou; Yuhe Xi; Renjie Tu; Song-Fang Han; Guo-Jun Xie; Shu-Hong Gao; Qilin Wang (World Journal of Microbiology and Biotechnology, 2018)

Effects of an additive (hydroxyapatite–biochar–zeolite) on the chemical speciation of Cd and As in paddy soils and their accumulation and translocation in rice plants - Jiao-Feng Gu; Hang Zhou; Wen-Tao Yang; Pei-Qin Peng; Ping Zhang; Min Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

P21Waf1/Cip1 depletion promotes dexamethasone-induced apoptosis in osteoblastic MC3T3-E1 cells by inhibiting the Nrf2/HO-1 pathway - Dandan Han; Jian Gao; Xiaolong Gu; Jan Georg Hengstler; Limei Zhang; Muhammad Shahid; Tariq Ali; Bo Han (Archives of Toxicology, 2018)

Human placenta-derived mesenchymal stem cells loaded on linear ordered collagen scaffold improves functional recovery after completely transected spinal cord injury in canine - Sufang Han; Zhifeng Xiao; Xing Li; Huan Zhao; Bin Wang; Zhixue Qiu; Zhi Li; Xin Mei; Bai Xu; Caixia Fan; Bing Chen; Jin Han; et al. (Science China Life Sciences, 2018)

China in action: national strategies to combat against emerging infectious diseases - Min Han; Jinhui Gu; George F. Gao; William J. Liu (Science China Life Sciences, 2017)

A synthetic cannabinoid JWH-210 reduces lymphoid organ weights and T-cell activator levels in mice via CB2 receptors - Sun Mi Gu; Hyun Jin Lee; Tac-hyung Lee; Yun Jeong Song; Young-Hoon Kim; Kyoung-Moon Han; Jisoon Shin; Hye-Kyung Park; Hyung Soo Kim; Hye Jin Cha; Jaesuk Yun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

(E)-2-Methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) Phenol Ameliorates LPS-Mediated Memory Impairment by Inhibition of STAT3 Pathway - Ji Yeon Choi; Chul Ju Hwang; Do Yeon Lee; Sun Mi Gu; Hee Pom Lee; Dong Young Choi; Ki Wan Oh; Sang-Bae Han; Jin Tae Hong (NeuroMolecular Medicine, 2017)

An anti-Propionibacterium acnes antibody shows heterologous resistance to an Actinobacillus pleuropneumoniae infection independent of neutrophils in mice - Jian-fang Liu; Qiu-yue Ma; Ri-ning Zhu; Meng-jun Cheng; Chun-tong Bao; Jing-min Gu; Chang-jiang Sun; Paul Richard Langford; Wen-yu Han; Lian-cheng Lei (Immunologic Research, 2017)

Identification and association of novel lncRNA pouMU1 gene mutations with chicken performance traits - Tuanhui Ren; Yanting Zhou; Yu Zhou; Weihua Tian; Zhenzhen Gu; Song Zhao; Yadi Chen; Ruili Han; Xiaojun Liu; Xiangtao Kang; Zhuanjian Li (Journal of Genetics, 2017)

The N-terminal and central domain of colicin A enables phage lysin to lyse Escherichia coli extracellularly - Guangmou Yan; Jianfang Liu; Qiang Ma; Rining Zhu; Zhimin Guo; Chencheng Gao; Shuang Wang; Ling Yu; Jingmin Gu; Dongliang Hu; Wenyu Han; Rui Du; et al. (Antonie van Leeuwenhoek, 2017)

Influence of Rapeseed Cake on Iron Plaque Formation and Cd Uptake by Rice (Oryza sativa L.) Seedlings Exposed to Excess Cd - Wen-Tao Yang; Hang Zhou; Jiao-Feng Gu; Qing-ru Zeng; Bo-Han Liao (Bulletin of Environmental Contamination and Toxicology, 2017)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

Identifying functional groups and ecological roles of tropical and subtropical freshwater Cladocera in Asia - Eric Zeus C. Rizo; Yangliang Gu; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2017)

Preparation and In Vitro Evaluation of a MRI Contrast Agent Based on Aptamer-Modified Gadolinium-Loaded Liposomes for Tumor Targeting - Lan-Xin Zhang; Kun-Feng Li; Huan Wang; Meng-Jie Gu; Li-Si Liu; Zhuo-Zhao Zheng; Nan-Yin Han; Zhen-Jun Yang; Tian-Yuan Fan (AAPS PharmSciTech, 2017)

Immune recovery after fluid resuscitation in rats with severe hemorrhagic shock - Feng Yao; Yuan-qiang Lu; Jiu-kun Jiang; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2017)

The microtubule end‐binding protein FgEB1 regulates polar growth and fungicide sensitivity via different interactors in Fusarium graminearum - Zunyong Liu; Sisi Wu; Yun Chen; Xinyue Han; Qin Gu; Yanni Yin; Zhonghua Ma (Environmental Microbiology, 2017)
Summary In yeasts, the end‐binding protein 1 (EB1) homologs regulate microtubule dynamics, cell polarization, and chromosome stability. However, functions of EB1 orthologs in plant pathogenic fungi have not been characterized yet. Here, we observed that the FgEB1 deletion mutant (ΔFgEB1) of Fusarium graminearum exhibits twisted hyphae, increased hyphal branching and curved conidia, indicating that FgEB1 is involved in the regulation of cellular polarity. Microscopic examination further showed that the microtubules of ΔFgEB1 exhibited less organized in comparison with those of the wild type. In addition, the lack of FgEB1 also altered the distribution of polarity‐related class I myosin via the interaction with the actin. On the other hand, we identified four core septins as FgEB1‐interacting proteins, and found that FgEB1 and septins regulated conidial polar growth in the opposite orientation. Interestingly, FgEB1 and FgKar9 constituted another complex that modulated the response to carbendazim, a microtubule‐damaging agent specifically. In addition, the deletion of FgEB1 led to dramatically decreased deoxynivalenol (DON) biosynthesis. Taken together, results of this study indicate that FgEB1 regulates cellular polarity, fungicide sensitivity and DON biosynthesis via different interactors in F. graminarum , which provides a novel insight into understanding of the biological functions of EB1 in filamentous fungi.

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

Behavioral responses of chinstrap and gentoo penguins to a stuffed skua and human nest intruders - Won Young Lee; Jin-Woo Jung; Han-Gu Choi; Hosung Chung; Yeong-Deok Han; Sam-Rae Cho; Jeong-Hoon Kim (Polar Biology, 2017)

Proteomic and transcriptomic investigations on cold‐responsive properties of the psychrophilic A ntarctic bacterium P sychrobacter sp. PAMC 21119 at subzero temperatures - Hye Yeon Koh; Hyun Park; Jun Hyuck Lee; Se Jong Han; Young Chang Sohn; Sung Gu Lee (Environmental Microbiology, 2017)
Summary Psychrobacter sp. PAMC 21119, isolated from Antarctic permafrost soil, grows and proliferates at subzero temperatures. However, its major mechanism of cold adaptation regulation remains poorly understood. We investigated the transcriptomic and proteomic responses of this species to cold temperatures by comparing profiles at −5°C and 20°C to understand how extreme microorganisms survive under subzero conditions. We found a total of 2,906 transcripts and 584 differentially expressed genes (≥ twofold, P P Psychrobacter sp. PAMC 21119 has developed to adapt to the cold environment in Antarctica.

Inflammation-induced CD69+ Kupffer cell feedback inhibits T cell proliferation via membrane-bound TGF-β1 - Xiang Zhang; Zhengping Jiang; Yan Gu; Yanfang Liu; Xuetao Cao; Yanmei Han (Science China Life Sciences, 2016)

An Investigation of the Innate Immune Response in Bovine Mammary Epithelial Cells Challenged by Prototheca zopfii - Zhaoju Deng; Muhammad Shahid; Limei Zhang; Jian Gao; Xiaolong Gu; Shiyao Zhang; Jiaqi Zou; Séamus Fanning; Bo Han (Mycopathologia, 2016)

Brain functional network abnormality extends beyond the sensorimotor network in brachial plexus injury patients - Jun-Tao Feng; Han-Qiu Liu; Xu-Yun Hua; Yu-Dong Gu; Jian-Guang Xu; Wen-Dong Xu (Brain Imaging and Behavior, 2016)

Global sensitivity analysis of PROSAIL model parameters when simulating Moso bamboo forest canopy reflectance - Chengyan Gu; Huaqiang Du; Fangjie Mao; Ning Han; Guomo Zhou; Xiaojun Xu; Shaobo Sun; Guolong Gao (International Journal of Remote Sensing, 2016)

Calmodulin‐mediated suppression of 2‐ketoisovalerate reductase in Beauveria bassiana beauvericin biosynthetic pathway - Jiyoung Kim; Deok‐Hyo Yoon; Junsang Oh; Min‐Woo Hyun; Jae‐Gu Han; Gi‐Ho Sung (Environmental Microbiology, 2016)
Summary Ketoisovalerate reductase (KIVR, E.C. 1.2.7.7) mediates the specific reduction of 2‐ketoisovalerate (2‐Kiv) to d ‐hydroxyisovalerate ( d ‐Hiv), a precursor for beauvericin biosynthesis. Beauvericin, a famous mycotoxin produced by many fungi, is a cyclooligomer depsipeptide, which has insecticidal, antimicrobial, antiviral, and cytotoxic activities. In this report, we demonstrated that Beauveria bassiana 2‐ketoisovalerate reductase (BbKIVR) acts as a typical KIVR enzyme in the entomopathogenic fungus B. bassiana . In addition, we found that BbKIVR interacts with calmodulin (CaM) in vitro and in vivo . The functional role of CaM‐binding to BbKIVR was to negatively regulate the BbKIVR activity in B. bassiana . Environmental stimuli such as light and salt stress suppressed BbKIVR activity in B. bassiana . Interestingly, this negative effect of BbKIVR activity by light and salt stress was recovered by CaM inhibitors, suggesting that the inhibitory mechanism is mediated through stimulation of CaM activity. Therefore, this work suggests that BbKIVR plays an important role in the beauvericin biosynthetic pathway mediated by environmental stimuli such as light and salt stress via the CaM signaling pathway.

Characterization of Stearoyl-CoA Desaturases from a Psychrophilic Antarctic Copepod, Tigriopus kingsejongensis - Woongsic Jung; Eun Jae Kim; Se Jong Han; Han-Gu Choi; Sanghee Kim (Marine Biotechnology, 2016)

Syndecan-4 regulates the bFGF-induced chemotactic migration of endothelial cells - Ran Li; Han Wu; Jun Xie; Guannan Li; Rong Gu; Lina Kang; Lian Wang; Biao Xu (Journal of Molecular Histology, 2016)

Impacts of rapeseed dregs on Cd availability in contaminated acid soil and Cd translocation and accumulation in rice plants - Wen-Tao Yang; Jiao-Feng Gu; Jia-Ling Zou; Hang Zhou; Qing-Ru Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Effects of organic acids on the photosynthetic and antioxidant properties and accumulations of heavy metals of Melilotus officinalis grown in Cu tailing - Yulin Han; Xue Wu; Jiguang Gu; Jiuzhou Zhao; Suzhen Huang; Haiyan Yuan; Jiajia Fu (Environmental Science and Pollution Research, 2016)

Rab27b is Involved in Lysosomal Exocytosis and Proteolipid Protein Trafficking in Oligodendrocytes - Yun-Tian Shen; Yun Gu; Wen-Feng Su; Jing-fei Zhong; Zi-Han Jin; Xiao-Song Gu; Gang Chen (Neuroscience Bulletin, 2016)

Characterization of DNA methyltransferase and demethylase genes in Fragaria vesca - Tingting Gu; Shuai Ren; Yuanhua Wang; Yuhui Han; Yi Li (Molecular Genetics and Genomics, 2016)

Cellular growth and fatty acid content of Arctic chlamydomonadalean - Woongsic Jung; Eun Jae Kim; Suyoun Lim; Hyunji Sim; Se Jong Han; Sanghee Kim; Sung-Ho Kang; Han-Gu Choi (Algae, 2016)

Exercise protects against PCB-induced inflammation and associated cardiovascular risk factors - Margaret O. Murphy; Michael C. Petriello; Sung Gu Han; Manjula Sunkara; Andrew J. Morris; Karyn Esser; Bernhard Hennig (Environmental Science and Pollution Research, 2016)

Identification and evolutionary history of the DD41D transposons in insects - Hua-Hao Zhang; Yi-Hong Shen; Xiao-Min Xiong; Min-Jin Han; Xiao-Gu Zhang (Genes & Genomics, 2016)

Trimeric autotransporter adhesins contribute to Actinobacillus pleuropneumoniae pathogenicity in mice and regulate bacterial gene expression during interactions between bacteria and porcine primary alveolar macrophages - Wanhai Qin; Lei Wang; Ruidong Zhai; Qiuyue Ma; Jianfang Liu; Chuntong Bao; Hu Zhang; Changjiang Sun; Xin Feng; Jingmin Gu; Chongtao Du; Wenyu Han; et al. (Antonie van Leeuwenhoek, 2016)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

Complete genomic characterization and genetic diversity of four European genotype porcine reproductive and respiratory syndrome virus isolates from China in 2011 - Zhi Zhou; Qi Liu; Dongmei Hu; Qian Zhang; Tao Han; Ying Ma; Xiaoxue Gu; Xinyan Zhai; Kegong Tian (Virus Genes, 2015)

Insights into tetracycline adsorption onto kaolinite and montmorillonite: experiments and modeling - Yanping Zhao; Xueyuan Gu; Shiyin Li; Ruiming Han; Guoxiang Wang (Environmental Science and Pollution Research, 2015)

Regulation of a phenylalanine ammonia lyase ( BbPAL ) by calmodulin in response to environmental changes in the entomopathogenic fungus B eauveria bassiana - Jiyoung Kim; Hyesung Park; Jae‐Gu Han; Junsang Oh; Hyung‐Kyoon Choi; Seong Hwan Kim; Gi‐Ho Sung (Environmental Microbiology, 2015)
Summary Phenylalanine ammonia lyase ( PAL , E. C . 4.3.1.5) catalyses the deamination of L ‐phenylalanine to trans ‐cinnamic acid and ammonia, facilitating a critical step in the phenylpropanoid pathway that produces a variety of secondary metabolites. In this study, we isolated BbPAL gene in the entomopathogenic fungus B eauveria bassiana . According to multiple sequence alignment, homology modelling and in vitro PAL activity, we demonstrated that BbPAL acts as a typical PAL enzyme in B . bassiana . BbPAL interacted with calmodulin ( CaM ) in vitro and in vivo , indicating that BbPAL is a novel CaM ‐binding protein. The functional role of CaM in BbPAL action was to negatively regulate the BbPAL activity in B . bassiana . High‐performance liquid chromatography analysis revealed that L ‐phenylalanine was reduced and trans ‐cinnamic acid was increased in response to the CaM inhibitor W ‐7. Dark conditions suppressed BbPAL activity in B . bassiana , compared with light. In addition, heat and cold stresses inhibited BbPAL activity in B . bassiana . Interestingly, these negative effects of BbPAL activity by dark, heat and cold conditions were recovered by W ‐7 treatment, suggesting that the inhibitory mechanism is mediated through stimulation of CaM activity. Therefore, this work suggests that BbPAL plays a role in the phenylpropanoid pathway mediated by environmental stimuli via the CaM signalling pathway.

A transcriptomic analysis of the response of the arctic pteropod Limacina helicina to carbon dioxide-driven seawater acidification - Hye Yeon Koh; Jun Hyuck Lee; Se Jong Han; Hyun Park; Seung Chul Shin; Sung Gu Lee (Polar Biology, 2015)

Deletion of a non-catalytic region increases the enzymatic activity of a β-agarase from Flammeovirga sp. MY04 - Wenjun Han; Jingyan Gu; Huihui Liu; Fuchuan Li; Zhihong Wu; Yuezhong Li (Journal of Ocean University of China, 2015)

miR-26a enhances autophagy to protect against ethanol-induced acute liver injury - Weidong Han; Xianghui Fu; Jiansheng Xie; Zhipeng Meng; Ying Gu; Xichun Wang; Ling Li; Hongming Pan; Wendong Huang (Journal of Molecular Medicine, 2015)

Prevalence of antibiotic resistance genes in antibiotic-resistant Escherichia coli isolates in surface water of Taihu Lake Basin, China - Song He Zhang; Xiaoyang Lv; Bing Han; Xiucong Gu; Pei Fang Wang; Chao Wang; Zhenli He (Environmental Science and Pollution Research, 2015)

The Study of the Effect of Hedyotis diffusa on the Proliferation and the Apoptosis of the Cervical Tumor in Nude Mouse Model - Peiying Zhang; Bei Zhang; Juan Gu; Lin Hao; Fangfang Hu; Conghui Han (Cell Biochemistry and Biophysics, 2015)

Size-dependent clearance of gold nanoparticles from lungs of Sprague–Dawley rats after short-term inhalation exposure - Sung Gu Han; Jong Seong Lee; Kangho Ahn; Yong Soon Kim; Jin Kwon Kim; Ji Huyn Lee; Jae Hoon Shin; Ki Soo Jeon; Wan Seob Cho; Nam Woong Song; Mary Gulumian; Beom Soo Shin; et al. (Archives of Toxicology, 2015)

Genome sequencing and analysis of an Escherichia coli phage vB_EcoM-ep3 with a novel lysin, Lysep3 - Meng Lv; Shuang Wang; Guangmou Yan; Changjiang Sun; Xin Feng; Jingmin Gu; Wenyu Han; Liancheng Lei (Virus Genes, 2015)

In Vivo Studies of Molybdenum-Induced Apoptosis in Kidney Cells of Caprine - Xiaolong Gu; Tariq Ali; Rongrong Chen; Guoliang Hu; Yu Zhuang; Junrong Luo; Huabin Cao; Bo Han (Biological Trace Element Research, 2015)

Increase in aliphatic glucosinolates synthesis during early seedling growth and insect herbivory in radish (Raphanus sativus L.) plant - Eun-Hye Gu; Mukhamad Su’udi; NaRae Han; Byounghoon Kwon; Sooyeon Lim; Jongkee Kim (Horticulture, Environment, and Biotechnology, 2015)

Population pharmacokinetic and pharmacodynamic model of propofol externally validated in children - Byung-Moon Choi; Hyun-Gu Lee; Hyo-Jin Byon; Soo-Han Lee; Eun-Kyung Lee; Hee-Soo Kim; Gyu-Jeong Noh (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Salinity-dependent changes in growth and fatty acid composition of new Arctic Chlamydomonas species, ArM0029A - Joon-Woo Ahn; Kwon Hwangbo; Chun Ji Yin; Jong-Min Lim; Han-Gu Choi; Youn-Il Park; Won-Joong Jeong (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Effects of nitrogen deposition rates and frequencies on the abundance of soil nitrogen-related functional genes in temperate grassland of northern China - Qiushi Ning; Qian Gu; Jupei Shen; Xiaotao Lv; Junjie Yang; Ximei Zhang; Jizheng He; Jianhui Huang; Hong Wang; Zhihong Xu; Xingguo Han (Journal of Soils and Sediments, 2015)

V-ATPase and V-PPase at the Tonoplast Affect NO3 − Content in Brassica napus by Controlling Distribution of NO3 − Between the Cytoplasm and Vacuole - Yongliang Han; Qiang Liu; Jidong Gu; Jiming Gong; Chunyun Guan; Joe Eugene Lepo; Xiangmin Rong; Haixing Song; Zhenhua Zhang (Journal of Plant Growth Regulation, 2015)

Salidroside Ameliorates Cd-Induced Calcium Overload and Gap Junction Dysfunction in BRL 3A Rat Liver Cells - Hui Zou; Di Hu; Tao Han; Hongyan Zhao; Junze Xie; Xuezhong Liu; Yi Wang; Jianhong Gu; Yan Yuan; Jianchun Bian; Zongping Liu (Biological Trace Element Research, 2015)

Novel mutations and clinical outcomes of copper-histidine therapy in Menkes disease patients - Ja Hye Kim; Beom Hee Lee; Yoo-Mi Kim; Jin-Ho Choi; Gu-Hwan Kim; Chong Kun Cheon; Han-Wook Yoo (Metabolic Brain Disease, 2015)

Nitrate reutilization mechanisms in the tonoplast of two Brassica napus genotypes with different nitrogen use efficiency - Yongliang Han; Qiong Liao; Yin Yu; Haixing Song; Qiang Liu; Xiangmin Rong; Jidong Gu; Joe Eugene Lepo; Chunyun Guan; Zhenhua Zhang (Acta Physiologiae Plantarum, 2015)

Polarization of excitation light influences molecule counting in single-molecule localization microscopy - Ye Chen; Han Lin; Mandy J. Ludford-Menting; Andrew H. Clayton; Min Gu; Sarah M. Russell (Histochemistry and Cell Biology, 2015)

Re-evaluation of green tide-forming species in the Yellow Sea - Eun Ju Kang; Ju-Hyoung Kim; Keunyong Kim; Han-Gu Choi; Kwang Young Kim (Algae, 2014)

Effects of Olanzapine–Fluoxetine Combination Treatment of Major Depressive Disorders on the Quality of Life During Acute Treatment Period - Wei Qu; Shanshan Gu; Han Luo; Qianying Tang; Junwei Guo (Cell Biochemistry and Biophysics, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

New distributional record for Pyropia koreana: confirmed to occur on the South Island, New Zealand - Wendy A. Nelson; Judith E. Sutherland; Mi Sook Hwang; Han-Gu Choi (Algae, 2014)

Major chemical compositions, possible sources, and mass closure analysis of PM2.5 in Jinan, China - Jinxia Gu; Shiyong Du; Daowen Han; Lujian Hou; Jing Yi; Ja Xu; Guanghui Liu; Bin Han; Guangwu Yang; Zhi-Peng Bai (Air Quality, Atmosphere & Health, 2014)

Characteristics of easterly-induced snowfall in Yeongdong and its relationship to air-sea temperature difference - Hyoung-Gu Nam; Byung-Gon Kim; Sang-Ok Han; Chulkyu Lee; Seoung-Soo Lee (Asia-Pacific Journal of Atmospheric Sciences, 2014)

Effects of Spatial Scale of Soil Heterogeneity on the Growth of a Clonal Plant Producing Both Spreading and Clumping Ramets - Yong-Qiang Qian; Dong Luo; Gu Gong; Lei Han; Guan-Sheng Ju; Zhen-Yuan Sun (Journal of Plant Growth Regulation, 2014)

Detection of methane biogenesis in a shallow urban lake in summer - Songhe Zhang; Chuan Guo; Chao Wang; Ju Gu; Peifang Wang; Yuxin Hui; Bing Han (Journal of Soils and Sediments, 2014)

Human hepatocellular carcinoma-infiltrating CD4+CD69+Foxp3− regulatory T cell suppresses T cell response via membrane-bound TGF-β1 - Yanmei Han; Yuan Yang; Zhubo Chen; Zhengping Jiang; Yan Gu; Yanfang Liu; Sheng Xu; Chuan Lin; Zeya Pan; Weiping Zhou; Xuetao Cao (Journal of Molecular Medicine, 2014)

PCB 77 dechlorination products modulate pro-inflammatory events in vascular endothelial cells - Katryn Eske; Bradley Newsome; Sung Gu Han; Margaret Murphy; Dibakar Bhattacharyya; Bernhard Hennig (Environmental Science and Pollution Research, 2014)

Inactivation of a Gene Encoding Carotenoid Cleavage Dioxygenase (CCD4) Leads to Carotenoid-Based Yellow Coloration of Fruit Flesh and Leaf Midvein in Peach - Juanjuan Ma; Jing Li; Jianbo Zhao; Hui Zhou; Fei Ren; Lu Wang; Chao Gu; Liao Liao; Yuepeng Han (Plant Molecular Biology Reporter, 2014)

The expression of IL-2 and IL-4 in CD4+ T cells from mouse lymph nodes and spleen during HSV-1-induced facial palsy - Lintao Gu; Yuechen Han; Wenwen Liu; Yanyan Mao; Jianfeng Li; Haibo Wang (Inflammation Research, 2014)

Growth and fruit production of asian pear trees grown on Y-, T-, and vase-training systems - Jang-Jeon Choi; Mengmeng Gu; Jin-Ho Choi; Jeom-Hwa Han; Sun-Hee Yim; Yoon-Kyeong Kim; Seok-Kyu Jung; Hyun-Sug Choi (Horticulture, Environment, and Biotechnology, 2014)

Assimilating ASAR data for estimating soil moisture profile using an ensemble Kalman filter - Fan Yu; Haitao Li; Haiyan Gu; Yanshun Han (Chinese Geographical Science, 2013)

Deep RNA-Seq uncovers the peach transcriptome landscape - Lu Wang; Shuang Zhao; Chao Gu; Ying Zhou; Hui Zhou; Juanjuan Ma; Jun Cheng; Yuepeng Han (Plant Molecular Biology, 2013)

Clinical Investigation on the Beneficial Effects of the Chinese Medicinal Herb Gushen Pian on Sensorineural Deafness and Tinnitus - Suoqiang Zhai; Yaoyun Fang; Weiyan Yang; Rui Gu; Dongyi Han; Shiming Yang (Cell Biochemistry and Biophysics, 2013)

Characterization of Genes Encoding Granule-Bound Starch Synthase in Sacred Lotus Reveals Phylogenetic Affinity of Nelumbo to Proteales - Chao Gu; Lu Wang; Liyao Zhang; Yanling Liu; Mei Yang; Zhaonian Yuan; Shaohua Li; Yuepeng Han (Plant Molecular Biology Reporter, 2013)

Effects of Monogalactoglycerolipid Deficiency and Diacylglycerol Acyltransferase Overexpression on Oil Accumulation in Transgenic Tobacco - Han-Ying Wu; Chao Liu; Min-Chun Li; Ming-Ming Zhao; Dan Gu; Yi-Nong Xu (Plant Molecular Biology Reporter, 2013)

Overexpression of the glutamine synthetase gene modulates oxidative stress response in rice after exposure to cadmium stress - Hye Jung Lee; Sailila E. Abdula; Dae Won Jang; Sung-Han Park; Ung-Han Yoon; Yu Jin Jung; Kwon Kyoo Kang; Ill Sup Nou; Yong-Gu Cho (Plant Cell Reports, 2013)

Impact of matrix metalloproteinase-8 gene variations on the risk of thoracic aortic dissection in a Chinese Han population - Xiao-Zeng Wang; Xiao-Mo Du; Quan-Min Jing; Xing-Xing Li; Ruo-Xi Gu; Jiao Wang; Ya-Ling Han (Molecular Biology Reports, 2013)

Combined structure-based pharmacophore, virtual screening, and 3D-QSAR studies of structural diverse dehydrosqualene synthase inhibitors - Fei Peng; Aihua Peng; Youfu Luo; Wei Huang; Bo Han; Xiaoyan Yang; Wei Ang; Tao Yang; Mingli Xiang; Cheng Peng; Gu He (Medicinal Chemistry Research, 2013)

Congenital MTHFR deficiency causing early-onset cerebral stroke in a case homozygous for MTHFR thermolabile variant - Seung Jin Kim; Beom Hee Lee; Yoo-Mi Kim; Gu-Hwan Kim; Han-Wook Yoo (Metabolic Brain Disease, 2013)

Organic acids on the growth, anatomical structure, biochemical parameters and heavy metal accumulation of Iris lactea var. chinensis seedling growing in Pb mine tailings - Yu-Lin Han; Su-Zhen Huang; Hai-Yan Yuan; Jiu-Zhou Zhao; Ji-Guang Gu (Ecotoxicology, 2013)

Spatiotemporal heterogeneity of Moso bamboo aboveground carbon storage with Landsat Thematic Mapper images: a case study from Anji County, China - Ning Han; Huaqiang Du; Guomo Zhou; Xiaojun Xu; Ruirui Cui; Chengyan Gu (International Journal of Remote Sensing, 2013)

Zircon U–Pb–Hf isotopes and bulk-rock geochemistry of gneissic granites in the northern Jiamusi Massif, Central Asian Orogenic Belt: implications for Middle Permian collisional orogeny and Mesoproterozoic crustal evolution - Pei-Long Cui; Jing-Gui Sun; Shi-Jiong Han; Peng Zhang; Yong Zhang; Ling-An Bai; A-Lei Gu (International Geology Review, 2013)

Research on wind-induced responses of a large-scale membrane structure - Xuanyi Zhou; Zhihui Han; Ming Gu; An-an Zhang; Weiyu Zhang; Wei Fang (Earthquake Engineering and Engineering Vibration, 2013)

Synthesis of novel spirooxindolo-pyrrolidines, pyrrolizidines, and pyrrolothiazoles via a regioselective three-component [3+2] cycloaddition and their preliminary antimicrobial evaluation - Guansheng Wu; Liang Ouyang; Jie Liu; Shi Zeng; Wei Huang; Bo Han; Fengbo Wu; Gu He; Mingli Xiang (Molecular Diversity, 2013)

De novo transcriptome analysis of an Arctic microalga, Chlamydomonas sp. - Sanghee Kim; Min Jung Kim; Min Gui Jung; Sooyong Lee; Ye-Seul Baek; Sung-Ho Kang; Han-Gu Choi (Genes & Genomics, 2013)

SENP2 regulates MEF2A de-SUMOylation in an activity dependent manner - Han Lu; Bin Liu; Shengwu You; Lei Chen; Qu Dongmei; Minjie Gu; Yan Lu; Yingyi Chen; Fujun Zhang; Buwei Yu (Molecular Biology Reports, 2013)

Coordinated regulation of anthocyanin biosynthesis through photorespiration and temperature in peach (Prunus persica f. atropurpurea) - Ying Zhou; Dong Guo; Jing Li; Jun Cheng; Hui Zhou; Chao Gu; Sue Gardiner; Yue-Peng Han (Tree Genetics & Genomes, 2013)

The relationship between carbon and nitrogen stable isotopes of zooplankton and select environmental variables in low-latitude reservoirs - Wei Hou; Binhe Gu; Huajun Zhang; Jiguang Gu; Bo-Ping Han (Limnology, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Mitochondrial dysfunction and cellular metabolic deficiency in Alzheimer’s disease - Xue-Mei Gu; Han-Chang Huang; Zhao-Feng Jiang (Neuroscience Bulletin, 2012)

Determination of methylmercury in marine fish from coastal areas of Zhejiang, China - Zhu Huang; Xiao-Dong Pan; Jian-Long Han; Ping-Gu Wu; Jun Tang; Ying Tan (Food Additives & Contaminants Part B-Surveillance, 2012)

A polysaccharide-degrading marine bacterium Flammeovirga sp. MY04 and its extracellular agarase system - Wenjun Han; Jingyan Gu; Qiujie Yan; Jungang Li; Zhihong Wu; Qianqun Gu; Yuezhong Li (Journal of Ocean University of China, 2012)

Abiotic oxidation of Mn(II) and its effect on the oxidation of As(III) in the presence of nano-hematite - Xu Han; Yi-Liang Li; Ji-Dong Gu (Ecotoxicology, 2012)

Survivals of D. galeata in sub-tropical reservoirs: harmful effects of toxic cyanobacteria in food source - Bo-Ping Han; Xian Lin; Lamei Lei; Jiguang Gu (Ecotoxicology, 2012)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

Novel de novo nonsense mutation of FBN1 gene in a patient with Marfan syndrome - YOUNG-HWA SONG; GU-HWAN KIM; HAN-WOOK YOO; JUNE-BUM KIM (Journal of Genetics, 2012)

The mitochondrial genomes of Cambaroides similis and Procambarus clarkii (Decapoda: Astacidea: Cambaridae): the phylogenetic implications for Reptantia - Sanghee Kim; Mi‐Hyun Park; Jae‐Ho Jung; Dong‐Ha Ahn; Tahera Sultana; Sejoo Kim; Joong‐Ki Park; Han‐Gu Choi; Gi‐Sik Min (Zoologica Scripta, 2012)
Kim, S., Park, M.‐H., Jung, J.‐H., Ahn, D.‐H., Sultana, T., Kim, S., Park, J.‐K., Choi, H.‐G. & Min, G.‐S. (2012). The mitochondrial genomes of Cambaroides similis and Procambarus clarkii (Decapoda: Astacidea: Cambaridae): the phylogenetic implications for Reptantia. — Zoologica Scripta , 41 , 281–292. We determined the complete mitochondrial (mt) genome sequences of two northern hemisphere freshwater crayfish species, Cambaroides similis and Procambarus clarkii (Decapoda: Astacidea: Cambaridae). These species have an identical gene order with typical metazoan mt genome compositions. However, their gene arrangement was very distinctive compared with the pan‐crustacean ground pattern because of the presence of a long inverted block, which included 19 coding genes and a control region (CR). Because the CR was inverted, their nucleotide frequencies showed a reversed strand‐specific bias compared with the other decapods. Based on a comparative analysis of mt genome arrangements between southern and northern hemisphere crayfish and their putative close marine relative ( Homarus americanus , a true clawed lobster), we postulated that the ancestor of freshwater crayfish had a typical pan‐crustacean mtDNA gene order, similar to its marine relatives. Based on this assumption, we traced the most parsimonious gene rearrangement scenario of the northern hemisphere crayfish. In a phylogenetic study on the infraordinal relationships in reptan decapods, the lineage Lineata [Thalassinidea (Brachyura, Anomura)] was well supported, while the infraorder positions of Achelata and Astacidea remained unidentified.

The expression changes of Numblike in rat brain cortex after traumatic brain injury - Shengyang Jiang; Xiaohong Wu; Yaohua Yan; Jian Xu; Bai Shao; Xun Zhuang; Yingying Han; Xiaosong Gu (Journal of Molecular Histology, 2012)

Differentially expressed proteins associated with myogenesis and adipogenesis in skeletal muscle and adipose tissue between bulls and steers - Qiankun Zhang; Hong-Gu Lee; Jung-A Han; Sang Kee Kang; Nam Kyung Lee; Myunggi Baik; Yun-Jaie Choi (Molecular Biology Reports, 2012)

Effects of carbon black to inflammation and oxidative DNA damages in mouse macrophages - Kyung-Taek Rim; Soo-Jin Kim; Jeong-Hee Han; Min-Gu Kang; Jong-Kyu Kim; Jeong-Sun Yang (Molecular & Cellular Toxicology, 2011)

LysGH15B, the SH3b Domain of Staphylococcal Phage Endolysin LysGH15, Retains High Affinity to Staphylococci - Jingmin Gu; Rong Lu; Xiaohe Liu; Wenyu Han; Liancheng Lei; Yu Gao; Honglei Zhao; Yue Li; Yuwen Diao (Current Microbiology, 2011)

A linkage map of cultivated cucumber (Cucumis sativus L.) with 248 microsatellite marker loci and seven genes for horticulturally important traits - Han Miao; Shengping Zhang; Xiaowu Wang; Zhonghua Zhang; Man Li; Shengqi Mu; Zhouchao Cheng; Ruowei Zhang; Sanwen Huang; Bingyan Xie; Zhiyuan Fang; Zhenxian Zhang; et al. (Euphytica, 2011)

Association of hypomethylation of LINE-1 repetitive element in blood leukocyte DNA with an increased risk of hepatocellular carcinoma - Jian-zhong Di; Xiao-dong Han; Wen-ye Gu; Yu Wang; Qi Zheng; Pin Zhang; Hui-min Wu; Zhong-zheng Zhu (Journal of Zhejiang University-SCIENCE B, 2011)

The internalization pathway, metabolic fate and biological effect of superparamagnetic iron oxide nanoparticles in the macrophage-like RAW264.7 cell - JingLi Gu; HaiFei Xu; YeHua Han; Wei Dai; Wei Hao; ChunYu Wang; Ning Gu; HaiYan Xu; JiMin Cao (Science China Life Sciences, 2011)

Temporal and Spatial Expression of Cyclin H in Rat Spinal Cord Injury - Gang Wu; Jianhua Cao; Chen Peng; Huiguang Yang; Zhiming Cui; Jian Zhao; Qiyun Wu; Jiangli Han; Honghui Li; Xingxing Gu; Feng Zhang (NeuroMolecular Medicine, 2011)

Imprinting and expression analysis of a non-coding RNA gene in the mouse Dlk1-Dio3 domain - Feng Wei Zhang; Tie Bo Zeng; Zheng Bin Han; Hong Juan He; Yan Chen; Ning Gu; Hui Jie Jiang; Qiong Wu (Journal of Molecular Histology, 2011)

Molecular phylogenetic assessment of the genus Hyphodiscus with description of Hyphodiscus hyaloscyphoides sp. nov. - Tsuyoshi Hosoya; Jae-Gu Han; Gi-Ho Sung; Yumiko Hirayama; Kazuaki Tanaka; Kentaro Hosaka; Isshin Tanaka; Hyeon-Dong Shin (Mycological Progress, 2011)

Efficient Intracellular Gene Delivery Using the Formulation Composed of Poly (L-glutamic Acid) Grafted Polyethylenimine and Histone - Jingjing Deng; Yuting Wen; Cuifeng Wang; Shirong Pan; Huaiyu Gu; Xin Zeng; Lina Han; Yuefang Zhao; Min Feng; Chuanbin Wu (Pharmaceutical Research, 2011)

Genotype-phenotype correlations in Chinese patients with TGFBI gene-linked corneal dystrophy - Yan Long; Yang-shun Gu; Wei Han; Xiu-yi Li; Ping Yu; Ming Qi (Journal of Zhejiang University-SCIENCE B, 2011)

Characterization of carbohydrate combining sites of Bryohealin, an algal lectin from Bryopsis plumosa - Min Gui Jung; Key Pyoung Lee; Han-Gu Choi; Sung-Ho Kang; Tatyana A. Klochkova; Jong Won Han; Gwang Hoon Kim (Journal of Applied Phycology, 2010)

Axenic purification and cultivation of an Arctic cyanobacterium, Nodularia spumigena KNUA005, with cold tolerance potential for sustainable production of algae-based biofuel - Ji-Won Hong; Han-Gu Choi; Sung-Ho Kang; Ho-Sung Yoon (Algae, 2010)

Brown algae (Phaeophyceae) from Russian Far Eastern seas: re-evaluation of Laminaria multiplicata Petrov et Suchovejeva - Tatyana A. Klochkova; Gwang-Hoon Kim; Kyung-Min Lee; Han-Gu Choi; Mihail N. Belij; Nina G. Klochkova (Algae, 2010)

Human dermal fibroblast proliferation activity of usimine-C from Antarctic lichen Ramalina terebrata - Sung Gu Lee; Hye Yeon Koh; Hyuncheol Oh; Se Jong Han; Il-Chan Kim; Hong Kum Lee; Joung Han Yim (Biotechnology Letters, 2010)

Object-oriented classification of high-resolution remote sensing imagery based on an improved colour structure code and a support vector machine - Haitao Li; Haiyan Gu; Yanshun Han; Jinghui Yang (International Journal of Remote Sensing, 2010)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

Polybrominated Diphenyl Ethers in the Atmosphere of Taizhou, a Major E-Waste Dismantling Area in China - Wenliang Han; Jialiang Feng; Zeping Gu; Duohong Chen; Minghong Wu; Jiamo Fu (Bulletin of Environmental Contamination and Toxicology, 2009)

Availability and mobility of heavy metal fractions related to the characteristics of the coastal soils developed from alluvial deposits - Jinling Li; Ming He; Wei Han; Yifan Gu (Environmental Monitoring and Assessment, 2009)

Cloning, expression and characterization of a new agarase-encoding gene from marine Pseudoalteromonas sp. - Xinzhi Lu; Yan Chu; Qianqian Wu; Yuchao Gu; Feng Han; Wengong Yu (Biotechnology Letters, 2009)

Effect of the behavior and availability of heavy metals on the characteristics of the coastal soils developed from alluvial deposits - Jinling Li; Ming He; Shouqin Sun; Wei Han; Youchi Zhang; Xiaohui Mao; Yifan Gu (Environmental Monitoring and Assessment, 2009)

Sequential Extractions and Isotope Analysis for Discriminating the Chemical Forms and Origins of Pb in Sediment from Liaodong Bay, China - Bing Xu; Zhaoyan Gu; Jingtai Han; Yanhui Zhang; Yongfu Chen; Yanwu Lu (Archives of Environmental Contamination and Toxicology, 2009)

Conserved expression of the PRELI domain containing 2 gene (Prelid2) during mid-later-gestation mouse embryogenesis - Mengya Gao; Qi Liu; Fengwei Zhang; Zhengbin Han; Tiantian Gu; Weiming Tian; Yan Chen; Qiong Wu (Journal of Molecular Histology, 2009)

Anti-angiogenesis effect of generation 4 polyamidoamine/vascular endothelial growth factor antisense oligodeoxynucleotide on breast cancer in vitro - Shan-zhi Gu; Xin-han Zhao; Ling-xiao Zhang; Li Li; Zhi-yu Wang; Min Meng; Gai-li An (Journal of Zhejiang University-SCIENCE B, 2009)

A new gliotoxin analogue from a marine-derived fungus Aspergillus fumigatus Fres - Wen Ying Zhao; Tian Jiao Zhu; Xiao Xian Han; Guo Tao Fan; Hong Bing Liu; Wei Ming Zhu; Qian Qun Gu (Natural Product Research, 2009)

Hypertonic saline resuscitation reduces apoptosis of intestinal mucosa in a rat model of hemorrhagic shock - Yuan-qiang Lu; Wei-dong Huang; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2008)

Tolerance and accumulation of lead by species of Iris L. - Yu-Lin Han; Su-Zhen Huang; Ji-Guang Gu; Shuo Qiu; Jie-Min Chen (Ecotoxicology, 2008)

Clinical investigation of surgery for intermittent exotropia - Chong-qing Yang; Ye Shen; Yang-shun Gu; Wei Han (Journal of Zhejiang University-SCIENCE B, 2008)

Cadmium tolerance and accumulation by two species of Iris - Yu-Lin Han; Hai-Yan Yuan; Su-Zhen Huang; Zhi Guo; Bing Xia; Jiguang Gu (Ecotoxicology, 2007)

Mammary tumor modifiers in BALB/cJ mice heterozygous for p53 - Joanna G. Koch; Xiangjun Gu; Younghun Han; Adel K. El-Naggar; Melissa V. Olson; Daniel Medina; D. Joseph Jerry; Anneke C. Blackburn; Gary Peltz; Christopher I. Amos; Guillermina Lozano (Mammalian Genome, 2007)

Vegetation of Barton Peninsula in the neighbourhood of King Sejong Station (King George Island, maritime Antarctic) - Ji Hee Kim; In-Young Ahn; Kyu Song Lee; Hosung Chung; Han-Gu Choi (Polar Biology, 2007)

Direct evidence that two cysteines in the dopamine transporter form a disulfide bond - Rong Chen; Hua Wei; Erik R. Hill; Lucy Chen; Liying Jiang; Dawn D. Han; Howard H. Gu (Molecular and Cellular Biochemistry, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Expression of Helicobacter pylori urease subunit B gene in transgenic rice - Qing Gu; Ning Han; Jianyi Liu; Muyuan Zhu (Biotechnology Letters, 2006)

Morphology and Molecular Data for Antarctic Cryophilic Microalga, Porosira pseudodenticulata - Woong-Sic Jung; Hyoung-Min Joo; Sung-Soo Hong; Jae-Shin Kang; Han-Gu Choi; Sung-Ho Kang (Algae, 2006)

Diversity of centromeric repeats in two closely related wild rice species, Oryza officinalis and Oryza rhizomatis - Weidong Bao; Wenli Zhang; Qiuying Yang; Yu Zhang; Bin Han; Minghong Gu; Yongbiao Xue; Zhukuan Cheng (Molecular Genetics and Genomics, 2006)

Cloning of Helicobacter pylori urease subunit B gene and its expression in tobacco (Nicotiana tabacum L.) - Qing Gu; Ning Han; Jianyi Liu; Muyuan Zhu (Plant Cell Reports, 2005)

Large-scale identification and characterization of genetic variants in asthma candidate genes - Jae-Jung Kim; Hyun-Hee Kim; Joo-Hyun Park; Ha-Jung Ryu; JuYoung Kim; Songmean Moon; Haeok Gu; Hung-Tae Kim; Jong-Young Lee; Bok-Ghee Han; Chan Park; Kuchan Kimm; et al. (Immunogenetics, 2005)

Heat shock protein 70 as an indicator of early lung injury caused by exposure to arsenic - Sung Gu Han; Vince Castranova; Val Vallyathan (Molecular and Cellular Biochemistry, 2005)

DNA Sequences and Identification of Porphyra Cultivated by Natural Seeding on the Southwest Coast of Korea - Mi-Sook Hwang; Sun-Mi Kim; Dong-Soo Ha; Jae-Min Baek; Hyeung-Seop Kim; Han-Gu Choi (Algae, 2005)

Detection and recovery of hydrolytic enzymes from spent compost of four mushroom species - Han Gyu Ko; Sang Ho Park; Seong Hwan Kim; Hyuk Gu Park; Won Mok Park (Folia Microbiologica, 2005)

Nuclear DNA Quantification of Some Ceramialean Algal Spermatia by Fluorescence Microscopic Image Processing and their Nuclear SSU rDNA Sequences - Han-Gu Choi; Eun-Young Lee; Yoon-Sik Oh; Hyung-Seop Kim; In-Kyu Lee (Algae, 2004)

Developing gene-tagged molecular markers for functional analysis of starch-synthesizing genes in rice (Oryza sativa L.) - Xinyan Liu; Minghong Gu; Yuepeng Han; Qing Ji; Jufei Lu; Shiliang Gu; Rong Zhang; Xin Li; Jianmin Chen; Schuyler S. Korban; Mingliang Xu (Euphytica, 2004)

A Rapid DNA Extraction Method for RFLP and PCR Analysis from a Single Dry Seed - Hee Wan Kang; Yong Gu Cho; Ung Han Yoon; Moo Young Eun (Plant Molecular Biology Reporter, 1998)

Nucleotide sequence of the human? 1-globin gene - J. M. Gonzalez-Redondo; I. S. Han; Y. -C. Gu; T. H. J. Huisman (Biochemical Genetics, 1988)